Magnet-absorbed detrital magnetite from the western Qaidam Basin: Implications to Mars sample return missions - Qi-Tao Hu; Wen-Ping Liu; Qi-Zhi Yao; Shao-Bing Zhang; Wan-Cai Li; Sheng-Quan Fu; Yi-Liang Li; Gen-Tao Zhou (Icarus, 2026)

Deep neural network-based prediction of sauce-flavor Baijiu fermentation process and regulation of flavor compound synthesis - Shiyuan Ma; Wei Cheng; Zhongfu Duan; Dan Huang; Ping Huang; Qiuxia Li; Siyuan Zeng; Rongqing Zhou; Yadong Zhang; Jiao Niu; Chongde Wu; Yi Shen (Bioresource Technology, 2026)

Arsenic detoxification mediated by mutualistic cross-feeding in a thermophilic microbial consortium - Chun Qing; Yingjie Zhou; Yanhong Wang; Ping Li; Brian Hedlund (Bioresource Technology, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

A multi-dimensional early warning model for coal and gas outburst risk based on microseismic monitoring with seismic velocity tomography-identified risk zones - Chao Zhou; Bo Li; Dazhao Song; Xueqiu He; Zhenlei Li; Liming Qiu; Yingjie Zhao; Shan Yin; Jintao Dang; Ping Wang (Journal of Applied Geophysics, 2026)

A morphometric framework for Danxia landform classification incorporating cliff characteristics - Hui Chen; Ping Zhou; Fang Chen; Hongwei Li; Jongmin Byun; Ping Yan; Sha Lei; Xinmin Zhou (Geomorphology, 2026)

Microneedle patches at the bio-agricultural Interface: Toward precision, resilience, and sustainability - Fangzheng Zhou; Xiaochen Huang; Yaqi Teng; Ping Yu; Boqiang Li; Haowen Sun; Yixin Gao; Ruikun He; Wei Sun; Bei Fan; Xiaoxue Jia; Long Li; et al. (Food Research International, 2026)

Genetic diversity and distribution pattern of three economically important species of Bangiaceae (Rhodophyta) along China's coast revealed by rbcL - Meng-Xue Xu; Jia-Qiu Pu; Wei Zhou; Cui-Cui Tian; Guang-Ping Xu; Li-En Yang (Estuarine, Coastal and Shelf Science, 2026)

Constructing structure-charge dual-regulated nanofiltration membranes via swelling embedding strategy for efficient separation - Ping Li; Yuan Zhou; Chunxi Hai; Wenjie Liu; Ying Cheng; Yu Tang; Yanxia Sun; Shengde Dong; Luxiang Ma; Xin He; Qi Xu (Desalination, 2026)

Antibiotics affect the water purification performance and greenhouse gases emission mode in modular moving bed constructed wetland - Ping Deng; Hongyun Ma; Zhihao Luo; Lingwei Kong; Lei Zhou; Xueqi Zhang; Jianshi Huang; Yiqian Chen; Yiyang Li; Yuefang He; Shaole Yu; Shuiping Cheng (Chemical Engineering Journal, 2026)

Synthesis and valorization of corn silk-derived carbon dots for antimicrobial fruit preservation - Yong-Ping Wen; Meng-Ting Wu; Kwang-Pyo Kim; Meng-Yi Chen; Jia-Hui Liu; Ya-Ping Li; An-Guo Wu; Xiang Li; Song-Zhi Xie; Die Gao; Jian-Ming Wu; Xiao-Gang Zhou (International Journal of Food Microbiology, 2026)

Erosion rates in the northern coast of Southern China Sea: Insights from granitic cosmogenic nuclide depth profiles - Hao Liang; Ying Xu; Ziye Zhou; Zhen Chen; Yongjie Tang; Cong Chen; Ke Zhang; Ping Huang; Zhigang Li; Gege Hui; Yipeng Zhang; Qingying Tian; et al. (Geomorphology, 2026)

Scleroglucan from Agroathelia rolfsii ameliorates glucolipid metabolic dysfunction in high-fat diet-fed mice and is associated with gut microbiota and metabolite changes - Dafang Yin; Kairui Tong; Min Zhou; Ping Yu; Mengfan Lyu; Mine Yang; Yanlong Wen; Lianghua Wen; Yang Li; Yadong Zhong; Jielun Hu (Food Research International, 2026)

Dynamic characterization of volatile profiles and intelligent discrimination of raw Milk under frozen storage using non-targeted volatile metabolomics and machine learning - Ken Lu; Liqiong Niu; Ting Wen; Zhicong An; Chen Liu; Jiangfei Chai; Hongliang Li; Bei Zhou; Yongjing Bie; Chaokun Wei; Yan Ping Chen; Yuan Liu (Food Research International, 2026)

Rhamnolipids: from biosynthesis to applications - Ai-Ping Pang; Zhiqing Zhang; Guo-Zhao Li; Yun Wang; Kun Yang; Junping Zhou; Lianggang Huang; Li-Qun Jin; Zhi-Qiang Liu; Yu-Guo Zheng (Food Chemistry, 2026)

Integrated analysis of lipid remodeling and volatile evolution during refining of Antarctic krill oil - Xinya Huang; Meiyu Zheng; Jin Zhang; Jinglun Zhou; Qingyang Zhang; Zhengting Zhu; Ping Kong; Shu Wang; Bin Li; Zhigang Hu; Kangyu Zhao; Dongping He; et al. (Food Chemistry, 2026)

Beyond mortality: A multi-outcome assessment of health economic benefits from air pollution control in China - Hao-Wen Liao; Zhi-Ming Han; Guo-Ping Dong; Duo-Hong Chen; Min Xie; Jun Liu; Junyu Zheng; Yun-Ting Zhang; Haseeb Tufail Moryani; Muhammad Amjad; Yang Zhou; Wen-Wen Bao; et al. (Environmental Research, 2026)

Regulatory mechanisms of N2O emissions from latosolic red soil by different ecotypes of earthworms: Insights from microbial diversity and metagenomic analysis - Chang Wei; Chang-Wen Yun; Xiao-Qing Li; Lang-Hao Lai; Jian-Peng Gao; Meng-Ping Tang; Chun-Na Zhou; Yu-Long Zhang; Hui-Juan Xu (Environmental Pollution, 2026)

A tea exosome-integrated self‑oxygenating cascade chitosan/oxidized alginate hydrogel for remodeling the hyperglycemic and hypoxic microenvironment in diabetic wound healing - Li-Hua Xie; Xin-Hui Zhou; Wei-Qiu Wen; Wei Wang; Ping Gui; Li Li; Guan-Hai Wang (Carbohydrate Polymers, 2026)

How well do reanalysis datasets capture the onset dates of extreme temperature events in China? - Ping Zhou; Yan Wu; Zexiang Li; Yawen Yang; Chuchu Zhang; Dan Li; Shuishi Xie; Liangqing Wu; Keyuan Zhong (Meteorology and Atmospheric Physics, 2026)

Natural occurrence of a slow lytic pseudomonas phage in a Pediatric case of multidrug-resistant P. aeruginosa severe pneumonia - Jiaying Sun; Jingru Zhou; Long Wang; Dilare Lidifu; Ping Ni; Qin Li; Xuhua Zhang; Wei Li; Wujin Chen (Virus Genes, 2026)

From precipitation forecasts to optimal reservoir operation: an integrated downscaling-forecasting-operation framework for reservoir floodwater utilization - Libin Zhang; Keke Zhou; Yonggen Zhang; Jianzhu Li; Ping Feng; Zhanguo Sun; Qinghua Liu; Lutz Weihermüller (Journal of Hydrology, 2026)

Landscaping neurodevelopment of attention-deficit hyperactivity disorder - Ningning Liu; Yin-Shan Wang; Zi-Xuan Zhou; Peng Gao; Chongjing Luo; Xinyi Zhang; Ziqing Zhu; Yuan Gao; Fei Ren; Yan Zhu; Li-Zhen Chen; Haimei Li; et al. (Science Bulletin, 2026)

Chenietains A-G, undescribed phenylpropanoid-related compounds from Cheniella touranensis and their cytotoxic potential in vitro - Xing-Ping Zhang; Yun Wang; Jia-Le Wang; Wu-Yan Chen; Wen-Jie Ma; Yan-Heng Zhou; Ming-Ming Li; Kou Wang (Phytochemistry, 2026)

Effect of depth-direction SVF gradient on particle deposition performance in fibrous media - Ankang Zhou; Shihang Li; Jiahua Chai; Kunkun Tu; Hao Jin; Wenjie Liang; Shuda Hu; Fan Geng; Qiang Zhang; Wuping Peng; Ping Li (Journal of Aerosol Science, 2026)

Integrating water use efficiency dynamics into ecological function zoning: Patterns, drivers, and trade-offs - Libin Zhang; Jiaxing Zhang; Qiang Ma; Jianzhu Li; Keke Zhou; Ting Zhang; Ping Feng (Environmental Research, 2026)

Efficient antibiotic degradation by concentrated solar activation of trichloroisocyanuric acid: The role of triplet-state-mediated singlet oxygen generation - Yue Yang; Li Tang; Kun Chen; Ping Chen; Yixun Zheng; Bingbing Liu; Jin Wu; Shimin Zhou; Yongpeng Zhang; Yuxin Xian; Wenying Lv; Guoguang Liu (Chemical Engineering Journal, 2026)

Highly efficient perovskite-based electrocatalyst with in-situ nanoparticle exsolution and oxygen-vacancy enhancement for solid oxide cells - Tian Gan; Xinyu Zhou; Yujun Han; Wenya Zhen; Bin Sheng; Tianqi Li; Haoqi Yang; Ping Li; Yongdan Li (Chemical Engineering Journal, 2026)

Surface coordination-induced heterogeneous nucleation of hierarchical coatings enabling pyrolysis vapor-mediated post mineralization for adaptive protection - Chengliang Zhou; Yanli Liao; Yanlei Gao; Xin He; Ping Jiang; Xia Zheng; Suwen Yang; Xingong Li (Chemical Engineering Journal, 2026)

Molybdenum-functionalized thiolated chitosan repurposes aqueous V(V) as an in situ PMS activator for simultaneous organic degradation and vanadium recovery - Yating Wu; Ting Xiang; Lei Zhang; Ping Gao; Lei Li; Chensi Shen; Fang Li; Juan Zhou (Chemical Engineering Journal, 2026)

Scalable and recyclable copper-loaded aminated polyacrylonitrile fibers for humidity-enhanced hydrogen sulfide capture - Ke-Jiang Zhao; Kai Jiang; Guo-ping Li; Chao-Jun Wu; Gui-Zhou Xu; Zuo-Hua Huang; Zhen-Bang Tian (Chemical Engineering Journal, 2026)

From serpentinization to carbonation: Petrological and geochemical constraints from an ophiolitic reaction profile - Hong-Da Zheng; Qing Xiong; Xiang Zhou; Biao Chang; Hong-Kun Dai; Hong-Zhu Cai; Li Wang; Yi-Cong Li; Long-Fei Xue; Ming Chen; Jian-Ping Zheng (Chemical Geology, 2026)

Jasmonate and hydrogen sulfide interaction ameliorates maize seed germination under heat stress through consolidating antioxidant defense system - Xiao-Ping Luo; Hong-Dan Zhou; Mi-Xue Tu; Zhong-Guang Li (Protoplasma, 2026)

Projections of the timing of extreme temperature events in the future, China - Xiangming Xu; Yan Wu; Yawen Yang; Dan Li; Chuchu Zhang; Ping Zhou; Zexiang Li; Liangqing Wu; Keyuan Zhong (Climate Dynamics, 2026)

Bioactive prenylated acylphloroglucinols from Hypericum scabrum - Li-Ping Teng; Jie-Lian Huang; Shui-Qing Guan; Chen-Xi Xin; Zi-Yin Mai; Yik-Ling Chew; Zhong-Bo Zhou; Gencheng Liang (Natural Product Research, 2026)

Chloride ions-assisted high-efficiency natural seawater splitting enabled by noble-metal-free MnOx(OH)y/GaN nanowires - Yumeng Li; Liang Qiu; Xiantong Zheng; Lin Yao; Muhammad Salman Nasir; Zijian Huang; Ying Li; Yixin Li; Ding Wang; Wenxing Yang; Jianyang Zang; Ping Wang; et al. (Science Bulletin, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Fungal community succession drives the decay of jujube fruit (Ziziphus jujuba Mill. cv. Jingcang 1) during ambient storage - Jian-Yu Wang; Ke-Xin Jiao; Min-Xin Mao; Cheng-Gang Li; Jian-Ping Qu; Bo Zhou; Qian Zhang; Qing Hao (Postharvest Biology and Technology, 2026)

Benzophenone-2 disrupts craniofacial cartilage development via esr2a-Dependent inhibition of endothelin signaling in zebrafish larvae - Zhuoyi Xie; Keying Li; Xiaomai Zhou; Qiuchen Wu; Xiangrong Zhou; Ping Zeng; Jing Li; Qiao Niu; Zhipeng Qi; Xinying Zhao; Weiyi Song (Environmental Research, 2026)

Increasing particulate organic carbon export efficiency in Arctic River Basins: A study of emerging trends - Shiqi Liu; Ping Wang; Renjie Zhou; Jingjie Yu; Linsheng Yang; Zhiyang Li; Liudmila S. Lebedeva; Tianye Wang; Yiyang Ding (Science China Earth Sciences, 2026)

Study on the engineering characterization of stabilized cadmium-contaminated soil using MgO activated FA and GGBS - Cuihong Li; Yubo Zhou; Wei Wang; Shaoyun Pu; Na Li; Ping Jiang (Bulletin of Engineering Geology and the Environment, 2026)

Characterizing brain structural and functional abnormalities in borderline personality disorder by seed-based d mapping approach - Wanru Qiu; Sen Li; Aoxue Zhang; Hao Yu; Jian Cui; Yinghong Xu; Liangliang Ping; Hao Zheng; Chunyu Dong; Kun Li; Cong Zhou (Brain Imaging and Behavior, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Taxadendins A-P, previously undescribed abietane diterpenoids with diverse structures from the bark of Taxodium ascendens - Zhi-Ping Zhou; Wen-Yan Li; Qin-Shi Zhao (Phytochemistry, 2026)

Structural and rheological modulation of low-oil emulsions by deamidated pea protein–gum arabic coacervates for reduced-fat applications - Lijuan Luo; Ping Li; Yuanyuan Deng; Guang Liu; Yan Zhang; Xiaojun Tang; Pengfei Zhou; Zhihao Zhao; Jiarui Zeng; Mingwei Zhang (Food Chemistry, 2026)

Multi-dimensional analysis revealing the mechanism of T-2 toxin driving liver fibrosis: integration of network toxicology, machine learning, experimental verification, and molecular docking - Lichun Qiao; Shaoteng Shi; Liangjia Wang; Muhammad Aftab Shafiq; Jing Tang; Miaoqian Li; Ping Wan; Jingxuan Zhou; Xulei Dai; Jing Han; Yijie Guo (Chemico-Biological Interactions, 2026)

Defensive remodeling of gut microbiota under microplastic stress and its pathogenic mechanism - Penghua Jian; Feng Zhang; Zhihao Chen; Xuan Zhou; Yan Xiong; Qiang Hu; Yingyu Wang; Dan Li; Jiai Yan; Ju Yang; Hong Cao; Ping Wu; et al. (Chemico-Biological Interactions, 2026)

Preparation of C and Co co-doped TiO2 Nanomaterials for Visible-Light Photocatalytic Antibacterial Activity - Chunhui Meng; Yuena Li; Qitong He; Yue Hao; Wenjun Yin; Huang Zhou; Ping Li (Water, Air, & Soil Pollution, 2026)

Hydroxyapatite nanoparticles improve vitrified bovine MII oocyte developmental competence by reducing ultrastructural damage and modulating gene expression - Xiao-Xia Li; Yi-Hang Wang; Jun Wang; Shi-Yu Zhang; Jia-Hao Zhang; Shi-Han Zhao; Qi Yan; Ping-Hua Cao; Zi-Qiang Zhang; Chen Zhou; Zhen Zhang; Qiao-Ting Shi; et al. (Animal Reproduction Science, 2026)

Molecular characterization of a novel partitivirus isolated from Fusarium solani, the causal agent of tobacco root rot - Xiao Wu; Ying Wang; Rui Guo; Ya Rong Wang; Si Jun Li; Xiang Ping Zhou; Jie Zhong; Yan Song Xiao; Tian Bo Liu (Archives of Virology, 2026)

Anemoside B4 inhibits mitochondrial dysfunction-related mitophagy in asthma by regulating KAT2B/IRF3 axis - Hao Tang; Ping Li; Mingxia Shang; Zhiping Zhou; Xing Yang; Bin Liu (Molecular and Cellular Biochemistry, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Coupling between mobile genetic elements and potential sulfur cycling microorganisms is associated with antibiotic resistance gene distribution in coastal sediments - Li Chen; Diantao Ping; Danyu Zheng; Shan Zhou; Chaoyue Zhang; Qi Chen; Xiaohui Wang; Xuri Dong; Lixin Zhu (Journal of Environmental Chemical Engineering, 2026)

Corrigendum to “Sulfide-based denitrification of ship wastewater: Core bacteria succession and metabolic mechanism with different sulfite loadings” [J. Environ. Chem. Eng. 14 (2026) 122365] - Shuai Zhao; Wei Li; Ruonan Xin; Sini Zhou; Jianhua Wang; Lingxiao Lv; Yin Liu; Nan Li; Ping Guo (Journal of Environmental Chemical Engineering, 2026)

Swelling-thermal crosslinking engineered polyamide nanofiltration membranes for high-performance Mg2+/Li+ separation - Yu Tang; Shengde Dong; Ping Li; Ying Cheng; Wenjie Liu; Chuanjiang Cheng; Yanxia Sun; Qi Xu; Chunxi Hai; Yuan Zhou (Journal of Environmental Chemical Engineering, 2026)

Sulfide-based denitrification of ship wastewater: Core bacteria succession and metabolic mechanism with different sulfite loadings - Shuai Zhao; Wei Li; Ruonan Xin; Sini Zhou; Jianhua Wang; Lingxiao Lv; Yin Liu; Nan Li; Ping Guo (Journal of Environmental Chemical Engineering, 2026)

Mg–K isotopic compositions deciphering mantle heterogeneity beneath southeast Tibet - Qiong Chen; Hao Cheng; Guo-Chun Zhao; Mei-Fu Zhou; Ping-Ping Liu; Wen-Jun Li; Min Sun (Geochimica et Cosmochimica Acta, 2026)

In vitro simulated digestion of Ganoderma lucidum proteoglycan and its effects on gut microbiota in type 2 diabetic rats - Qianqian Zhang; Xinru Zheng; Jieying Chen; Ying Zhang; Jiaqi Li; Yingxin Wang; Yanna Pan; Fanzhen Yu; Zeng Zhang; Hongjie Yang; Yanming He; Ping Zhou (Food Bioscience, 2026)

Indoor Thermal Comfort Study of Office Buildings in Cold Regions of China Based on a Database: A Case Study of Beijing, Tianjin, and Dalian - Ping Chen; Xueying Li; Xiaoyi She; Hanyu Zhou; Kai Nan; Ming Zhang (Energy and Buildings, 2026)

Mutual activation of g-C3N4 and persulfate synchronizes rapid visible-light-triggered fabrication of multifunctional hydrogels - Mingming Deng; Dagang Zhou; Lin Luo; Boyi Fu; Ping Li; Qi Liu; Chi Huang (Chemical Engineering Journal, 2026)

Corrigendum to: “Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury” [Chem. Eng. J. 524 (2025) 169698] - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2026)

Based on the “biotin-streptavidin” system to construct exosome- linked hydrogel for promoting healing of chronic wounds in obesity by regulating the NF-κB pathway - Lingxiang Sun; Wenze Han; Yilin Ping; Xi Chen; Xuedong Deng; Zheng Wang; Jingjing Deng; Jian Zhou; Tingting Wu; Yifan Zhao; Xiuping Wu; Bing Li (Chemical Engineering Journal, 2026)

Corrigendum to “Quercetin attenuates cisplatin-induced mitochondrial apoptosis via PI3K/Akt mediated inhibition of oxidative stress in pericytes and improves the blood labyrinth barrier permeability” [Chemico-Biological Interactions 393 (2024) 110939] - Tian-lan Huang; Wen-jun Jiang; Zan Zhou; Tian-feng Shi; Miao Yu; Meng Yu; Jun-qiang Si; Yan-ping Wang; Li Li (Chemico-Biological Interactions, 2026)

Quantifying scale effects in pile scour depth prediction for field applications via interpretable machine learning - Yang-Xin Zhou; Qing-Kai Song; Wen-Gang Qi; Li-Jing Yang; Xiao-Bing Lu; Fu-Ping Gao (Coastal Engineering, 2026)

Optimal combination of iron/magnesium salts and urea can promote the degradation rate of maize straw by catalyzing the rapid de-polymerization of lignin - Han Li; Yuan fang Zhou; Sen Zhao; Si hui Yan; Ding hua Jia; Yan ping Zhang; Xiang dong Yang; Juan Li (Biocatalysis and Agricultural Biotechnology, 2026)

Graphitization of marine kerogen and its effects on nanopores and adsorption performance - Guangming Meng; Xianming Xiao; Haifeng Gai; Yanming Zhao; Yijie Xing; Kun Zhang; Yu Liu; Qin Zhou; Tengfei Li; Wei Liu; Peng Cheng; Ping Gao (Science China Earth Sciences, 2026)

Microscopic Hydraulic–Mechanical Coupling Fracturing Behavior and Failure Mechanisms of Reservoir Rocks - Zhi Zhao; Zhi-Hong Li; Yun-Gang Duan; Liang-Fu Xie; Zheng Li; Guo-Feng Yu; Xiao-Ping Zhou (Rock Mechanics and Rock Engineering, 2026)

A multicomponent Fc-fused subunit vaccine induces cross-protective immunity against porcine reproductive and respiratory syndrome virus QYYZ-like and NADC30-like strains - Linxing Tian; Zhengdan Lin; Mengxi Pan; Yanwen Wen; Mingxing Lu; Shudan Liu; Chao Zhang; Zhenxiang Rong; Jiahui Ma; Ruiqu Zhou; Nan Cao; Xinghua Chen; et al. (Veterinary Microbiology, 2026)

Triphasic volatile emission dynamics and gene expression in postharvest PGF-lost non-melting peach (Prunus persica) var. RedY - Ping Zhou; Xiaodan Zhang; Xin Feng; Rui Guo; Shaobin Yan; Xiuqing Wei; Liang Li; Yajun Tang; Zhizheng Fang; Yan Lei (Postharvest Biology and Technology, 2026)

Structural dynamics of chloroplast genome in Paphiopedilum (Orchidaceae): in response to natural hybridization - Xue-Ying Wei; Ai-Qun Hu; Jin Zhou; Jiang-Ping Shu; Wei-Yue Sun; Li-Qiang Li; Jian-Wen Shao; Hui Wang; Yue-Hong Yan (Molecular Phylogenetics and Evolution, 2026)

Detecting drought propagation pathways in different climatic regions of China - Zhaoqiang Zhou; Linqi Li; Yibo Ding; Yiyang Zhao; Haiyun Shi; Renjie Hou; Ping Wang; Ping Xue; Tian Wang; Peng Chen (Journal of Hydrology, 2026)

Metagenomics-based insights into the microbial community composition and quality characteristics development potentiality in traditional dry-cured ham - Ping Li; Yang Wang; Zhijie Bao; Xiaoyu He; Sunyan Wang; Xinlian Su; Wen Nie; Feiran Xu; Hui Zhou; Han Li; Baocai Xu (International Journal of Food Microbiology, 2026)

Lactiplantibacillus plantarum ZJ316 synergizes with tryptophan diet to modulate gut microbiota and metabolite profiles in mice - Qingqing Zhou; Yingying Zhou; Lu Li; Kening Fu; Shibo Liu; Ping Li; Qing Gu (Food Bioscience, 2026)

Impacts of diverse urbanization scenarios on typhoon precipitation patterns in the Pearl River Delta: A case study of Typhoon Mangkhut - Yongwei He; Zhongming Gao; Yulong Ma; Ping Zhou; Jingyu Yao; Xixi Yang; Lei Li (Atmospheric Research, 2026)

Long-term organic amendments accelerate straw decomposition via specialized microbial enrichment in greenhouse vegetable soils - Long Ma; Shaowen Huang; Dali Song; Chao Ai; Ruonan Li; Liying Wang; Ping He; Wei Zhou (Applied Soil Ecology, 2026)

Application of Magnetic-Seismic Geophysical Prospecting Technology in Identifying the Carboniferous Volcanic Rocks in the Chepaizi, West Margin of Junggar Basin - Guo-hua Jiao; Wei-ping Zhang; Jin-ke Zhou; Fu-gang Sun; Hai-tao Yang; Man Li; Zhu-qiang Li (Applied Geophysics, 2026)

An impact-based drought classification method using real-world agricultural drought records and explainable automated machine learning - Keke Zhou; Jianzhu Li; Ting Zhang; Xiaogang Shi; Ping Feng (Journal of Hydrology, 2026)

Thermal degradation kinetics and behavior of MPN from Ginkgo biloba - Yu Kong; Yi-yuan Zhou; Ya-ping Wang; Xiao-fang Wang; Shan Duan; Mo-wen Su; Juan Zhao; Li-min Wang; Qing Kang; Xin-jun Du (Journal of Food Engineering, 2026)

Partitioned N-TiO2–N-TiO2@SWCNT/PET composite fabric for industrial wastewater habitat reconstruction and potential cross-niche carbon sequestration - Jian Qiu; Yang Hu; Ying Chen; Shilong Li; Yudong Yuan; Bin Chen; Ping Shi; Jianfa Zhao; Wenheng Jing; Wei Zhou; Yuan Bai; Lele Cui; et al. (Journal of Environmental Chemical Engineering, 2026)

Lactic acid bacteria diversity in traditional fermented dairy products: Seasonal influences and microbial interactions - Jie Zhao; Yangbo Jiao; Ping Du; Dan Wang; Yu Li; Xin Su; Shuaili Zheng; Liang Zhou; Jiaqi Xie; Jie Yu (Food Bioscience, 2026)

Zircon thermal annealing ages determine a late Eocene birth for the First Bend of the Yangtze River - Yang Zhang; Rui Li; Guang-Yan Zhou; David Chew; Jian-Ping Zheng; Qing Xiong; Wei Wang (Earth and Planetary Science Letters, 2026)

MnO2/CNT-Modified Anode Microbial Fuel Cells for Removing Varying Amounts of Cu2+ from Wastewater - Jiahui Zhu; Lingling Li; Jun Zhou; Nasha Dou; Lei Gong; Mingjing Li; Hui Tan; Ping Yang; Wenfeng Wang (Water, Air, & Soil Pollution, 2026)

Endometrial microbiota-dimethylglycine-Treg cell axis affects endometrial receptivity in recurrent implantation failure - Fen-Ting Liu; Ping Zhou; Feng Deng; Bao-Ying Liao; Zi Yang; Di Sun; Heng Pan; Yang Yu; Shuo Yang; Rong Li (Science China Life Sciences, 2026)

Rapid selection of early-maturing and low-ear position maize hybrids suitable for China using genomic prediction - Ping Luo; Wenzhe Li; Lin Zhang; Jie Yang; Houwen Wang; Fei Wang; Ruisi Yang; Xinlong Xu; Ke Yang; Hongjun Yong; Mingshun Li; Jianfeng Weng; et al. (Plant Molecular Biology, 2026)

Functional Characterization of CsFBK, an F-Box Gene from Camellia Sinensis, Reveals its Negative Regulation of Leaf Angle in tea and Tobacco - Yongqing Bai; Bokun Zhou; Tong Li; Ping Li; Shiyu Tian; Xinzhuan Yao; Litang Lu (Journal of Plant Growth Regulation, 2026)

Mantle dunites archive multistage melt metasomatism under a fossil slow-ultraslow spreading center: an example from the Tibetan Xigaze ophiolite - Li Wang; Qing Xiong; Hong-Kun Dai; Xiang Zhou; Hong-Da Zheng; Hao-Qin Sun; Yi-Cong Li; Long-Fei Xue; Alessio Sanfilippo; Valentin Basch; Jian-Ping Zheng (Contributions to Mineralogy and Petrology, 2026)

In-situ Elemental and Boron Isotopic Geochemistry of Tourmalines from Pegmatites in the Edanggang Li-Be Deposit in the Quanji Massif, NW China - Xuan Zhou; Tong Pan; Shan-Ping Li; Qing-Feng Ding (Journal of Earth Science, 2026)

DMSN@AuNPs-enhanced QCM immunosensor array for non-invasive and highly sensitive detection of Cyfra21-1 in saliva - Xiaojing Zhang; Hongyang Guo; Li Sin Wong; Hangming Xiong; Liubing Kong; Guangqing Ren; Yanjie Hu; Yong Zhou; Shuaike Zheng; Li Zhang; K. Jimmy Hsia; Hao Wan; et al. (Analytica Chimica Acta, 2026)

Clonal hematopoiesis mutation is associated with risk of incident lung cancer and death - Ying Zhu; Chen Zhu; Ping Li; Ruiqi Ma; Dan Zhou; Kai Li; Jianzheng Zhang; Qiang Tong (GeroScience, 2026)

High-loading single-atom photocatalysts for high-selectivity conversion of CO2 to ethanol - Long-Shuai Zhang; Feiyao Wu; Shenrui Liang; Qianqian Tang; Hui Li; Huang Zhou; Fanqi Meng; Xunheng Jiang; Haiyan Liu; Qing Sun; Meifeng Wu; Yitao Cui; et al. (Science Bulletin, 2026)

Fate and risk of pesticides in drinking water: From source to tap using a comprehensive analysis and prioritization approach - Tingting Yang; Feng Ge; Yuan Hong; Yixuan Wang; Gang Zhou; Huimin Chen; Ninghui Song; Ping Li (Journal of Environmental Sciences, 2026)

Synergistic technology of liquid nitrogen condensation integrated with pressure swing adsorption for CH4/VOCs recovery: modeling, experiment, and optimization - Suiyang Han; Weiqiu Huang; Xufei Li; Yankang Zhou; Xinchen Tian; Zhanyou He; Fangrui Feng; Ping Xia; Wenlong Xu (Fuel, 2026)

Impact of boiling-drying regimes on milling properties, digestion characteristics, and multi-scale starch structure of parboiled rice - Yi Wang; Jiarui Zeng; Yuying He; Guang Liu; Pengfei Zhou; Ping Li; Zhihao Zhao; Mingwei Zhang; Cuiping Yi; Yuanyuan Deng (Food Research International, 2026)

Reveaing the dynamic changes of non-volatile metabolites and taste evolution of Duyun Maojian tea during the processing - Xiaolu Zhou; Qian Wang; Nguyen Huy Hoang; Ping Li; Jiacai Wang; Caibi Zhou; Shanggao Liao (Food Chemistry, 2026)

An innovative triple-channel probing strategy for ultrasensitive detection of quercetin in food matrices based on carbon dots - Ping Li; Zhen-quan Yang; Lixia Xiao; Xuechao Xu; Tianzu Guan; Wenyuan Zhou; Xiaowei Tang; Xiaojuan Gong; Qin Hu (Food Chemistry, 2026)

Enhancement of protein gelation and nutritional properties in pea protein gels through enzymatic deamidation - Lijuan Luo; Ping Li; Yuanyuan Deng; Guang Liu; Yan Zhang; Xiaojun Tang; Pengfei Zhou; Zhihao Zhao; Jiarui Zeng; Mingwei Zhang (Food Hydrocolloids, 2026)

Dual impact of ambient pH on the virulence of Phytophthora nicotianae and resistance in tobacco - Wenqiu Du; Li Zhou; Ping Li; Lijuan Peng; Yuhan He (Plant Cell Reports, 2026)

Corynoline promotes apoptosis and inhibits proliferation of glioblastoma via regulating the STAT3/Bcl-2 signalling pathway - Yu Xiong; Wenyuan Ji; Jianjun Zhou; Shenghua Liu; Lusheng Li; Xuan Zhai; Bin Zou; Ligang Chen; Ping Liang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Immune modulation of Spodoptera litura larvae parasitized by Meteorus pulchricornis and role of the host β-1, 3-glucan-binding protein in parasitism success - Yan Song; Zhi-Xiang Liu; Feng-ming Gu; Ping Li; Wei-Hong Zhou; Jun Wang; Fu-An Wu; Sheng Sheng (Pesticide Biochemistry and Physiology, 2026)

Iron: A double-edged sword of female reproductive health - Rui Mao; Dan Yin; Wenbo Lv; Die Wang; Ying Ouyang; Cuilan Zhou; Jun Liu; Suyun Li; Yunhua Zhu; Ping Yu; Hongqing Liao; Cuiying Peng (Journal of Trace Elements in Medicine and Biology, 2026)

Nanopore characteristics of lower Cambrian shale based on gas adsorption and multifractal analysis: Implications for gas development and CO2 storage - Wei Liu; Xianming Xiao; Ping Gao; Yanming Zhao; Yijie Xing; Qizhang Fan; Guangming Meng; Jinku Li; Qin Zhou; Tengfei Li; Siyi Liu (Fuel, 2026)

Lactic acid bacteria in Jiangxiangxing Baijiu fermentation: Resource exploration, community succession and their ecological dynamics - Pan Huang; Zhongfu Duan; Shiyuan Ma; Wei Cheng; Qiuxia Li; Dan Huang; Ping Huang; Rongqing Zhou; Jiao Niu; Yadong Zhang; Chongde Wu (Food Bioscience, 2026)

Simultaneous activation of pyroptosis and cGAS-STING pathway with iridium(III) thiophene complexes for enhanced oral squamous cell carcinoma sono-immunotherapy - Jia-Wen Chen; Peng Wang; Jia-Ying Zhou; Yi-Fei Luo; Yi-Ling Li; Jia-Yin Wu; Ling-Ran Li; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

Interspecific interactions increase soil aggregate stability through altered root traits in long-term legume/maize intercropping - Xiao-Yang Duan; Surigaoge Surigaoge; Yu-He Du; Dai-Han Fu; Hao Yang; Xin Yang; Huai-Yin Ma; Hu Zhou; Peter Christie; Dario Fornara; Wei-Ping Zhang; Long Li (Soil and Tillage Research, 2026)

Responses of mesozooplankton to extreme positive Indian Ocean Dipole (pIOD) and cold-core eddy in the eastern Equatorial Indian Ocean and southern Bay of Bengal during 2019/2020 winter - Ping Du; Xiao Ma; Yuanli Zhu; Ruijie Ye; Shenran Zhang; WNC Priyadarshani; P.A.K.N. Dissanayake; Haifeng Zhang; Yibo Liao; Yanbin Tang; Zhibing Jiang; Hongliang Li; et al. (Progress in Oceanography, 2026)

Enhancing free hydroxyl radical generation via noble metal-modified TiO₂ for efficient benzisothiazolinone degradation with reduced H₂O₂ consumption - Meng Xu; Xiao-qing Dong; Li-fang Chen; Ping Yu; Xin-yu Li; Shan-shan Lv; Ya-wen Qi; Wei Zhang; Peng Jiang; Xiao-long Zhou (Journal of Water Process Engineering, 2026)

Assessment of monthly vegetation response and ecosystem risks to drought-flood abrupt alternation using an integrated framework - Boyuan Yang; Keke Zhou; Jianzhu Li; Ping Feng; Xuejun Yang (Journal of Hydrology, 2026)

Organ-level translocation and tissue-specific accumulation of micro- and nanoplastics in wild birds - Mengzhu Wang; Shirui Wang; Pinxi Zhou; Hongcheng Shan; Shangmingyu Zhang; Zhixiong Yang; Yibo Wang; Zhengrui Hu; Jiayu Zhang; Yi Wu; Xinyu Lu; Zhiqiang Li; et al. (Journal of Hazardous Materials, 2026)

Effects of biochar on farmland soil aggregate stability and phosphorus desorption - Ping Xue; Tianxiao Li; Qiang Fu; Renjie Hou; Mo Li; Song Cui; Zhaoqiang Zhou; Qinglin Li; Fanying Kong (Journal of Environmental Management, 2026)

Iron-driven synergism among microbial functional taxa facilitates recovery from denitrification toxicity - Yongzhi Zhang; Xiaoxiao Li; Linjun Gao; Ping Ye; Rui Wang; En Zhou; Tian Sun; Miaoqing Xu; Rui Wan; Xiang Li (Journal of Environmental Management, 2026)

Algae: A considerable regulator of methylmercury in mercury-contaminated paddy fields - Ling Su; Guangjun Luo; Tianrong He; Pan Wu; Ping Li; Deliang Yin; Yuping Xiang; Xian Zhou (Journal of Environmental Sciences, 2026)

Nitrate reduction of dissolved organic carbon exported by episodic upwelling: A novel explanation for negative carbon isotope excursions during the Ediacaran–Cambrian transition - Guangming Meng; Haifeng Gai; Yaowen Wu; Ping Gao; Chengang Lu; Qin Zhou; Tengfei Li; Qizhang Fan; Wei Liu; Yanming Zhao; Yijie Xing; Jinku Li; et al. (Global and Planetary Change, 2026)

N2O and NO formation influenced by metal elements during coal pyrolysis and char combustion - Yanjun Zuo; Zhaoxin Wan; Haiyang Li; Ping Liu; Xiaoshuo Liu; Yingchuan Zhou; Zhi Han; Yufeng Duan (Fuel, 2026)

Evolution of rheological properties and prediction of mastic viscoelastic behavior of warm mix asphalt - Meiyan Huang; Jianguo Wei; Ping Li; Yuming Zhou; Yiliang Li; Qilin Fu (Fuel, 2026)

Enhanced flavor and modified structure of Maillard reaction products from chicken liver protein hydrolysate through composite fermentation pretreatment - Wenchao Chen; Wei Cui; Ping Li; Zhaoming Wang; Xingguang Chen; Hui Zhou; Baocai Xu (Food Chemistry, 2026)

Amino-functionalized covalent organic framework-carboxylated carbon nanotubes via covalent bonding for sensitive Tau electrochemical immunosensing - Ping He; Wen-Tao Li; A-Min Zhu; Si-Yuan An; Jun-Ping Ma; She-Ying Dong; Yuan-Zhen Zhou; Jun-Jie Zhu (Chemical Engineering Journal, 2026)

Observation of out-of-plane ferroelectricity in ∼5 nm ultrathin SrBi2Ta2O9 films for memristors and synapses application - Li-Ping Tan; Xue-Feng Hu; A-Long Li; Wei-Wei Qing; Ming Zhou; De-Bao Yu; Guo-Peng Zhang; Qing-Qing Mu; Zi-Long Wang; Xiao-Liang Wang; Ya-Li Bi; Wei Zhang (Chemical Engineering Journal, 2026)

A metal-immuno photosensitizer strategy: Iridium(III)-zidovudine conjugate triggering sequential organelle stress and synergizing with PD-L1 inhibitor in oral squamous cell carcinoma - Yi-Ling Li; Peng Wang; Wu-Ya Zhang; Rui Zhou; Jia-Ying Zhou; Jia-Wen Chen; Jia-Yin Wu; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

Chemical constituents from Helvella leucopus and their chemotaxonomic significance - Zhao-Zhao Zhang; Yi-Yang Xie; Li-Ping Teng; Zhong-Bo Zhou (Biochemical Systematics and Ecology, 2026)

Inhibition of the Microglial cGAS-STING Pathway Improves Neurological Deficits and Long-Term Hydrocephalus Symptoms in Mice with Intraventricular Hemorrhage - Hao-Xiang Wang; Hua-Jiang Deng; Kun-Hong Zhong; Zi-Ang Deng; Bao-Cheng Gao; Xin Tang; Yuan-You Li; Ke-Ru Huang; Ai-Ping Tong; Da-Xiong Feng; Liang-Xue Zhou (Molecular Neurobiology, 2026)

Retraction Note to: Downregulation of the Long Non-Coding RNA Meg3 Promotes Angiogenesis After Ischemic Brain Injury by Activating Notch Signaling - Juan Liu; Qing Li; Kun-shan Zhang; Bin Hu; Xin Niu; Shu-min Zhou; Si-guang Li; Yu-ping Luo; Yang Wang; Zhi-feng Deng (Molecular Neurobiology, 2026)

Association between low daily average temperature and epilepsy outpatient visits: a hospital-based study in Chongqing, China - Pei Jiang; Jing Yang; Yumeng Zhou; Jinchi Gu; Fengxia Liu; Chunlei Tan; Yao Cheng; Hao Wang; Li Mao; Peng Hu; Ping Chen; Ding Liu; et al. (International Journal of Biometeorology, 2026)

Diversity and seasonal dynamics of parasitoid communities sustaining biocontrol of citrus leafminer moth Phyllocnistis citrella - Xin-Yi Chen; Yu-Tong Zhou; Pei-Ping Xu; Ze-Yun Fan; Li-He Zhang; Guillaume Nyagatare; Bao-Li Qiu (Biodiversity and Conservation, 2026)

Coupled biogeochemical processes account for vertical heterogeneity of groundwater iodine in the Hetao Basin - Junxia Li; Xingtao Liu; Zhou Jiang; Liang Shi; Yanhong Wang; Ping Li; Xianjun Xie; Yanxin Wang (Water Research, 2025)

Groundwater depletion in China’s Granary: The unintended consequences of cropping pattern shifts - Yiqun Shang; Jinwei Dong; Ping Fu; Nanshan You; Xi Zhang; Yuanyuan Di; Yan Zhou; Xi Chen; Zhichao Li; Xinqi Zheng (Journal of Hydrology, 2025)

Fabrication of oil-in-natural deep eutectic solvents Pickering interfacial catalysis: Boosting a sustainable platform for enzymatic esterification of high-acid oil - Liyan Pan; Weiqi Liu; Yuanyuan Deng; Guang Liu; Yan Zhang; Xiaojun Tang; Ping Li; Zhihao Zhao; Jiarui Zeng; Mingwei Zhang; Pengfei Zhou (Food Chemistry, 2025)

Ln-MOF based magnetic composite nanosensor for sensitive dual-mode fluorescence/colorimetric detection of fluoroquinolones - Fukai Li; Jian Zhou; Kai Li; Min Wang; Mengrui Yang; Ping Gong; Liang Li (Food Chemistry, 2025)

A high safety composite separator for powerful battery with ultra-long lifespan over 14,000 cycles at 10C - Ke Fang; Yan-yan Chen; Jian-wei Ji; Tian-kun Gao; Mei-qi Hu; Lian-li Zou; Ying Liu; Li-ping Zhou; Ming-quan Liu; Mao-xiang Jing (Chemical Engineering Journal, 2025)

Self-adaptive auditory perceptual system for voice instruction recognition powered by triboelectric acoustic sensor - Si Yuan Zhou; Shi Han Wang; Jing Zhang; Lin Feng Wu; Wei Sheng Wang; Bei Chen Gong; Jia Kang Di; Xiang Mei Duan; Hua Ping Wu; Li Qiang Zhu (Chemical Engineering Journal, 2025)

Drivers of protistan communities in a subtropical coastal wetland: roles of plant types and soil depths - Zi-Kai Liu; Lu Li; Bowen Huang; Luhong Zhou; Yongxin Lin; Ping Yang; Ju-Pei Shen; Weidong Chen (CATENA, 2025)

Characterizing 3D flash drought events and exploring flash drought propagation in the North China Plain, China - Siyao Zhang; Keke Zhou; Jianzhu Li; Ting Zhang; Ping Feng (CATENA, 2025)

Skeletal and sedimentary structures in yardang caverns in the Mars analog, Qaidam Basin: origin and implication - Qi-Tao Hu; Wen-Ping Liu; Yu-Lu Xue; Qi-Zhi Yao; Sheng-Quan Fu; Yi-Liang Li; Gen-Tao Zhou (CATENA, 2025)

Effect of Accelerators on Hydrothermal Anaerobic Digestion of Platanus Orientalis Linn Fallen Leaves - Hui Tan; Hongyu Huo; Jun Zhou; Mingjing Li; Jiahui Zhu; Lei Gong; Wenfeng Wang; Ping Yang (Water, Air, & Soil Pollution, 2025)

Araloside A Induces Raf/MEK/ERK-Dependent Autophagy to Mitigate Alzheimer’s and Parkinson’s Pathology in Cellular and C. elegans Models - Xue Chen; Xing-Yue Zhou; Cai Lan; Hai-Jun Fu; Zhi-Chao Li; Meng-Yi Chen; Yong-Ping Wen; Lu Yu; Da-Lian Qin; An-Guo Wu; Jian-Ming Wu; Xiao-Gang Zhou (Molecular Neurobiology, 2025)

Granulated Organic Amendment Enhances Soil Fertility, Alleviates Microbial Metabolic Limitation, and Increases Rice Yield in a Medium and Low-Yield Paddy Fields of Subtropical China - Yingnan Xian; Yan Li; Zhe Li; Mingxia Wang; Yuting Dai; Baozhen Li; Ping Zhou; Wei Gao; Xiaobin Guo; Jinshui Wu (Journal of Soil Science and Plant Nutrition, 2025)

Predictive value of serum lipid for kawasaki disease shock syndrome: a prospective study - Ping Wu; Bowen Li; Jinlin Wu; Yunhao Li; Fan Ma; Nanjun Zhang; Xiaoliang Liu; Yimin Hua; Kaiyu Zhou; Chuan Wang; Hongyu Duan; Shuran Shao (Immunologic Research, 2025)

Soil and enzymatic C:N:P stoichiometry response to carbon and nutrient input: evidence from long-term fertilization experiments - Qiong Xiao; Yaping Huang; Guoping Chen; Kailou Liu; Yu Jiang; Boku Zhou; Ping Zhu; Xiaori Han; Junyong Ma; Shutang Liu; Shaomin Huang; Aijun Zhang; et al. (Plant and Soil, 2025)

Sorafenib induces intestinal toxicity by disturbing gut microbiota and activating the LPS/TLR4/NF-κB signaling pathway in mice - Yaning Xu; Yongshi Mo; Wenxin Zhou; Meirong Qin; Meifang Li; Guo Yin; Hansheng Yu; Yuchun Chen; Haiyan Du; Yibao Jin; Houshuang Huang; Chong Ma; et al. (Toxicology, 2025)

Plasma-activated water: A novel approach to modulating main pectin, hemicellulose and cellulose metabolism in goji berry cell walls - Kai-Ping Cong; Ting-Ting Li; Cai-E. Wu; Gong-Jian Fan; Dan-Dan Zhou; Xiao-Jing Li; An-Di Suo (Postharvest Biology and Technology, 2025)

Effect of apparent pore-fluid compressibility and degree of saturation with atmospheric pressure on wave-induced transient pore pressure response - Wen-Gang Qi; Pei-Qing Zhao; Li-Jing Yang; Mo-Zhen Zhou; Fu-Ping Gao; Dong-Sheng Jeng (Ocean Engineering, 2025)

Remediating the material properties of soil by an innovative micro-nano bubble method - Zhihao CHEN; Zhanyan CHEN; Li WANG; Ping XIANG; Fan YANG; Jiali YU; Jianguo ZHOU; Shunyao ZHUANG; Huabin TU; Yonghong WU (Pedosphere, 2025)

High-throughput discrimination of chlorogenic acid isomers in Lonicerae Japonicae Flos by U-shaped mobility analyzer-mass spectrometer - Meng Ding; Luwei Zheng; Ao Zhou; Yuling Li; Yiming Wang; Xiaoqiang Zhang; Wenjian Sun; Wen Gao; Ping Li; Hua Yang (Food Chemistry, 2025)

Novel umami peptides from Grass Carp marinated with Red Yeast Rice Flour and their taste presentation mechanisms characterized by in silico approach and sensory evaluation - Qiaohui Zeng; Miaoshan Zhou; Lifang Gao; Ping Qi; Shilin Cao; Jian Li; Xinan Zeng; Jingjing Wang (Food Bioscience, 2025)

Numerical modeling of tunnel water inrush in a unified nonlocal general particle dynamics framework - Yu-Long Li; Xiao-Ping Zhou (Engineering Geology, 2025)

Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2025)

Development of novel smartphone-based micro-electrochemical immunosensors for the point of care testing and typing of Helicobacter pylori in serum and whole blood - Yuhan Wang; Ping Zhang; Wei Fang; Chuxian Zhou; Gengzhou Yang; Wenwei Huang; Lijie Zhang; Xiaoli Zhang; Bing Gu; Minmin Li; Jiajie Liang; Yong Tang (Chemical Engineering Journal, 2025)

Synergistic dual-Lewis sites in cobalt-doped Fe3S4 for enhanced hydrogen peroxide activation and contaminant degradation - Li-Ping Jin; Fan Zhou; Qin Liu; Su-Qin Wang; Meng-Meng Zeng; Xin-Yu Huang; Li Liu; Xiao-Han Yu; Mei-Feng Wu; Jian-Ping Zou (Chemical Engineering Journal, 2025)

Androgen induces 3′UTR shortening of de novo lipogenesis genes by alternative polyadenylation in prostate cancer cells - Wei-Jie Sun; Fei Liang; Hui Zhao; Yun-Mei Wang; Zhong-Yin Zhou; Hui Xu; Hang Liu; Dong Tang; An-Long Xu; Yong-Gui Fu; Xi Li; Jun Ouyang; et al. (Science China Life Sciences, 2025)
Alternative polyadenylation (APA) is a pervasive mechanism that is emerging as a formidable player in post-transcriptional regulation. The transcriptional landscape can be altered via APA in response to various stimulating factors. Using the PacBio single-molecule long-read sequencing method, we present for the first time the 3′UTR landscape and reveal a global increase of APA events in prostate cancer (PCa) LNCaP cells in response to androgen dihydrotestosterone (DHT), a critical regulator of PCa progression. With evidence from differential gene expression analyses of Illumina RNA-sequencing data, we demonstrated that genes with DHT-induced changes in both expression and APA were enriched in lipid metabolism. These genes predominantly supported de novo fatty acid synthesis, such as FASN and ACSL3 . Furthermore, we showed that an isoform switch to the proximal poly(A) site of these genes depended on the androgen receptor, and the expression of cancer-associated genes was upregulated by the escape of miRNA-regulated repression machinery. To address the role of key gene shortening in PCa, we prepared 22RV1-FS cells missing the distal poly(A) signal of FASN in the AR + PCa cell line 22RV1 using CRISPR/Cas9 technology. As expected, the edited 22RV1-FS cells overexpressed FASN mRNA and protein and were inclined to cell proliferation in vitro and tumorigenesis in vivo . Interestingly, we found that FASN transcripts with a shortened 3′UTR were significantly increased in advanced PCa and castration-resistant prostate cancer compared with benign prostate hyperplasia, suggesting a possible association between usage of the proximal poly(A) site and disease progression. Therefore, our study highlights the importance of the APA mechanism in response to DHT stimulation in PCa cells and provides a novel regulatory mechanism through which DHT-induced APA causes altered expression of de novo lipogenesis genes, with a possible association with the progression of PCa.

Investigation of the South Atlantic Anomaly (SAA) by proton flux variabilities based on 6 years’ CSES data - Lu Wang; Zhenxia Zhang; Xinqiao Li; Zhenghua An; Yanbing Xu; Ping Wang; Hong Lu; Xiaoyun Zhao; Dali Zhang; Xiaohua Liang; Zhiqiang Ding; Shujie Li; et al. (Science China Earth Sciences, 2025)

Salicylic acid-triggered hydrogen sulfide improves maize seed germination under drought stress by bolstering osmoregulatory system - Mi-Xue Tu; Hong-Dan Zhou; Xiao-Ping Luo; Chun-Yan Mao; Zhong-Guang Li (Plant Cell Reports, 2025)

The role of TLR4/NF-kB signaling axis in pneumonia: from molecular mechanisms to regulation by phytochemicals - Jun Yin; Jianxiang Huang; Ping Zhou; Linwei Li; Qin Zheng; Hong Fu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Synthesis and antitumor evaluation of oleanolic acid acylhydrazone derivatives - Juan Cai; Bo-Wen Pan; Liang-Liang Zheng; You-Ping Tian; Zhang-Chao Dong; Li-Juan Liu; Ting-Ting Feng; Ying Zhou; Xiong-Wei Liu; Yang Shi (Molecular Diversity, 2025)

Analysis of rockburst hazard and optimization of prevention and control measures in multi-seam mining based on refined numerical simulations - Anliang Lu; Dazhao Song; Zhenlei Li; Chao Zhou; Ping Wang; Xueqiu He (Bulletin of Engineering Geology and the Environment, 2025)

Design and Control of a Bionic Underwater Collector Based on the Mouth Mechanism of Stomiidae - Zexing Mo; Ping Ren; Lei Zhang; Jisheng Zhou; Yaru Li; Bowei Cui; Luze Wang (Journal of Marine Science and Engineering, 2025)
Deep-sea mining has gradually emerged as a core domain in global resource exploitation. Underwater autonomous robots, characterized by low cost, high flexibility, and lightweight properties, demonstrate significant advantages in deep-sea mineral development. To address the limitations of traditional deep-sea mining equipment, such as large volume, high energy consumption, and insufficient flexibility, this paper proposes an innovative Underwater Vehicle Collector System (UVCS). Integrating bionic design with autonomous robotic technology, this system features a collection device mimicking the large opening–closing kinematics of the mouth of deep-sea dragonfish (Stomiidae). A dual-rocker mechanism is employed to realize the mouth opening-closing function, and the collection process is driven by the pitching motion of the vehicle without the need for additional motors, thus achieving the advantages of high flexibility, low energy consumption, and light weight. The system is capable of collecting seabed polymetallic nodules with diameters ranging from 1 to 12 cm, thus providing a new solution for sustainable deep-sea mining. Based on the dynamics of UVCS, this paper verifies its attitude stability and collection efficiency in planar motions through single-cycle and multi-cycle simulation analyses. The simulation results indicate that the system operates stably with reliable collection actions. Furthermore, water tank testings demonstrate the opening and closing functions of the UVCS collection device, fully confirming its design feasibility and application potential. In conclusion, the UVCS system, through the integration of bionic design, opens up a new path for practical applications in deep-sea resource exploitation.

A low-temperature emergency power source designed from warm pastes based on hydrogel - Chuanchao Sheng; Wei Li; Sixie Yang; Xiaowei Mu; Xinyi Sun; Hang Liu; Haoshen Zhou; Ping He (Science Bulletin, 2025)

Eco-intensified recovery of acetonitrile and ethanol from industrial wastewater via heat-integrated reactive pressure-swing distillation - Jian Zhai; Ting Li; Xueke Zheng; Qingbo Sun; Chunbo Hao; Xuefei Leng; Ping Zhao; Jinwen Li; Yuran Zhou (Process Safety and Environmental Protection, 2025)

Polycyclic polyprenylated acylphloroglucinols with cytotoxicity against human tongue squamous carcinoma cells in vitro from Hypericum curvisepalum - Min-Min Cao; Xian Wei; Jie Huang; Zhong-Qiu Gan; Li-Ping Teng; Zhong-Bo Zhou (Phytochemistry Letters, 2025)

Efficient room-temperature hydrolytic cleavage of CS2 via Pd-anchored polynitrogen porous polymers - Kai-Wen Jiang; Xing-Yu Chen; Xiao-Li Jiang; Qing-Ya Sun; Yu-Peng Dai; Hui-Zhen He; Ying Zhou; Ping Shang; Xuan-Feng Jiang (Journal of Hazardous Materials, 2025)

Purification, identification, and mechanism of action of novel antioxidant peptides from quinoa (Chenopodium quinoa wild.) protein hydrolysate - Huan-Huan Xiao; Xue-Ying Li; Ying-Ying Chen; Jin-Xiang Zhou; Ting Zhang; Qiang-Ming Li; Li-Hua Pan; Jian-Ping Luo; Xue-Qiang Zha (Food Chemistry, 2025)

Black rice stepwise fermentation enhances yogurt gel quality: Solidification rate, texture, LAB distribution and viability persistence - Jiarui Zeng; Zhiming Wang; Guang Liu; Xuchao Jia; Pengfei Zhou; Ping Li; Zhihao Zhao; Yan Zhang; Xiaojun Tang; Dong Liu; Yuanyuan Deng; Mingwei Zhang (Food Chemistry, 2025)

Cosolvent-modulated polyamide nanostructures enable precise Mg2+/Li+ separation for lithium recovery from brines - Ping Li; Yuan Zhou; Chunxi Hai; Ying Cheng; Yu Tang; Yanxia Sun; Shengde Dong; Luxiang Ma; Xin He; Qi Xu (Desalination, 2025)

Excellent durability and multifunctional textiles with dual-mode evaporative and radiative cooling enabled by in-situ growth of SiO2 and electrostatic network coating - Luxuan Zhang; Bo Xu; Man Zhou; Ying Liu; Ying Zhang; Li Cui; Ping Wang; Qiang Wang; Yuanyuan Yu (Chemical Engineering Journal, 2025)

Protein engineering and flow reactor design for anchored peptide-mediated continuous biocatalysis - Huan Li; Chun-Jiang Ma; Ya-Ting Gao; Qing-qing Zhou; Huan Chen; Feng Cheng; Ya-Ping Xue; Yu-Guo Zheng (Chemical Engineering Journal, 2025)

All-in-one wearable electronic based on bacterial cellulose composite: Integrating strain sensing and energy harvesting - Ping Sun; Zongxue Gu; Duo Xu; Bin Yu; Hui Sun; Juan Li; Nan Zhou; Jing Li; Keshuai Liu; Yingcun Liu; Chong Gao; Weilin Xu (Chemical Engineering Journal, 2025)

Therapeutic effects of Scutellaria baicalensis total flavonoids on metabolic syndrome in rats via modulation of PPARα and PPARγ signaling - Yang Zhou; Zhi-Ping Li; Yu-Hang Lian; Xin Gao; Song-He Yin; Yu-Mei Zhao (Journal of Molecular Histology, 2025)

Tongxinluo alleviates myocardial ischemia–reperfusion injury by inhibiting the pyroptosis of endothelial cells via the NLRP3/Caspase-1/GSDMD signaling pathway - Xuan Wu; Yun-long Hou; Tong-xing Wang; Li-ping Chang; Hong-ru Zhou; Ming-ye Wang; Yi-ling Wu (Journal of Molecular Histology, 2025)

Comparison of surface energy balance and melt characteristics between debris-covered and debris-free zones on Qingbingtan Glacier No. 72, Mt. Tomor of Tien Shan - Jie He; Puyu Wang; Hongliang Li; Ping Zhou; Jianxin Mu; Fanglong Wang; Puchen Chen; Fengchen Yu; Yuping Dai (Climate Dynamics, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Artificial Neural Network Model for Predicting Local Equilibrium Scour Depth at Pile Groups in Steady Currents - Xinao Zhao; Ping Dong; Yan Li; Yan Zhou; Xiaoying Zhao; Qing Wang; Chao Zhan (Journal of Marine Science and Engineering, 2025)
Piles are common support elements for marine and coastal structures. The scour around pile foundations caused by currents is a major threat to the stability and safety of these structures. The empirical equations commonly used for estimating the equilibrium scour depth around pile groups are limited in their predicative capability, especially when the current approaches the pile group at an angle. This study applies a Multi-Layer Perceptron Backpropagation (MLP/BP) neural network to develop a general model for predicting the local maximum equilibrium scour depth around pile groups in steady currents. The input parameters for the model include all relevant non-dimensional hydrodynamic and structural variables taking full account of the effects of the pile group arrangement and its orientation relative to the approaching current. The model’s performance was evaluated by comparing its predictions against those generated by multiple other machine learning methods, as well as against results from widely used empirical formulas. A comprehensive sensitivity analysis is carried out to determine the importance ranking of the input parameters on model accuracy.

Hydrothermal cyclic regeneration performance and synergistic pollutant degradation of spent activated carbon from water purification - Guifang Chen; Mengning Liu; Wei Wang; Zhanyao Li; Fuyu Huang; Xujiang Wang; Shouyan Chen; Ping Zhou (Journal of Water Process Engineering, 2025)

Occurrence, molecular transformation and prioritizing environmental risks of organic nitrogen in aqueous phase from hydrothermal carbonization of waste activated sludge - Tingting Yang; Lichao Tan; Jiaqi Ge; Xue Zhang; Gang Zhou; Ping Li; Ninghui Song; Feng Ge (Journal of Hazardous Materials, 2025)

Oxidative damage induced by daily exposure to primary and emerging aromatic amines: Insights from large scale biomonitoring and cell-based high-throughput PCR array analysis - Shaohan Zhang; Zijun Zhou; Pingping Wang; Yanan Yao; Yuhao Cao; Jialan Liu; Ping Li; Tao Zhang; Hongkai Zhu; Lei Wang; Hongwen Sun; Zhipeng Cheng (Journal of Hazardous Materials, 2025)

Activity and sulfur resistance enhancement of metal-based catalysts derived from layered double hydroxides for selective catalytic reduction of NO with NH3 - Gan Chen; Zhenzhen Guan; Shifeng Zhou; Yu Guo; Ziying Yang; Jiang Wu; Fangqin Li; Ping He; Xinxia Ma (Fuel, 2025)

Black tea addition enhances the aroma release of rose petals by activating related pathways during the scenting process - Yueling Zhao; Liuyi Chen; Jinlin Bian; Faxin Li; Yuanyuan Wang; Hongyu Zhou; Zihan Ma; Ping Xu; Xiao Du (Food Chemistry, 2025)

Ultrastable high internal phase Pickering emulsions stabilized by deamidated pea protein: Formation mechanisms and applications in 3D printing - Lijuan Luo; Ping Li; Yuanyuan Deng; Guang Liu; Yan Zhang; Xiaojun Tang; Pengfei Zhou; Zhihao Zhao; Mingwei Zhang (Food Chemistry, 2025)

Graphene quantum dots induce hexagonal CdS prism formation and interparticle Z-scheme heterojunctions for efficient Hg0 removal under visible light - Xi Zhou; Yibing Xie; Lu Wang; Langlang Wang; Xiang Li; Ping Ning; Xueqian Wang (Chemical Engineering Journal, 2025)

Genome-wide Identification of the MTP Gene Family in Cotton and Expression Analysis Under Multiple Metal Stresses - Yong Yang; Wenjie Lai; Ping Li; Shihan Zhou; Yutong Wu; Yuanhao Ding; Haiyan Hu (Plant Molecular Biology Reporter, 2025)

ZmDof08, a zinc finger transcription factor, plays critical roles in photosynthesis in maize - Ting Li; Jinjie Guo; Jiahao Zhang; Ping Deng; Yuanyuan Xu; Xinjia Li; Yu He; Lian Zhou; Chaofeng Li; Chaoxian Liu (Plant Cell Reports, 2025)

Quorum-sensing Inhibitory Activity of Xanthones from Hypericum Curvisepalum N. Robson Against Chromobacterium Violaceum - Hong Zeng; Qiu-Ying He; Sheng-Qiang Yang; Xiao-Lian Wei; Jia-Zi Luo; Jing-Kai Zhou; Rong-Bing Fu; Li-Ping Teng; Zhong-Bo Zhou (Current Microbiology, 2025)

Discovery of indole-carbohydrazide hybrids as novel broad-spectrum fungicidal lead compound though membrane-targeting mechanism - Ying Wu; Li-Hui Shao; Xian-Qun Hu; Yu Long; Yuan-Yuan Wu; Pei-Bu Yu; Ai-Ping Yan; Long-Fei Li; Xiang Zhou; Song Yang (Molecular Diversity, 2025)

Proteomics and metabolomics reveal the role of miR-320b in regulating inflammation of bovine mammary epithelial cells - Li Zhou; Zhuo-Ma Luoreng; Xing-Ping Wang; Ya-Qing Dou; Hui Li (Research in Veterinary Science, 2025)

Isolation of dihydroagarofuran sesquiterpene from the fruits of Tripterygium hypoglaucum and evaluation of their anti-inflammatory activity - Shi-Li Wu; Xing Yang; Wen-Xiu Ning; Gang-Yun Wu; Xin-Yu Dai; Yu Zhang; Duo-Zhi Chen; Xiao Ding; Hong-Ping He; Wei Zhou; Xiao-Jiang Hao (Phytochemistry, 2025)

BarleyOmics: A comprehensive multi-omics database of barley - Junheng Zhao; Shanggeng Xie; Chenyang Zhang; Zengjie Hu; Xiangqian Lu; Nannan Zheng; Yujie Fu; Jie Yao; Ping Zhou; Danyin Huang; Zhizhong Zhang; Mengdi Li; et al. (Molecular Plant, 2025)

Effects of heat treatment on the binding between the key aroma-active compounds in Zanthoxylum bungeanum oil and pork myofibrillar proteins (MPs) - Qin Xiang; Lijuan Yao; Jiao Zhou; Songling Li; Wei Zeng; Ping Liu (Food Chemistry, 2025)

Study on the correlation between Flavobacterium columnare infection and gill injury in Largemouth bass (Micropterus salmoides) and the protective effect of Enoxolone - Chen Li; Yunshan Qiu; Lin Luo; Xinnan Zhou; Hongli Liu; Ping Ouyang; Yi Geng; Defang Chen; Xiaoli Huang (Fish & Shellfish Immunology, 2025)

Promoting l-theanine accumulation in Camellia sinensis through irrigation with Pseudomonas knackmussii - Gang Zhou; Junchen Feng; Siran Yu; Ping Li (Plant Cell Reports, 2025)

Six Weeks of Moderate-Intensity Treadmill Exercise Improves Intestinal Barrier and Intestinal Inflammation in Parkinson’s Disease Mice - Ting Li; Sheng-Yang Zhou; Wei Quan; Yu Zhou; Jian Wu; Li-Ping Zhao; Chen-Meng Qiao; Wei-Jiang Zhao; Chun Cui; Yan-Qin Shen (Molecular Neurobiology, 2025)

Clinical characteristics and outcomes of tuberculosis and non-tuberculous mycobacteria infections: a population-based study of concurrent and sequential infections - Zhen-Tao Fei; Dan-Ping Zhou; Wei Huang; Ping Liu; Qian-Ping Lu; Hao Li; Yang Yang; Dan Ye; Xu-Hui Liu; Lu Xia (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

The pathological characteristics at different stages and early diagnosis by duplex PCR of Nocardia seriolae disease in largemouth bass (Micropterus salmoides) - Xinnan Zhou; Yunshan Qiu; Chen Li; Ya Huang; Ping Ouyang; Defang Chen; Yi Geng; Xiaoli Huang (Aquaculture, 2025)

Exploring possible ancient applications of perilla: evidence from 3 million fruit remains from Han Dynasty tombs in China - Yun-Jun Bai; Ming Jiang; Xue-Ping Wei; Zhi-Jun Zhao; Xin-Ying Zhou; Hong-En Jiang; Tao Xie; Xiao-Lin Li; Yu-Yang Zhao; Xue Yan; Meng Cheng; Lu-Qi Huang; et al. (Science Bulletin, 2025)

A preliminary investigation of pore development mechanisms in highly matured solid bitumen: Implications from the Ediacaran Dengying Formation solid bitumen in the central Sichuan Basin, Southwest China - Lianqiang Zhu; Hui Tian; Peng Cheng; Haifeng Gai; Tengfei Li; Qin Zhou; Wei Wu; Chao Luo; Ping'an Peng (Marine and Petroleum Geology, 2025)

Arsenic mobilization by Bathyarchaeia in subsurface sediments at the Jianghan Plain, China - Zhou Jiang; Wenjie Fang; Yongguang Jiang; Yidan Hu; Yiran Dong; Ping Li; Liang Shi (Journal of Hazardous Materials, 2025)

Effects of exogenous mineral silicon on physiological characteristics and arsenic uptake and transport in rice - Jing Han; Qihao He; Mingjing Lei; Ke Li; Yufei Zhou; Wenmin Li; Ying Xiao; Fan Zhang; Chang Sun; Jieying Wang; Jian Zhu; Zhiming Liu; et al. (Journal of Hazardous Materials, 2025)

Cyclic trace enzymatic hydrolysis pretreatment enhances brown rice: Cooking and taste - Yuanyuan Deng; Pengfei Zhou; Ya Li; Ping Li; Zhihao Zhao; Jiajia Wang; Lihuang Zhong; Guang Liu; Mingwei Zhang; Dong Liu; Jiarui Zeng (Food Chemistry, 2025)

Investigating the fine structures of ginkgo starch during kernel development and their correlations with thermal properties - Yan Lu; Lian Zhou; Cai-Yun Zhang; Yan Qi; Xiao-Min Zhang; Zhang Pan; Hong-Jia Zhang; Yu-Ping Ling; Qing Liu; Chang-Quan Zhang; Li Wang (Food Chemistry, 2025)

A Unified Nonlinear Creep Damage Coupled Model for Rocks Based on Fractional Calculus and Statistical Damage Model - Da-Lang Tian; Zheng-Chuan Li; Fan Shen; Yu-tong Li; Zheng Li; Xiao-Ping Zhou (Rock Mechanics and Rock Engineering, 2025)

Lithofacies Types and Pore Structure Characteristics of Marine Shale in the Lower Cambrian Shuijingtuo Formation, Middle Yangtze Region, China - Jialin Fan; Wei Liu; Yujing Qian; Jinku Li; Qin Zhou; Ping Gao (Journal of Marine Science and Engineering, 2025)
The lithofacies and pore structural characteristics of shale reservoirs directly affect the exploration and development of shale gas. To clarify the exploration and development potential of the Lower Cambrian Shuijingtuo Formation (SJT) shale in the Middle Yangtze region, China, this study employs integrated experimental approaches, including optical and scanning electron microscopy (SEM) observations, X-ray diffraction (XRD) mineralogical analysis, and low-pressure gas (N2/CO2) adsorption, to classify mudstone lithofacies within the SJT and elucidate pore structural characteristics and dominant geological control across different lithofacies. The research results show that (1) Six main types of shale lithofacies are found in the STJ, including low-TOC massive calcareous mudstone (LMCM), low-TOC laminated mixed mudstone (LLMM), medium-TOC massive mixed mudstone (MMMM), high-TOC massive mixed mudstone (HMMM), high-TOC laminated siliceous mudstone (HLSM), and laminated argillaceous mudstone (LAM). (2) The pore types of SJT mudstone primarily include organic pores, intragranular clay mineral pores, and microfractures. The pore structure of mudstone is mainly controlled by clay mineral content and TOC content. However, the controlling factors of pore structure vary among different mudstone lithofacies. LMCM and LLMM are dominated by intragranular clay mineral pores, with their pore structures mainly controlled by clay mineral content. The pore types of HLMM and HLSM are organic pores, with pore structures predominantly controlled by TOC content. (3) The SJT mudstone gas reservoir exhibits diverse types, including HLSM, LAM, and LLMM. HLSM is characterized by the highest brittleness index and elevated pore volume (PV) and it can be considered the optimum lithofacies in the study area. Additionally, LLMM has the highest PV and relatively high brittleness index, positioning it as another significant reservoir target in the study area. Therefore, the Lower Cambrian shale gas reservoirs in the Middle Yangtze region exhibit diverse reservoir types. These research findings provide a scientific basis for the next phase of shale gas exploration planning in the Lower Cambrian.

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Genetic deletion of microRNA-15a/16-1 in pericytes stimulates cerebral angiogenesis and promotes functional recovery after ischemic stroke - Ping Sun; Yang Xu; Tianqing Xiong; Shun Li; Na Qiu; Chao Zhou; Jiefei Wang; Alexander Chang; Uma R. Chandran; Ke-Jie Yin (Angiogenesis, 2025)

Great Oxidation Event was caused by Neoarchean global cratonization: opportunity and challenge from rock and sedimentary records in China - Li-Gang Zhou; Jun-Ping Liu; Jing Li; Zai-Bo Sun; Lu Xiang; Yan-Yan Zhou; Hao-Shu Tang; Yan-Bin Zhang; Xi-Yan Zhu; Hai-Long He; Ming-Guo Zhai (Science Bulletin, 2025)

Discovery of structurally intriguing diterpenoids as anti-neuroinflammatory agents from mangrove plant Excoecaria agallocha L. via inhibiting macrophage polarization and inflammasome - Jun-Yi Li; Ming-Bin Chen; Ting-Ting Fu; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Jing Zhou; Yong Rao; Zhong-Ping Jiang; Ling Huang (Phytochemistry, 2025)

In vitro and in vivo antibacterial effects of indole-3-lactic acid against Salmonella enterica serovar Typhimurium - Qingqing Zhou; Yajun Yu; Zuorui Xie; Yingying Zhou; Yanan Li; Ping Li; Jiangning Hu; Qing Gu (Food Bioscience, 2025)

Transcriptome analysis reveals the mechanism of cortisol through GR regulating the expression of inflammatory cytokines in Siberian sturgeon (Acipenser baerii) after LPS treatment in vitro - Peng Tang; Yinqiu Chen; Defang Chen; Hao Zhu; Shaotong Dai; Jiawen Zhou; Xin Zhang; Xiaoli Huang; Ping Ouyang; Yi Geng; Zhiqiong Li (Fish & Shellfish Immunology, 2025)

Cortical thickness alternation in obsessive-compulsive disorder patients compared with healthy controls - Chunyu Dong; Hao Zheng; Hailong Shen; Yu Wan; Yinghong Xu; Ying Li; Liangliang Ping; Hao Yu; Chuanxin Liu; Jian Cui; Kun Li; Cong Zhou (Brain Imaging and Behavior, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

The transcription factor CsPAT1 from tea plant (Camellia sinensis) is involved in drought tolerance by modulating phenylpropanoid biosynthesis - Jing-Wen Li; Ping Zhou; Zhi-Hang Hu; Ai-Sheng Xiong; Xing-Hui Li; Xuan Chen; Jing Zhuang (Journal of Plant Physiology, 2025)

Recent progress in intrinsic self-healing polymer materials: Mechanisms, challenges and potential applications in oil and gas development - Shunming Zhou; Ning Qi; Zehui Zhang; Ping Jiang; Aihua Li; Yixin Lu; Xuhang Su (Chemical Engineering Journal, 2025)

Validation of Interaction Between Sugarcane miR167d and Predicted Target Gene ScPUM1 and Analysis of Their Expression Under Cold Stress: A Novel Mechanism of miR167d - Qiqi Song; Pengjin Zhu; Jiahui Li; Qin Cheng; Qinliang Tan; Quanguang Zhou; Ping Lv; Zemei Nong (Journal of Plant Growth Regulation, 2025)

Berberine diminishes the malignant progression of non-small cell lung cancer cells by targeting CDCA5 and CCNA2 - Xin Zhao; Minwen Ha; Lulu Zhou; Yanyun Wang; Ping Li (Journal of Natural Medicines, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Moisture–Microbial Interaction Amplifies N 2 O Emission Hot Moments Under Deepened Snow in Grasslands - Jie Luo; Yong Peng; Zhou Jia; Yuntao Wu; Yuxuan Gao; Nairsag Jalaid; Xingming Zhang; Heng Ge; Bowen Qing; Hongyi Chen; Yanxin Zhan; Ping Li; et al. (Global Change Biology, 2025)
Freeze–thaw‐induced N 2 O pulses could account for nearly half of annual N 2 O fluxes in cold climates, but their episodic nature, sensitivity to snow cover dynamics, and the challenges of cold‐season monitoring complicate their accurate estimation and representation in global models. To address these challenges, we combined in situ automated high‐frequency flux measurements with cross‐ecoregion soil core incubations to investigate the mechanisms driving freeze–thaw‐induced N 2 O emissions. We found that deepened snow significantly amplified freeze–thaw N 2 O pulses, with these ~50‐day episodes contributing over 50% of annual fluxes. Additionally, freeze–thaw‐induced N 2 O pulses exhibited significant spatial heterogeneity, ranging from 3.4 to 1184.1 μg N m −2 h −1 depending on site conditions. Despite significant spatiotemporal variation, our results indicated that 68%–86% of this variation can be explained by shifts in controlling factors: from water‐filled pore space (WFPS), which drove anaerobic conditions, to microbial constraints as snow depth increases. Below 43% WFPS, soil moisture was the overwhelmingly dominant driver of emissions; between 43% and 66% WFPS, moisture and microbial attributes (including denitrifying gene abundance, nitrogen enzyme kinetics, and microbial biomass) jointly triggered N 2 O emissions pulses; above 66% WFPS, microbial attributes, particularly nitrogen enzyme kinetics, prevailed. These findings suggested that maintaining higher soil moisture served as a trigger for activating microbial activity, particularly enhancing nitrogen cycling. Furthermore, we showed that hotspots of freeze–thaw‐induced N 2 O emissions were linked to high root production and microbial activity in cold and humid grasslands. Overall, our study highlighted the hierarchical control of WFPS and microbial processes in driving freeze–thaw‐induced N 2 O emission pulses. The easily measurable WFPS and microbial attributes predictable from plant and soil properties could forecast the magnitude and spatial distribution of N 2 O emission “hot moments” under changing climate. Integrating these hot moments, particularly the dynamics of WFPS, into process‐based models could refine N 2 O emission modeling and enhance the accuracy of global N 2 O budget prediction.

Deepened snow promotes temporal stability of semi‐arid grasslands via improving water acquisition‐and‐use strategies - Ping Li; Zhou Jia; Yuntao Wu; Pengfei Chang; Nairsag Jalaid; Lulu Guo; Shengnan Pan; Shaopeng Wang; Lin Jiang; Shuijin Hu; Lingli Liu (Ecology, 2025)
Precipitation fluctuations strongly influence biomass production and its stability of terrestrial ecosystems. However, our understanding of the extent to which plant communities adjust their water‐use strategies in response to non‐growing season precipitation variations remains limited. Our 5‐year snow manipulation experiment in a semi‐arid grassland, complemented with paired stable isotope measurements of δ 18 O and δ 13 C for all species within the community, demonstrated that the impact of snowmelt on plant physiological activities extended into the peak growing season. Deepened snow enhanced ecosystem water use efficiency (WUE), biomass production, and its temporal stability. We further examined whether the observed increase in biomass stability was associated with the functional diversity of plant water‐use strategies. Plant cellulose Δ 18 O cell analysis revealed that both community‐weighted mean and functional dispersion of stomatal conductance were positively associated with biomass production and its stability. The δ 13 C results further indicated that even with increased stomatal conductance, grasses were able to maintain their high intrinsic WUE by increasing photosynthesis more than transpiration. This resulted in higher biomass and greater dominance of high‐WUE functional groups under deepened snow. In addition, we also found that deepened snow increased root biomass, particularly in the 0‐ to 5‐cm and 20‐ to 40‐cm soil layers. This increase in root biomass enhanced the uptake of snowmelt from both surface and deep soil layers, further contributing to community stability. Overall, our study demonstrates that plant communities can optimize water acquisition and utilization, thereby enhancing the stability of biomass production through coordinated changes in plant physiology, species reordering, and root distribution under altered snow regimes.

Anti-hypoxia polyacetylenes and sesquiterpenoids from Codonopsis pilosula (Franch.) Nannf - Zhuo-Yang Cheng; Jun-Ge Jin; Meng Yan; Xin-Yue Chen; Jian-Kuan Li; Jian-Ping Gao; Jiang-Tao Zhou (Natural Product Research, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Revealing the adsorption kinetics of microplastics towards hydrophobic antibiotic: New insights into the microplastics aging behavior and aquatic environmental factors - Ping Wu; Guo-dong Kang; Xue-jian Li; Lei-lei Lu; Hao Zhou; Sheng-hu Zhang; Yuan-qing Bu; Hou-hu Zhang (Journal of Environmental Chemical Engineering, 2025)

Regulatory effects of Lacticaseibacillus rhamnosus ZFM216 and its bacteriocin on intestinal microbiota in vitro - Qingqing Zhou; Yeqing Lou; Chenjie Shan; Zhongdu Ye; Danli Wu; Ping Li; Eefjan Breukink; Qing Gu (Food Bioscience, 2025)

High-Voltage aqueous supercapacitors based on l-lysine pH Self-Buffering Coating-modified carbon cloth electrode - Ang Xu; Jie Gao; Huan Li; Xiyu Song; Bo Xu; Ying Liu; Yuanyuan Yu; Ping Wang; Qiang Wang; Man Zhou (Chemical Engineering Journal, 2025)

Morphological characteristics and distribution of antennal sensilla of Spodoptera litura (Lepidoptera: Noctuidae) using scanning electron microscopy - Yong-Ping Li; Hai-Yan Zhou; Hui Ye; Robert A. Haack; Yuan Yang; Qiu-Lian Hu; Ming-Min Jiang; Jun Cao (Zoomorphology, 2025)

Identification and characterization of anthocyanins’ composition and regulatory genes involved in anthocyanins biosynthesis in water dropwort (Oenanthe javanica) - Kai Feng; Nan Sun; Ya-Qing Bian; Wu-Di Rui; Ya-Jie Yan; Zhi-Yuan Yang; Jia-Lu Liu; Zi-Qi Zhou; Shu-Ping Zhao; Peng Wu; Liang-Jun Li (Planta, 2025)

Aberrance of GAP43/p-GAP43 Closely Associates with the Pathology of Neuron Loss in Prion-Infected Rodent Models - Xiao-Xi Jia; Cao Chen; Chao Hu; Yue-Zhang Wu; Zhi-Yue Chao; Jia-Feng Zeng; Ru-Han A.; Dong-Hua Zhou; Yuan Wang; Wei-Wei Zhang; Kang Xiao; Li-Ping Gao; et al. (Molecular Neurobiology, 2025)

Low-frequency rTMS Plays a Neuroprotective role in Pilocarpine-induced Status Epilepticus Rat Models Through the AMPAR GluA1–STIM–Ca2+ Pathway - Li-Qin Che; Zhen-Zhen Qu; Zhuo-Feng Mao; Qi Qiao; Kai-Ping Zhou; Li-Jing Jia; Wei-Ping Wang (Molecular Neurobiology, 2025)

Regional abnormalities of white and gray matter in youths with conduct problems - Man Dong; Xiaodong Cheng; Yage Li; Shanling Ji; Hao Yu; Liangliang Ping; Chuanxin Liu; Cong Zhou (Brain Imaging and Behavior, 2025)

A mini review of Liparis species: an ornamental genus with considerable medicinal value - Xiao-Bing Chen; Li-Yun Huang; Min Zhou; Zhi-Jie Ling; Yan-Ping Liu; Xi-Lin Ouyang (Natural Product Research, 2025)

Sus scrofa RNase L inhibits PRRSV replication by activation of type I IFN signaling pathway and apoptosis - Xiangju Wu; Xiaoyan Cong; Ping Jiang; Mingming Zhou; Ying Yu; Dandan Jiang; Yue Hu; Juntong Li; Jinxia Zhang; Ying Cao; Haowen Zhang; Yijun Du; et al. (Veterinary Microbiology, 2025)

Aflatoxin B1 exposure induces Alzheimer's disease like pathology by disrupting redox homeostasis and activating ferroptotic signals in C57BL/6 J mice - Jinxian Lin; Huihui Hong; Sicheng Liu; Zhengwei Liang; Qixue Zheng; Kun Luo; Jiayi Li; Zhulin Du; Jinping Yu; Lingling Yang; Ping Deng; Huifeng Pi; et al. (Science of The Total Environment, 2025)

Urinary biomarkers of drinking water disinfection byproducts in relation to blood-based liver function parameters among reproductive-aged Chinese women - Ping-Ping Gui; Yan-Ling Deng; Min Zhang; Yu Miao; Peng-Hui Liu; Jia-Yue Zeng; Yang Wu; Cheng-Ru Li; Xiao-Ying Liu; Yang-Juan Li; Jin-Qin Zhu; A-Xue Liu; et al. (Science of The Total Environment, 2025)

Five brasilane-type sesquiterpenoids with neuroprotective activities from Xylaria nigripes - Hong-Ping Long; Xi Zhou; Si-Qian Zhou; Lan-Qing Li; Ai-Lin Liang; Wen-Yu Lu; Wen-Xuan Wang; Shao Liu; Jing Li; Ji-Kai Liu (Phytochemistry, 2025)

Straw amendment induced contrasting net carbon balance in subtropical paddy and adjacent upland soils - Ping Zhou; Xue Li; Jiaxin Lai; Xiaobin Guo; Jinshui Wu (Applied Soil Ecology, 2025)

Simulation study of the production efficiency of family-type agricultural management entities under regulation measures on farmland: Three-stage super-SBM model considering greenhouse gas emissions - Shuqi Dong; Renjie Hou; Tianxiao Li; Qiang Fu; Ping Xue; Yu Gao; Zhaoqiang Zhou; Qinglin Li (Agricultural Systems, 2025)

Low-Frequency Sweep Design—A Case Study in Middle East Desert Environments - Yong-fei Qi; Zhou-hong Wei; Ming-tao Nie; Guo-fa Li; Tao Wang; Hai Ling; Sheng-kui Cong; Xin-yang Chen; Chang-ping Duan; Yang Liu (Applied Geophysics, 2025)

Role of microbiota and its ecological succession on flavor formation in traditional dry-cured ham: a review - Ping Li; Zhijie Bao; Yang Wang; Xinlian Su; Hui Zhou; Baocai Xu (Critical Reviews in Food Science and Nutrition, 2025)

PhenologyNet: A fine-grained approach for crop-phenology classification fusing convolutional neural network and phenotypic similarity - Hai-Chao Yang; Jian-Ping Zhou; Chao Zheng; Zheng Wu; Yi Li; Li-Gong Li (Computers and Electronics in Agriculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

An integrated photocatalytic redox architecture for simultaneous overall conversion of CO2 and H2O toward CH4 and H2O2 - Muhammad Salman Nasir; Bowen Sheng; Ying Zhao; Haotian Ye; Jun Song; Jinglin Li; Ping Wang; Tao Wang; Xinqiang Wang; Zhen Huang; Baowen Zhou (Science Bulletin, 2025)

Effects of Ammonia loading and oxygen flux on nitrogen removal in a PNA-coupled MABR - Jiang-Feng Zhang; Jinfeng Bao; Chun-Yu Lai; Chen Zhou; Ang Li; He-Ping Zhao (Journal of Water Process Engineering, 2025)

Equilibrium boron isotope fractionation during kaolinite adsorption and applications to chemical weathering processes - Yin-Chuan Li; Ya-Ru Zhou; Hai-Zhen Wei; Martin R. Palmer; Fa-Yang Guo; Yong-Hui Li; Yong-An Qi; Da-Ping Xia (Geochimica et Cosmochimica Acta, 2025)

Integrated microbiome and metabolomics analysis of spoilage characteristics of modified atmosphere packaged pork - Xueya Wang; Ping Li; Xingguang Chen; Wei Cui; Shenyu Ni; Huaxing Xu; Yujuan Xu; Kezhou Cai; Hui Zhou; Baocai Xu (Food Research International, 2025)

Characterizing Chinese saffron Origin, Age and grade using VNlR hyperspectral imaging and Machine learning - Jiahui Wu; Jing Nie; Hao Hu; Xinyue Xu; Chunlin Li; Hongkui Zhou; Peishi Feng; Hanyi Mei; Karyne M. Rogers; Ping Wang; Yuwei Yuan (Food Research International, 2025)

Unveiling the mechanism of Latilactobacillus sakei LZ217 cell-free supernatant against Helicobacter pylori through metabolomics and network pharmacology - Chenlan Xia; Qingqing Zhou; Xia Meng; Ziqi Chen; Shiying Wu; Ping Li; Qing Gu (Food Bioscience, 2025)

Regulating heat-induced fibrous whey protein-wheat starch composite emulsion gels as dysphagia food by preheating temperature: Insights from protein-starch interactions - Zhiming Wang; Jiarui Zeng; Yuanyuan Deng; Pengfei Zhou; Ping Li; Zhihao Zhao; Guang Liu; Mingwei Zhang (Food Hydrocolloids, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Response of soil phosphorus components to black carbon in seasonally frozen areas: Insight into ecoenzymatic stoichiometry - Ping Xue; Heng Li; Qiang Fu; Tianxiao Li; Renjie Hou; Mo Li; Song Cui; Zhaoqiang Zhou; Qinglin Li (Applied Soil Ecology, 2025)

The deformation characteristics of modified lightweight expanded polystyrene soils under cyclical loading - Ping Jiang; Yuming Fu; Wei Wang; Xuhui Zhou; Na Li; Huaqiang Tao (Soil Dynamics and Earthquake Engineering, 2025)

Seven undescribed compounds from dried flower buds of Ochrocarpus longifolius - Shu-Lan Liu; Xue-Ling Huang; Shun-Hua Zhong; Yong-Hui Ma; Feng Wei; Yu-Ye Zhang; Jin Li; Ke-Jian Pang; Ping Zhao; Xin-Zhou Yang (Phytochemistry, 2025)

Corrigendum to “Cobalt induces neurodegenerative damages through Pin1 inactivation in mice and human neuroglioma cells” [J Hazard Mater 419 (2021) 126378] - Fuli Zheng; Yuqing Li; Fengshun Zhang; Yi Sun; Chunyan Zheng; Zhousong Luo; Yuan-Liang Wang; Michael Aschner; Hong Zheng; Liqiong Lin; Ping Cai; Wenya Shao; et al. (Journal of Hazardous Materials, 2025)

Conventional and biodegradable microplastics affected arsenic mobility and methylation in paddy soils through distinct chemical-microbial pathways - Hai-Qian Li; Jin-Peng Lv; Yue-Hui Jia; Jie Liu; Qiong Liang; Jian Zhou; Ai-Zhen Yang; Teng Yan; Yu-Ping Yang; Gui-Lan Duan (Journal of Hazardous Materials, 2025)

Prediction of hydrate formation boundaries in pure water and salt/alcohol containing systems based on prior knowledge and artificial intelligence - Shu-Kai Chen; Xiao-Fang Lv; Jian-Ping Ding; Yang Liu; Ji-Miao Duan; Hui Du; Chuan-Shuo Wang; Ming-Guo Peng; Qian-Li Ma; Shi-dong Zhou (Fuel, 2025)

Glyphosate detection based on Eu coordination polymer through competitive coordination - Linglong Yi; Shangzai Wu; Guojian Ren; Qi Zhou; Ping Li; Yuan Wang; Xudong Tian; Danfeng He; Qinhe Pan (Food Chemistry, 2025)

Multifunctional role of surfactant in fabricating polyamide nanofiltration membranes for Li+/Mg2+ separation - Shang Fang; Kecheng Guan; Aiwen Zhang; Liheng Dai; Siyu Zhou; Wenming Fu; Mengyang Hu; Ping Xu; Pengfei Zhang; Zhan Li; Zhaohuan Mai; Hideto Matsuyama (Desalination, 2025)

Nanoplastic-mineral heteroaggregation under varying degrees of plastic pollution: Implications for antibiotic adsorption in aquatic systems - Xiupei Zhou; Aoze Li; Marko Cerne; Sophie MacRae; Ian Eggleston; Hongtao Qiao; Xiaoyun Li; Guoyong Huang; Ping Wang; Jian Zhao; Baoshan Xing (Chemical Engineering Journal, 2025)

Influence of Syncline Structures on Deformation and Failure in Anti-Dip Soft–Hard Rock Slopes - Chunhong Zhou; Lei Wang; Ping Wang; Wanli Liu; Yuchuan Shi; Feng Ji; Zhuo Li; Juncheng Wang (Geotechnical and Geological Engineering, 2025)

Di-(2-ethylhexyl) Phthalate Exposure Induces Developmental Toxicity in the Mouse Fetal Heart via Mitochondrial Dysfunction - Yafei Guo; Bowen Li; Yu Yan; Nanjun Zhang; Shuran Shao; Lixia Yang; Lixue Ouyang; Ping Wu; Fan Ma; Hongyu Duan; Kaiyu Zhou; Yimin Hua; et al. (Cardiovascular Toxicology, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Dynamic trends in maize diseases and pests across six regions in China over two decades - Hong-ying Cui; Amber Sciligo; Xiao-ling Tan; Cang Hui; Yong-sheng Zhang; Wei Li; Zi-qiao Zhou; Zhen-qing Peng; Ping Ma; Zhi-shu Xiao; Fang Ouyang (Crop Protection, 2024)

Pollution status and assessment of seven heavy metals in the seawater and sediments of Hangzhou Bay, China - Rong Zhu; Yan-Yan Zeng; Li-Min Liu; Lu Yin; Kai-Ping Xu; Wei-Feng Chen; Shang-Chun Li; Xiao-Feng Zhou (Marine Pollution Bulletin, 2024)

Application of botulinum toxin A in tissue repair and regeneration - Xuan-Zhu Guo; Ya-Nan Niu; Xuan Zhou; Qiao Wei; Meng Li; Jia-Ning Xia; Yu-Qi Cui; Chao-Xin Chai; Yi-Ming Wang; Li-Ping Chen (Toxicon, 2024)

Solving the storage location assignment of large-scale automated warehouse based on dynamic vortex search algorithm - Haoran Li; Jingsen Liu; Ping Hu; Huan Zhou (Swarm and Evolutionary Computation, 2024)

Promotion of antibiotic-resistant genes dissemination by the micro/nanoplastics in the gut of snail Achatina fulica - Yan-Mei Da; Xiao-Ru Yang; Ming-Jun Li; Shun-Shun Li; Ze-Ping Gao; Ying Zhang; Jian-Qiang Su; Guo-Wei Zhou (Science of The Total Environment, 2024)

Remediation of multi-metal(loid) contaminated soils using Mn-modified biochar: Mechanistic insights and influencing factors - Jin-Zhou Su; Xiao-Ning Feng; Ping Xiang; Zhao-Lai Guo; Li-Xin Li; Tao Zhang; Jun-Bao Yu (Process Safety and Environmental Protection, 2024)

Associations of maternal serum concentration of iron-related indicators with gestational diabetes mellitus in Chinese: A pilot prospective cohort study - Geng-dong Chen; Peng-sheng Li; Zi-xing Zhou; Ting-ting Pang; Hai-yan Wang; Xiao-yan Gou; Shao-xin Ye; Dong-xin Lin; Da-zhi Fan; Zheng-ping Liu (Journal of Trace Elements in Medicine and Biology, 2024)

Recent development on drought propagation: A comprehensive review - Zhaoqiang Zhou; Ping Wang; Linqi Li; Qiang Fu; Yibo Ding; Peng Chen; Ping Xue; Tian Wang; Haiyun Shi (Journal of Hydrology, 2024)

Stabilization of compound lead and arsenic contaminated soils by using two iron-based materials: Long-term efficacy - Chen Feng; Jiang-shan Li; An-nan Zhou; Wen-hao Jiang; Ping Wang; Qiang Xue (Journal of Environmental Chemical Engineering, 2024)

Snow depth retrieval method for PolSAR data using multi-parameters snow backscattering model - Haiwei Qiao; Ping Zhang; Zhen Li; Lei Huang; Zhipeng Wu; Shuo Gao; Chang Liu; Shuang Liang; Jianmin Zhou; Wei Sun (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Integration of automatic discontinuity identification and multi-scale hierarchical modeling for stability analysis of highly-jointed rock slopes - Ya-ping Wang; Jia-wen Zhou; Jun-lin Chen; Yu-chuan Yang; Fei Ye; Hai-bo Li (International Journal of Rock Mechanics and Mining Sciences, 2024)

Unraveling anti-aging mystery of green tea in C. elegans: Chemical truth and multiple mechanisms - Jia-ping Ke; Jia-Yi Li; Zi Yang; Hao-Yue Wu; Jing-Ya Yu; Yi Yang; Chen-Hui Chen; Peng Zhou; Fang Hua; Wei Wang; Fenglin Hu; Gang-Xiu Chu; et al. (Food Chemistry, 2024)

MoS2 coupled with ball milling co-modified sludge biochar to efficiently activate peroxymonosulfate for neonicotinoids degradation: Dominant roles of SO4•-, 1O2 and surface-bound radicals - Yifan Liu; Yongfei Ma; Zhikang Deng; Ping Li; Song Cui; Chenyu Zeng; Rui Mu; Yusheng Zhou; Xuebin Qi; Zulin Zhang (Environmental Research, 2024)

Avi-tag mediated Phage@gold nanoprobe illuminates bacteria - Ping Li; Mangmang Shen; Haojie Ge; Xinan Jiao; Xin Zhou; Xiang Chen (Chemical Engineering Journal, 2024)

EGR1 transcriptionally regulates SVEP1 to promote proliferation and migration in human coronary artery smooth muscle cells - Qiang Tian; Jia-He Chen; Yi Ding; Xin-Yu Wang; Jia-Yun Qiu; Qian Cao; Li-Li Zhuang; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2024)

Engineered bispecific antibodies with enhanced breadth and potency against SARS-CoV-2 variants and SARS-related coronaviruses - Fangfang Chang; Qian Wu; Yabin Hu; Zhendong Pan; Yong-Chen Liu; Yue-Zhou Li; Mihnea Bostina; Wenpei Liu; Ping Zhao; Xiaowang Qu; Yi-Ping Li (Medical Microbiology and Immunology, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

CD36-mediated ROS/PI3K/AKT signaling pathway exacerbates cognitive impairment in APP/PS1 mice after noise exposure - Zan Zhou; Wen-jun Jiang; Yan-ping Wang; Jun-qiang Si; Xian-si Zeng; Li Li (Science of The Total Environment, 2024)

Vegetation restoration enhancing soil carbon sequestration in karst rocky desertification ecosystems: A meta-analysis - Wei Zheng; Xiaobin Guo; Ping Zhou; Li Tang; Jiaxin Lai; Yuting Dai; Wende Yan; Jinshui Wu (Journal of Environmental Management, 2024)

1-Dimensional metal Nitride-Supported platinum nanoclusters for Low-Temperature hydrogen production from formic acid - Liang Qiu; Bowen Sheng; Haotian Ye; Ping Wang; Jinglin Li; Ying Li; Yixin Li; Tianqi Yu; Muhammad Salman Nasir; Xinqiang Wang; Hu Pan; Zhen Huang; et al. (Chemical Engineering Journal, 2024)

Tunable sulfur vacancies in amorphous-crystalline AC-Bi2S3-x@C derived from CAU-17 for efficient capture of radioiodine: Comparison of sulfur vacancies in amorphous and crystalline structures - Kai-Wei Chen; Xin-Yu Zhou; Yi-Ting Chen; Xiao-Jun Dai; Shu-Xuan Li; Ao-Tian Gu; Chun-Hui Gong; Peng Wang; Ping Mao; Ji-Gen Lu; Yi Yang (Chemical Engineering Journal, 2024)

Assessment of Microseismic Events via Moment Tensor Inversion and Stress Evolution to Understand the Rupture of a Hard–Thick Rock Stratum - Jie-Fang Song; Cai-Ping Lu; Arno Zang; Xiu-Feng Zhang; Jian Zhou; Zhao-Wei Zhan; Li-Ming Zhao (Rock Mechanics and Rock Engineering, 2024)

Aberrant Enhanced NLRP3 Inflammasomes and Cell Pyroptosis in the Brains of Prion-Infected Rodent Models Are Largely Associated with the Proliferative Astrocytes - Dong-Hua Zhou; Xiao-Xi Jia; Yue-Zhang Wu; Wei-Wei Zhang; Yuan Wang; Dong-Lin Liang; Li-Ping Gao; Kang Xiao; Cao Chen; Xiao-Ping Dong; Qi Shi (Molecular Neurobiology, 2024)

Association of Plasma Metal Levels with Outcomes of Assisted Reproduction in Polycystic Ovary Syndrome - Dan Yin; Rui Mao; Die Wang; Ping Yu; Cuilan Zhou; Jun Liu; Suyun Li; Yulin Nie; Hongqing Liao; Cuiying Peng (Biological Trace Element Research, 2024)

Characterization and genomic analysis of phage vB_SmaP_c9-N, a novel Stenotrophomonas maltophilia podophage with antibiofilm activity - Yaosheng Xi; Wei Zhou; Xiao Li; Xiangru Lan; Qili Yang; Yu-Ping Huang (Archives of Virology, 2024)

Simulation of canopy urban heat island at a block scale based on local climate zones and urban weather generator: a case study of Beijing - Wenzhi Zhang; Hongyuan Huo; Xiaowei Geng; Ping Zhou; Li Guo; Zhao-Liang Li (International Journal of Remote Sensing, 2024)

A longitudinal Study on the Effect of Media Exposure on Travel Intention during Public Health Crises - Bin Zhou; Yuxin Wang; Ping Li; Qihao Xiong; Chris Ryan (Environment, Development and Sustainability, 2024)

Microplastics in the human body: A comprehensive review of exposure, distribution, migration mechanisms, and toxicity - Yue Li; Liping Chen; Nonglin Zhou; Yuyuan Chen; Zhichen Ling; Ping Xiang (Science of The Total Environment, 2024)

ESR chronology of the Quaternary sedimentary sequence of the Shinaimiao borehole in Hebi City, Henan Province, China - Hao Ji; Zhong-shan Shen; Chun-Ru Liu; Xiong-Nan Huang; Xiao-Ping Yang; Chuan-Yi Wei; Xin-Xiu Li; Qing Zhou; Gong-Ming Yin (Quaternary Geochronology, 2024)

RAD-seq data for Engelhardia roxburghiana provide insights into the palaeogeography of Hainan Island and its relationship to mainland China since the late Eocene - Pei-Han Huang; Tian-Rui Wang; Min Li; Zi-Jia Lu; Ren-Ping Su; Ou-Yan Fang; Lang Li; Shi-Shun Zhou; Yun-Hong Tan; Hong-Hu Meng; Yi-Gang Song; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Occurrence and maturation transformation of organic and inorganic nitrogen in the Lower Cambrian shelf–slope facies shale: Implications for overmature N2-rich shale reservoirs in Southern China - Guangming Meng; Haifeng Gai; Xiumin Yang; Ping Gao; Qin Zhou; Chengang Lu; Gang Li; Xing Wang; Peng Cheng (Marine and Petroleum Geology, 2024)

Combating coal-burning-borne endemic arsenism in Shaanxi Province, Northwest China: The impact of high-arsenic coal ban, improved cook-stoves, and health education - Yujie Ning; Chaowei Wang; Shujin Li; Sijie Chen; Feiyu Zhang; Rong Zhou; Yuequan Yuan; Xi Lv; Yifan Wu; Yu Zhang; Zhongxue Fan; Xiaoqian Li; et al. (Journal of Hazardous Materials, 2024)

Investigating the thermal stability and calcium resistance of O/W emulsions prepared with glycosylated whey protein hydrolysates modified by different saccharides - Congzhen Shi; Yuanyuan Deng; Zhiming Wang; Yan Zhang; Xiaojun Tang; Zhihao Zhao; Ping Li; Pengfei Zhou; Guang Liu; Mingwei Zhang (Food Chemistry, 2024)

Effect of turbulent mixing on the formation of intermediate nepheloid layer over the northern continental slope of the Andaman sea - Ruijie Ye; Feng Zhou; Xiao Ma; Chenggang Liu; Qicheng Meng; Di Tian; Ruoyu Guo; Hongliang Li; Lu Shou; Ping Du; Soe Moe Lwin (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

Multifunctional and immunoregulatory microenvironment-responsive hydrogel for whole course management of infected diabetic wounds - Zhenyu Luo; Xiaoxue Fu; Hua Jiang; Weikun Meng; Shue Jin; Yongrui Cai; Ze Du; Ping Song; Anjing Chen; Li Li; Peifang Li; Jiali Chen; et al. (Chemical Engineering Journal, 2024)

Unravelling ice growth characteristics beneath cloud tops with joint analysis of airborne Ka-band radar and Himawari observations - Shuangzhi You; Delong Zhao; Haoran Li; Wei Zhou; Yuanmou Du; Ping Tian; Jiujiang Sheng; Wei Xiao; Fei Wang; Hui He; Mengyu Huang; Deping Ding; et al. (Atmospheric Research, 2024)

Microbial metabolism strengths carbon sequestration and crop yield in upland red soil after long-term ex situ incorporation of straw - Li Tang; Xiaobin Guo; Daoyou Huang; Xiaomeng Wei; Hao Sheng; Pei Luo; Ping Zhou; Wei Gao; Yan Li; Miaomiao Zhang; Wei Zheng; Jinshui Wu (Journal of Soils and Sediments, 2024)

Microbial Community Structure and Metabolism of Xinjiang Fine-Wool Sheep based on High-Throughput Sequencing Technology - Rui Yao; Fulin Li; Xuyang Dong; Yueren Xu; Ruirui Hu; Limin Wang; Kuojun Cai; Xiaogang Liu; Wei Ni; Ping Zhou; Shengwei Hu (Current Microbiology, 2024)

Manganese mineralization constrained by redox conditions in the Cryogenian Nanhua Basin, South China and its implications for nitrogen and carbon cycling - Ping Wang; Jian Wang; Yuansheng Du; Wenchao Yu; Qi Zhou; Li Tian; Liangjun Yuan; Wen Pan; Wei Wei; Yongjun Qin; Zhixin Ma (Frontiers in Marine Science, 2024)
The Nanhua Basin of South China recorded complete Cryogenian stratigraphic sequence from the Sturtian Glaciation (~717–660 Ma) to the Marinoan Glaciation (~654–635 Ma). The interglacial Datangpo Fm in the Nanhua Basin is divided into two members, and the first member consists of the Mn-carbonate unit and the overlying black shale unit, containing a series of large and superlarge manganese deposits. The metallogenic process of manganese deposits is not clear, and the Mn-carbonates formed through the precursor of Mn-oxide/oxyhydroxide reduction or directly precipitated from an anoxic water column. Moreover, the redox conditions in the deep Nanhua Basin during the precipitation of manganese deposits are also controversial. In this study, the high-resolution nitrogen contents (TN), isotope compositions, carbon isotope compositions of organic and inorganic matter from the first member of the Datangpo Fm are analyzed. The δ 15 N values of the Mn-carbonate unit (+1.53‰ to +5.26‰, mean +3.36‰) are higher than those of the overlying black shale unit (−3.74‰ to +3.54‰, mean +0.89‰). The Mn contents show a negative relationship with TN but a positive relationship with δ 15 N in the Mn-carbonate unit, implying that the formation of Mn-carbonates is related to redox variations. The relatively higher δ 15 N values in the Mn-carbonate unit indicated oxic conditions, and NH 4 + can be released and partially oxidized during the mineralization of organic matter, resulting in the residual 15 N-enriched NH 4 + being transferred into clay minerals. Meanwhile, the lower δ 15 N values in the black shale unit indicated anoxic conditions, which recorded primary N isotope signals. The Mn-carbonate unit is characterized by negative δ 13 C carb values (−11.17‰ to −5.22‰, mean −8.30‰), which show a positive relationship with δ 13 C org , but a negative relationship with Mn contents, implying that the negative δ 13 C carb excursions were related to the organic matter degradation during Mn-carbonate formation. The findings of this study indicated that the metallogenesis of manganese deposits in the Cryogenian Nanhua Basin was constrained mainly by the oxic interval in the deep basin. The nitrogen and carbon cycling process can provide new insights into geochemical cycling after the Sturtian Glaciation.

Rich-silicon rice husk ash increases iron plaque formation and decreases cadmium and arsenic accumulation in rice seedlings - Jiao-Feng Gu; Xuan-Tao Yi; Kun Ouyang; Qian Li; Ping You; Rui Zhou; Peng Zeng; Ye Liao; Hang Zhou (Chemosphere, 2024)

Label-free and ultrasensitive detection of environmental lead ions based on spatially localized DNA nanomachines driven by hyperbranched hybridization chain reaction - Xiao-Yu Li; Bo-Xi Zhou; Yu-Ling Xiao; Xin Liu; Yong-Qian Wang; Ming-Min Li; Jun-Ping Wang (Journal of Hazardous Materials, 2024)

A novel bacteriocin against methicillin-resistant Staphylococcus aureus, purified from Lactiplantibacillus plantarum ZFM9 - Zhongdu Ye; Huifei Shentu; Qingqing Zhou; Danli Wu; Ping Li; Qing Gu (Food Chemistry, 2024)

Histopathology and transcriptome profiling reveal features of immune responses in gills and intestine induced by Spring viremia of carp virus - Ping Ouyang; Qiunan Li; Shuya Liu; Yankai Li; Shuhan Li; Yongheng Zhou; Peng jia; Defang Chen; Xiaoli Huang; Yi Geng (Fish & Shellfish Immunology, 2024)

The impact of socioeconomic factors on vegetation restoration in karst regions: A perspective beyond climate and ecological engineering - Ershuang Yuan; Qiuwen Zhou; Weihong Yan; Dawei Peng; Yalin Wang; Xinglan Yang; Ping Li (Ecological Engineering, 2024)

Fe-reinforced silkworm silk with superstrong mechanical properties for mass production - Qingsong Liu; Xin Wang; Yifan Zhou; Yi Li; Zhangchuan Peng; Zhangchen Tang; Xiangyu Cai; Xinyu Fan; Xin Tang; Xiaoyin Tan; Xiaoqian Xie; Xinning Li; et al. (Chemical Engineering Journal, 2024)

Antibacterial and gut health effects of Amomum tsao‐ko in aquatic feed: A sustainable alternative to chemical antibiotics - Weiyao Peng; Guohui Liao; Lianzhang Wu; Jian Zhang; Juncai He; Penghui Gao; Yunsheng Cha; Shengjun You; Mei Huang; Jilan Zhou; Yuqiu He; Yi Yang; et al. (Journal of Fish Biology, 2024)
Amomum tsao‐ko Crevost et Lemarie (Zingiberaceae), an aromatic plant, has been considered to have diverse medicinal values and economic significance. It has been reported to possess antibacterial, antioxidant, and antidiabetic effects. With the increasing risk of diseases in aquaculture, there is a need for alternative solutions to chemical antibiotics. Plant extracts have shown promise as natural feed additives for aquatic animals. In this study, the antibacterial effect of Amomum tsao‐ko crude extracts was evaluated using the Oxford cup method. The extracts exhibited significant antimicrobial activity against Salmonella typhimurium and Salmonella enteritidis . Furthermore, the addition of Amomum tsao‐ko to fish feed resulted in notable changes in the gut structure of zebrafish and tilapia. The length and morphology of intestinal villi were enhanced, promoting improved digestion. Analysis of the gut microbial community revealed that Amomum tsao‐ko supplementation induced key changes in the gut microbial community composition of both zebrafish and tilapia. Notably, a 1% inclusion of Amomum tsao‐ko resulted in a marked rise in Proteobacteria levels in zebrafish, which diminished at 10% dosage. The supplement elicited mixed reactions among other bacterial phyla like Actinobacteria and Verrucomicrobiota. Fluctuations were also observed at the genus level, pointing to the concentration of Amomum tsao‐ko playing a pivotal role in influencing the structure of intestinal bacteria. The findings of this study suggest that Amomum tsao‐ko has antibacterial properties and can positively influence the gut health of fish. The potential use of Amomum tsao‐ko as a natural feed additive holds promise for improving aquaculture practices and reducing reliance on chemical antibiotics. Further research is needed to explore the full potential and applications of Amomum tsao‐ko in fish feed development.

Molecular characterization of fad6 gene and its transcriptional changes in response to different initial diets and nutritional status in yellow catfish (Pelteobagrus fulvidraco) - Bo Zhou; Xiu-Ying Wei; Zheng-Yong Wen; Bin Wang; Yu-Ying Zhao; Wan-Hong Zeng; Yu He; Panita Prathomya; Yun-Yun Lv; Yan-Ping Li; Jun Wang; Rui Li; et al. (Frontiers in Marine Science, 2024)
Fatty acid desaturases (FADs) are rate-limiting enzymes for the biosynthesis of highly unsaturated fatty acids (HUFAs). As a new member of the FAD family, Fad6 and its roles remain unclear in various teleost fishes. In this study, we identified a fad6 gene from yellow catfish (yc fad6 ) and determined its spatiotemporal expression patterns and responses to different initial diets and nutritional status in yellow catfish. Our results showed that the open reading frame (ORF) of yc fad6 was 1,080 bp in length, encoding a protein of 359 amino acids. Multiple protein sequences alignment proved that fad6 is highly conserved among diverse vertebrates. Meanwhile, phylogenetic analysis revealed that Southern catfish and yellow catfish were clustered into one branch, supporting evolutionary consistence between the fad6 gene and fish morphology. Moreover, comparisons of genomic synteny and gene structure revealed functional and evolutionary conservation of the fad6 gene in various teleost fishes. Tissue distribution analysis by quantitative RT-PCR demonstrated that the yc fad6 gene was extensively expressed in examined tissues, with higher transcription levels in the heart and liver. Meanwhile, yc fad6 gene was widely expressed in various developmental stages, indicating Fad6 may play important roles in HUFA biosynthesis at early developmental stages in yellow catfish. Functional experiments verified that the transcription of yc fad6 decreased significantly with the extension of feeding time (with egg yolk or Artemia nauplii ) at the early developmental stages, indicating that a diet rich in HUFA can remarkably inhibit the transcription of yc fad6 in yellow catfish. In addition, yc fad6 transcription was significantly reduced after a short-term (24-h) or long-term food deprivation (1-week) and then continued to decrease during refeeding, suggesting that nutritional states can affect the transcription of yc fad6 , which further regulates the metabolism of HUFAs. Anyway, these fundamental findings provide basic references for further investigating evolutionary and physiological functions of the fad6 gene in yellow catfish as well as in other teleost fishes.

Two pairs of new isobenzofuranone enantiomers from a soil-derived fungus Penicillium canescens DWS225 - Jing Wang; Xiao-Qian Wu; Ji-Song Mo; Yu-Fen Tan; Hong-Ping Long; Si-Qian Zhou; Shao Liu; Jing Li; Wen-Xuan Wang (Natural Product Research, 2024)

Microbial metabolic capacity regulates the accrual of mineral-associated organic carbon in subtropical paddy soils - Zhe Li; Xun Duan; Xiaobin Guo; Wei Gao; Yan Li; Ping Zhou; Qihong Zhu; Anthony G. O'Donnell; Ke Dai; Jinshui Wu (Soil Biology and Biochemistry, 2024)

Development of T cell antigen-based human coronavirus vaccines against nAb-escaping SARS-CoV-2 variants - Hao Zhou; Ping Leng; Yang Wang; Kaiwen Yang; Chen Li; David M. Ojcius; Pengfei Wang; Shibo Jiang (Science Bulletin, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

Multi-spectroscopic characterization of organic salt components in medicinal plant - Lingyu Han; Fang Ma; Ping He; Qun Zhou; Zhanping Li; Suqin Sun (Food Chemistry, 2024)

Structural characterization of modified soy protein isolate composite coatings and its application on fresh-cut cantaloupe (Cucumis melo cv. Xiaomi) - Tian Yang; Dan-Dan Zhou; Cai-E Wu; Ting-Ting Li; Gong-Jian Fan; Xiao-Jing Li; Kai-Ping Cong; Zhi-Cheng Yan; Xin Cheng (Food Bioscience, 2024)

Evolution of morphology, structure, and performance of the COF membranes with monomer concentrations: Enabling effective desalination and kinetics analysis - Li-ping Yue; Fan-xin Kong; Yi Wang; Guang-dong Sun; Ai-guo Zhou; Jin-fu Chen (Desalination, 2024)

Removal of radioactive iodine by Cu2O prepared with PVP as an active agent: Role of crystal facets and oxygen vacancy in adsorption mechanisms - Xiao-Jun Dai; Kai-Wei Chen; Man-Li He; Kai Chen; Xin-Yu Zhou; Yi-Ting Chen; Chun-Hui Gong; Peng Wang; Ping Mao; Yi Yang (Chemical Engineering Journal, 2024)

Downregulation of OATP2B1 by proinflammatory cytokines leads to 5-ASA hyposensitivity in Ulcerative colitis - Ping Li; Jun Luo; Yiming Jiang; Xiaoyi Pan; Minlei Dong; Binxin Chen; Jinhai Wang; Hui Zhou; Huidi Jiang; Yangri Duan; Nengming Lin (Chemico-Biological Interactions, 2024)

Adenylate kinase phosphate energy shuttle underlies energetic communication in flagellar axonemes - Huan Wu; Yanman Zhang; Yuqian Li; Shuya Sun; Jintao Zhang; Qingsong Xie; Yue Dong; Shushu Zhou; Xuan Sha; Kuokuo Li; Jinyi Chen; Xin Zhang; et al. (Science China Life Sciences, 2024)

An engineered DNA aptamer-based PROTAC for precise therapy of p53-R175H hotspot mutant-driven cancer - Lingping Kong; Fanlu Meng; Ping Zhou; Ruixin Ge; Xiaoshan Geng; Zhihao Yang; Guo Li; Linlin Zhang; Jing Wang; Jinfeng Ma; Cheng Dong; Jun Zhou; et al. (Science Bulletin, 2024)

Anti-inflammatory discovery of sesquiterpenoids and a jasmonic acid derivative from Artemisia stolonifera - Ting Wu; Wen-Jing Wang; Zhou-Yuan Li; Yi-Tian Liu; Tian-Ping Yu; Shuang-Ge Li; Hong-Zhi Du; Chun Gui; Da-Hui Liu; Xiao-Long Yang (Phytochemistry, 2024)

Heterogeneous catalytic ozonation of ciprofloxacin in wastewater with red mud: Characterization and performance - Fuyu Huang; Huiru Ma; Zhanyao Li; Liqiang Zhang; Jun Li; Shouyan Chen; Ping Zhou; Guifang Chen (Journal of Water Process Engineering, 2024)

Sulfur vacancy-rich bismuth sulfide nanowire derived from CAU-17 for radioactive iodine capture in complex environments: Performance and intrinsic mechanisms - Kai-Wei Chen; Xin-Yu Zhou; Xiao-Jun Dai; Yi-Ting Chen; Shu-Xuan Li; Chun-Hui Gong; Peng Wang; Ping Mao; Yan Jiao; Kai Chen; Yi Yang (Journal of Hazardous Materials, 2024)

Relish-mediated C2H2 zinc finger protein IMZF restores Drosophila immune homeostasis via inhibiting the transcription of Imd/Tak1 - Hongjian Zhou; Li Liu; Yujia Pang; Yina Xu; Jing Wu; Fei Ma; Ping Jin; Xue Zhou (Insect Biochemistry and Molecular Biology, 2024)

Comparative plastomes of eight subgenus Chamaesyce plants and system authentication of Euphorbiae Humifusae Herba - Long Wang; Ziting Huo; Wenbo Xu; Peina Zhou; Wenxiang Nan; Huijun Guo; Qianwen Zhang; Peng Yang; Raphael N. Alolga; Xiaojian Yin; Ping Li; Xu Lu (Food Chemistry, 2024)

A newly-discovered tea population variety processed Bai Mu Dan white tea: Flavor characteristics and chemical basis - Yanping Lin; Yibiao Huang; Su Zhou; Xiaolan Li; Yike Tao; Yani Pan; Xinyu Feng; Haowei Guo; Ping Chen; Qiang Chu (Food Chemistry, 2024)

Molecular characterization, expression analysis and function identification of Pf_IL-12p35, Pf_IL-23p19 and Pf_IL-12p40 genes in yellow catfish (Pelteobagrus fulvidraco) - Xin-Xin Jiang; Zi-Rui Tang; Zhang-Ping Li; Gui-Rong Zhang; Xu Zhou; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2024)

Pathological variations and immune response in Channa argus infected with pathogenic Nocardia seriolae strain - Tingting Zhou; Ping Cai; Junwei Li; Xueming Dan; Zhongsheng Li (Fish & Shellfish Immunology, 2024)

Prokaryotic community assembly patterns and nitrogen metabolic potential in oxygen minimum zone of Yangtze Estuary water column - Yihua Sun; Ping Du; Hongliang Li; Konglin Zhou; Lu Shou; Jianfang Chen; Meng Li (Environmental Research, 2024)

Ternary-coordination-regulated polyamide nanofiltration membranes for Li+/Mg2+ separation - Shang Fang; Kecheng Guan; Siyu Zhou; Qiangqiang Song; Yongxuan Shi; Wenming Fu; Zhan Li; Ping Xu; Mengyang Hu; Zhaohuan Mai; Pengfei Zhang; Hideto Matsuyama (Desalination, 2024)

Natural polysaccharide-dominated synthesis of MnO2 nanoparticles as textile coating for efficiently removing indoor bacteria and air pollutants - Xueming Bao; Yun Yuan; Zirong Li; Yuanyuan Yu; Li Cui; Man Zhou; Qiang Wang; Ping Wang (Chemical Engineering Journal, 2024)

Amorphous/Graphitic carbon phase engineering of Corrosion-Resistant Fe@C Core-Shell nanowires for optimized dipole polarization and enhanced microwave absorption - Ping-an Yang; Wenjiao Deng; Haibo Ruan; Zhengwei Qu; Rui Li; Lirui Wang; Jiufei Luo; Zhihao Zhou; Mengjie Shou; Xin Huang; Qiao Chen; Xinglong Gong (Chemical Engineering Journal, 2024)

Biosafety assessments of hexafluoropropylene trimer derivative as a fluorinated cooling fluid for electronics - Yi-Tong Zhou; Pei-Jie Zhang; Shu-Ping Wang; Chang-Hao Li; Jia-Qing Zhang; Wei-Xin Zhang; Yuan-Di Zhao; Yuan-Cheng Cao; Jin-Xuan Fan (Toxicological Research, 2024)

Potential Plausible Role of Stem Cell for Treating Depressive Disorder: a Retrospective Review - Zhuo Chang; Qing-yi Wang; Lu-hao Li; Bei Jiang; Xue-ming Zhou; Hui Zhu; Yan-ping Sun; Xue Pan; Xu-xu Tu; Wei Wang; Chen-yue Liu; Hai-xue Kuang (Molecular Neurobiology, 2024)

Unveiling the molecular mechanisms of size-dependent effect of polystyrene micro/nano-plastics on Chlamydomonas reinhardtii through proteomic profiling - Xiaoxue Li; Zheng Chu; Chenran Feng; Ping Song; Tong Yang; Lirun Zhou; Xin Zhao; Xin Chai; Jiale Xing; Sa Chen; Junzhe Zhang; Jigang Wang; et al. (Chemosphere, 2024)

Seasonal characterization of chemical and optical properties of water-soluble organic aerosol in Beijing - Bo You; Zhiqiang Zhang; Aodong Du; Yan Li; Jiaxing Sun; Zhijie Li; Chun Chen; Wei Zhou; Weiqi Xu; Lu Lei; Pingqing Fu; Shengjie Hou; et al. (Science of The Total Environment, 2024)

Experimental study on the hydrodynamic performance of a side-by-side box-membrane breakwater - Jing-Ping Wu; Chuan-Rui Li; Jing-Jing Qi; Xing-Yu Xu; Jia-Ning Li; Xiu-Xing Zhang; Qing Qin; Zhi-Rong Zhou (Ocean Engineering, 2024)

Establishment and characterization of a golden pompano (Trachinotus blochii) fin cell line for applications in marine fish pathogen immunology - Jin-Feng Tong; Lang Yu; Rui-Hai Gan; Li-Ping Shi; Shao-Yang Bu; Yue Gu; Xin Wen; Jun-Long Sun; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2024)

Polypeptide urea increases rice yield and nitrogen use efficiency through root growth improvement - Shuang Liao; Fei Deng; Wei Zhou; Li Wang; Wu Li; Hui Hu; Shi-lin Pu; Shu-xian Li; Yong Chen; You-feng Tao; Chi Zhang; Qiu-ping Li; et al. (Field Crops Research, 2024)

Chemical constituents from Strobilanthes cusia and their chemotaxonomic significance - Si-Qi Huang; Chao-Tian He; Qiu-Ying He; Gui-Shuai Lang; Hong-Jie Chen; Li-Ping Teng; Zhong-Bo Zhou (Biochemical Systematics and Ecology, 2024)

Research and application progress of microbial β-mannanases: a mini-review - Ping Wang; Xiaohui Pei; Weiqiang Zhou; Yue Zhao; Pengfei Gu; Yumei Li; Juan Gao (World Journal of Microbiology and Biotechnology, 2024)

Silencing of ApCht7 and ApCht10 revealed their function and evaluation of their potential as RNAi targets in Acyrthosiphon pisum - Chunchun Li; Lixiang Wang; Lei Liu; Ning Lv; Yu-Ping Gou; Senshan Wang; Jing-Jiang Zhou; Chang-Zhong Liu (Journal of Pest Science, 2024)

Lentinan mitigates pemetrexed chemoresistance by the PI3K/Akt pathway in non-small cell lung cancer - Ping Tian; Dajun Du; Li Yang; Nan Zhou; Ling Tao (Cell Biochemistry and Biophysics, 2024)

Research progress on improving the freeze-drying resistance of probiotics: A review - Sitong Ge; Jiarun Han; Qiaoyu Sun; Qingqing Zhou; Zhongdu Ye; Ping Li; Qing Gu (Trends in Food Science & Technology, 2024)

Binding properties of chemosensory protein 4 in Riptortus pedestris to aggregation pheromones - Jin-Bu Li; Qiang Liu; Sai Ma; Yue-Ying Wang; Xing-Zhou Liu; Chao-Wei Wang; Da-Jiang Wang; Zhuang-Zhuang Hu; Jia-Wen Gan; Xiu-Yun Zhu; Bao-Ping Li; Mao-Zhu Yin; et al. (Pesticide Biochemistry and Physiology, 2024)

Spatio-temporal patterns of intense tropical cyclones in the Western North Pacific over the past 1600 years - Liang Zhou; Rumeng Hao; Mingchen Li; Yan Su; Shu Gao; Yang Yang; Zhixiong Shen; Jianjun Jia; Ya Ping Wang (Marine Geology, 2024)

Water distribution in pore systems and its influences on gas-bearing property of deep shale: A case study of the Longmaxi Formation in the Luzhou area, southern Sichuan Basin - Yue Feng; Xianming Xiao; Ping Gao; Dongfeng Hu; Ruobing Liu; Gang Li; Chengang Lu; Qin Zhou (Marine and Petroleum Geology, 2024)

Geochemical characteristics of Ordovician crude oils in the FI17 strike-slip fault zone of the Fuman oilfield, Tarim basin: Implications for ultra-deep hydrocarbon accumulation in the Tarim basin - Zhongdeng Lu; Hongwei Ping; Honghan Chen; Yanqiu Zhang; Zhou Xie; Yintao Zhang; Zulin Chen; Xin Yang; Xinle Zhang; Kang Yang; Xiaoqiang Li (Marine and Petroleum Geology, 2024)

Catalytic ozonation of ammonia nitrogen with powdered activated coke: Influence of operational parameters and surface chemistries - Guifang Chen; Huiru Ma; Fuyu Huang; Zhanyao Li; Liqiang Zhang; Jun Li; Ping Zhou; Shouyan Chen; Yongwei Li (Journal of Water Process Engineering, 2024)

Artificial microbial consortia engineering: Intensify nitrogen removal from mature landfill leachate by simultaneous nitrification and denitrification - Xia Ke; Yi-Xin Li; Ting-Ting Guo; Zu-Lian Liao; Su-Qin Tang; Yi-Cheng Zhang; Shi-Peng Zhou; Ya-Ping Xue; Yu-Guo Zheng (Journal of Water Process Engineering, 2024)

A bipolar SMPS network for measuring atmospheric aerosols using natural air ions - Yiran Li; Jin Wu; Hao Wu; Xiaomeng Liu; Qi Zhou; Yiqun Lu; Yuhang Wu; Mengyu Liu; Hengjia Ou; Shixin Mai; Xuehui He; Huaying Song; et al. (Atmospheric Environment, 2024)

Effect of Perilla seeds inclusion on the performance, egg quality characteristics, biochemical parameters and egg yolk fatty acid composition of laying hens - Ping Li; Samiullah Khan; Yanhua Huang; Shengtao Lu; Panhong Zhou; Jiale Ling; Tianzheng Xu; Xiaoli Shi (Tropical Animal Health and Production, 2024)

Maintenance of callus-associated endophyte balance to mitigate oxidative browning in plant tissue culture practices - Yu-Tao Wang; Chun-Xiao Chen; Ping Zhou; Chun-Xi Lu; Yun Wen; Yu Li; Xiao-Xia Pan; Shu-Sheng Zhu; Ming-Zhi Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Correlation of Immune-Inflammatory Response System (IRS)/Compensatory Immune-Regulatory Reflex System (CIRS) with White Matter Integrity in First-Episode Patients with Schizophrenia - Mengzhuang Gou; Wei Li; Jinghui Tong; Yanfang Zhou; Ting Xie; Ting Yu; Wei Feng; Yanli Li; Song Chen; Baopeng Tian; Shuping Tan; Zhiren Wang; et al. (Molecular Neurobiology, 2024)

Drought shortens subtropical understory growing season by advancing leaf senescence - Huanfa Sun; Liming Yan; Zhao Li; Wanying Cheng; Ruiling Lu; Xingli Xia; Jiaye Ping; Chenyu Bian; Ning Wei; Cuihai You; Songbo Tang; Ying Du; et al. (Global Change Biology, 2024)
Subtropical forests, recognized for their intricate vertical canopy stratification, exhibit high resistance to extreme drought. However, the response of leaf phenology to drought in the species‐rich understory remains poorly understood. In this study, we constructed a digital camera system, amassing over 360,000 images through a 70% throughfall exclusion experiment, to explore the drought response of understory leaf phenology. The results revealed a significant advancement in understory leaf senescence phenology under drought, with 11.75 and 15.76 days for the start and end of the leaf‐falling event, respectively. Pre‐season temperature primarily regulated leaf development phenology, whereas soil water dominated the variability in leaf senescence phenology. Under drought conditions, temperature sensitivities for the end of leaf emergence decreased from −13.72 to −11.06 days °C −1 , with insignificance observed for the start of leaf emergence. Consequently, drought treatment shortened both the length of the growing season (15.69 days) and the peak growth season (9.80 days) for understory plants. Moreover, this study identified diverse responses among intraspecies and interspecies to drought, particularly during the leaf development phase. These findings underscore the pivotal role of water availability in shaping understory phenology patterns, especially in subtropical forests.

A study on expression of GRP78 and CHOP in neutrophil endoplasmic reticulum and their relationship with neutrophil apoptosis in the development of sepsis - Jinchuan Zhao; Ping Yang; Li Lu; Tao Yi; Yunfeng Li; Wei Mao; Qin Zhou; Ke Lin (Journal of Biosciences, 2024)

Changes in size-dependent Chlorophyll a concentration and group-specific picophytoplankton abundance in short-term nutrient-addition experiments in the Equatorial Eastern Indian Ocean - Ping Sun; Kai-Ming Sun; Yuping Zhou; Lu Liu; Chao Yuan; Zongjun Xu; Yan Li; Xuelei Zhang; Zongling Wang (Frontiers in Marine Science, 2024)
To clarify the changes in phytoplankton community and influencing factors in short-term nutrient-addition experiments in the Equatorial Eastern Indian Ocean, we conducted three experiments (one in situ-like experiment, one on-deck experiment with deep seawater, and one on-deck experiment with surface seawater). Our findings indicate that when nutrients were added, there was a more significant increase in the chlorophyll a (chl a ) concentrations of microphytoplankton (>20 μm) compared to those of nanophytoplankton (2-20 μm) and picophytoplankton (<2 μm). The chl a concentrations for phytoplankton <20 μm only exhibited significant increases in the on-board incubation of surface seawater collected at 1300 hr when grazing stress have likely been weak. In picophytoplankton, occasional increases in the abundances of Synechococcus were found, while the abundances of Prochlorococcus and eukaryotic picophytoplankton (Peuk) did not increase significantly. It results likely from the preference of grazing effect by herbivores and bottle effects. Additionally, the Prochlorococcus from 75 m was more adapted to weak light, thus its abundance sharply decreased when incubated under high light. We suggest that the nutrient effects have greater influence on microphytoplankton, but other factors, such as grazing and light, might contribute more to <20 μm phytoplankton. Furthermore, bottle effects should be considered when conducting incubation experiments.

Comparison of different sewage sludge pretreatment technologies for improving sludge solubilization and anaerobic digestion efficiency: A comprehensive review - Pan Zhou; Dunjie Li; Cong Zhang; Qian Ping; Lin Wang; Yongmei Li (Science of The Total Environment, 2024)

Plasma-activated water regulates water distribution to resist softening of goji berries - Kai-Ping Cong; Cai-E. Wu; Ting-Ting Li; Gong-Jian Fan; Dan-dan Zhou; Xiao-jing Li; An-Di Suo; Xu Li (Postharvest Biology and Technology, 2024)

Molecular mechanism of efficient degradation of TPM dyes by Serratia species WKD at high temperature - Yi Wei; Xin-Jiao Dong; Gang Li; Huan Wu; Lin-Na Du; Jia-Cheng Zhou; Jun Zhang; Yan-Ping Xiao; Yue-Mei Shang; Hong-Xia Liu (International Biodeterioration & Biodegradation, 2024)

Engine-out emissions from an ammonia/diesel dual-fuel engine – The characteristics of nitro-compounds and GHG emissions - Run Chen; Tie Li; Xinran Wang; Shuai Huang; Xinyi Zhou; Shiyan Li; Ping Yi (Fuel, 2024)

Exosome-functionalized heterogeneous nanofibrous scaffolds repair bone defects accompanied by muscle injury - Shue Jin; Zeyu Luo; Yongrui Cai; Jing Wen; Pengyu Lu; Xiaoxue Fu; Ping Mou; Anjin Chen; Weikun Meng; Jidong Li; Zongke Zhou; Weinan Zeng (Chemical Engineering Journal, 2024)

Host-guest synergistic hydrogen bond triggered signal amplification for visualizing the plant hormone salicylic acid - A-Ling Tang; Li-Long Zhang; Shuai Tan; Ping Yang; Wei Niu; Mei-Hong Ge; Lin-Lin Yang; Pei-Yi Wang; Li-Wei Liu; Xiang Zhou; Song Yang (Chemical Engineering Journal, 2024)

Quercetin attenuates cisplatin-induced mitochondrial apoptosis via PI3K/Akt mediated inhibition of oxidative stress in pericytes and improves the blood labyrinth barrier permeability - Tian-Lan Huang; Wen-Jun Jiang; Zan Zhou; Tian-Feng Shi; Miao Yu; Meng Yu; Jun-Qiang Si; Yan-Ping Wang; Li Li (Chemico-Biological Interactions, 2024)

Inflammatory cell death PANoptosis is induced by the anti-cancer curaxin CBL0137 via eliciting the assembly of ZBP1-associated PANoptosome - Ya-Ping Li; Zhi-Ya Zhou; Liang Yan; Yi-Ping You; Hua-Yu Ke; Tao Yuan; Hai-Yan Yang; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Inflammation Research, 2024)

Persistence of fertilization effects on soil organic carbon in degraded alpine wetlands in the Yellow River source region - Peng Duan; Rongyi Wei; Fangping Wang; Yongxiao Li; Ci Song; Bixia Hu; Ping Yang; Huakun Zhou; Buqing Yao; Zhizhong Zhao (Journal of Mountain Science, 2024)

Long-term cadmium exposure induces epithelial-mesenchymal transition in breast cancer cells by activating CYP1B1-mediated glutamine metabolic reprogramming in BT474 cells and MMTV-Erbb2 mice - Jingdian Li; Peng Gao; Mingke Qin; Junhua Wang; Yan Luo; Ping Deng; Rongrong Hao; Lei Zhang; Mindi He; Chunhai Chen; Yonghui Lu; Qinlong Ma; et al. (Science of The Total Environment, 2024)

Active dark carbon fixation evidenced by 14C isotope assimilation and metagenomic data across the estuarine-coastal continuum - Bolin Liu; Yanling Zheng; Xinyu Wang; Lin Qi; Jie Zhou; Zhirui An; Li Wu; Feiyang Chen; Zhuke Lin; Guoyu Yin; Hongpo Dong; Xiaofei Li; et al. (Science of The Total Environment, 2024)

Indole alkaloids isolated from the Nicotiana tabacum-derived Aspergillus fumigatus 0338 as potential inhibitors for tobacco powdery mildew and their mode of actions - Yue-Yu Ma; Gui Pu; Hua-Yin Liu; Sui Yao; Guang-Hui Kong; Yu-Ping Wu; Yin-Ke Li; Wei-Guang Wang; Min Zhou; Qiu-Fen Hu; Feng-Xian Yang (Pesticide Biochemistry and Physiology, 2024)

Multistage and diverse melt-mantle interaction in dunite-harzburgite channel systems beneath oceanic slow-ultraslow spreading centers: Evidence from the Xigaze ophiolite (Tibet) - Li Wang; Qing Xiong; Jian-Ping Zheng; Hong-Kun Dai; Lian-Rong Tian; Xiang Zhou (Lithos, 2024)

Potential of perennial sorghum for biogas production: Pretreatment with yeast-contained inoculants during anaerobic storage - Xiaolong Tang; Chaosheng Liao; Shufeng Zhou; Cheng Chen; Lin Li; Guangrou Lu; Xiaokang Huang; Mingjie Zhang; Chao Chen; Ping Li (Fuel, 2024)

Fibrous whey protein mediated homogeneous and soft-textured emulsion gels for elderly: Enhancement of bioaccessibility for curcumin - Zhiming Wang; Yuanyuan Deng; Yan Zhang; Xiaojun Tang; Pengfei Zhou; Ping Li; Zhihao Zhao; Zhangying Wang; Guang Liu; Mingwei Zhang (Food Chemistry, 2024)

Simulation of gross primary productivity and impact of drought in Liulin watershed of Taihang mountains over 2000–2020 - Junzhi Zhou; Ting Zhang; Jianzhu Li; Ping Feng (Ecological Modelling, 2024)

Combined inhibitory effects of microcystin-LR and microcystin-RR on growth and development in zebrafish larvae - Xiao-chun Guo; Shao-yong Lu; Sheng-nan Zhang; Ping Xie; Guang-yu Li; Zu-qin Shi; Yi-tong Zhou; Yu-meng Wang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Unraveling the critical roles of surface chemical states on anion exchange of halide perovskites - Fanghao Ye; Mengyao Tian; Xi Lan; Junzi Li; Ming Wang; Siyang Liu; Mingchao Zhu; Zhiqing Zhang; Hang Zhou; Tingchao He; Ping Xu; Guijun Li (Chemical Engineering Journal, 2024)

Experimental study on strength characteristics and constitutive behavior of frozen chloride silty clay - Yu Tang; Ping Yang; Lin Li; Zhiliang Zhou (Cold Regions Science and Technology, 2024)

Sustainable management and valorization of biomass wastes using synthetic microbial consortia - Shi-Peng Zhou; Xia Ke; Li-Qun Jin; Ya-Ping Xue; Yu-Guo Zheng (Bioresource Technology, 2024)

A global synthesis of the patterns of genetic diversity in endangered and invasive plants - Zhi-Zhou He; Gisela C. Stotz; Xiang Liu; Jia-Jia Liu; Yu-Guo Wang; Ji Yang; Lin-Feng Li; Wen-Ju Zhang; Peng Nan; Zhi-Ping Song (Biological Conservation, 2024)

CsBZR1 Family Transcription Factors in Wild and Cultural Tea Plants and Their Response to Hormone and Abiotic Stress - Jing-Wen Li; Ping Zhou; Ni Yang; Zhi-Hang Hu; Yi Chen; Wei Luo; Jie-Yu Kong; Zhi-Yuan Qin; Xing-Hui Li; Xuan Chen; Jing Zhuang (Journal of Plant Growth Regulation, 2024)

Dissection and validation of quantitative trait loci (QTLs) conferring grain size and grain weight in rice - Ping Sun; Yuanyuan Zheng; Pingbo Li; Hong Ye; Hao Zhou; Guanjun Gao; Qinglu Zhang; Yuqing He (Euphytica, 2024)

Whole genome analysis of intestinal source Bacillus and its effect on the prevention and control of hybrid snakehead (Channa maculata ♀ × Channa argus ♂) nocardiosis - Tingting Zhou; Ping Cai; Junwei Li; Zhongsheng Li; Xueming Dan; Xiande Huang; Xiaoyong Zhang (Frontiers in Marine Science, 2024)
In order to explore the antagonistic mechanism of Lysinibacillus sphaericus AEB18 against Nocardia seriolae , the whole genome of strain AEB18 was sequenced, and the effect of strain AEB18 in controlling nocardiosis of hybrid snakehead was verified in vitro and in vivo . Strain AEB18 genome was a circular DNA of 4,653,716 base pairs (bp) and GC content of 37.4%, predicting 4,529 coding genes, 108 tRNAs, 37 rRNAs, and 95 non-coding (nc)RNAs. The eggNOG (Non-supervised Orthologous Groups), GO (Gene Ontology), KEGG (Kyoto Encyclopedia of Genes and Genomes) and the CAZy (Carbohydrate-Associated Enzyme) database annotated the strain AEB18 genome to 3,965, 3,325, 2,061, and 112 genes, respectively. Furthermore, nine gene clusters, including polyketones, non-ribosomal synthetic peptides, β-lactones, terpenes, ribosomal synthetic peptides, and other secondary metabolites with bacteriostatic effect were obtained through the prediction of secondary metabolites of strain AEB18. After the addition of L. sphaericus AEB18 (1 × 10 9 CFU/g) with a mass fraction of 1% to the basal diet for 21 days, the weight gain rate and the activity of amylase in intestinal chyme of hybrid snakehead were significantly increased ( P < 0.05). In addition, hybrid snakehead fed with L. sphaericus AEB18 supplemented diets showed significantly reduced mortality rate ( P< 0.05) after N. seriolae infection, compared with the control group (mortality rate was 100%). Overall, L. sphaericus AEB18 positively affected hybrid snakeheads, promoted growth and reduced mortality rate of hybrid snakeheads with nocardiosis. Taken together, the L. sphaericus AEB18 possesses great potential as a biocontrol agent, which can be commercially developed to improve disease control in freshwater aquaculture.

Cinnamaldehyde treats largemouth bass non-lethal bacterial enteritis by regulating gut morphology, barrier, inflammation, microbiota and serum biochemistry - Ping Ouyang; Shuanghui Huang; Wenyan Wei; Jianing Wu; Yongheng Zhou; Shuhan Li; Qiunan Li; Yi Geng; Xiaoli Huang; Defang Chen; Lizi Yin (Aquaculture, 2024)

Evaluation of therapeutic benefits of botulinum toxin for foot dystonia associated with Parkinson's disease - Ping Ni; Ying-ying Xu; Lin-na Wang; Jia-qian Cao; Wei-feng Luo; Qi-lin Zhang; Xiang Li; Xu-ping Zhou; Jing Liu (Toxicon, 2024)

Promoting effect of Cu and Mn doping on the Fe/ZSM-5 catalyst for selective catalytic reduction of NO with NH3 - Yuheng Qiao; Zhenzhen Guan; Mengyan Zhang; Gan Chen; Shifeng Zhou; Hailong Liu; Jiang Wu; Ruitang Guo; Weiguo Pan; Fangqin Li; Ping He (Fuel, 2024)

Investigation on the failure mechanism of a tunnel entrance high-steep slope with ultra-large wedge blocks based on discrete element method - Huai-sheng Xu; Shao-jun Li; Ding-ping Xu; Xiu-yang Liu; Yue-lin Xia; Guan-qi Wang; Xing-dong Ma; Zheng-jun Zhou (Computers and Geotechnics, 2024)

Define of Optimal Addition Period of Osteogenic Peptide to Accelerate the Osteogenic Differentiation of Human Pluripotent Stem Cells - Yameng Song; Hongjiao Li; Zixuan Wang; Jiamin Shi; Jing Li; Lu Wang; Lingzi Liao; Shengqin Ma; Yun Zhang; Bin Liu; Yaling Yang; Ping Zhou (Tissue Engineering and Regenerative Medicine, 2024)

The Non-Singular Terminal Sliding Mode Control of Underactuated Unmanned Surface Vessels Using Biologically Inspired Neural Network - Donghao Xu; Zelin Li; Ping Xin; Xueqian Zhou (Journal of Marine Science and Engineering, 2024)
Underactuated Unmanned Surface Vessels (USVs) are widely used in civil and military fields due to their small size and high flexibility, and trajectory tracking control is a critical research area for underactuated USVs. This paper proposes a trajectory tracking control strategy using the Biologically Inspired Neural Network (BINN) for USVs to improve tracking speed and accuracy. A virtual control law is designed to obtain the required virtual velocity for trajectory tracking control, in which the velocity error is calibrated to ensure that the position error converges to zero. To observe and compensate for unknown and complex environmental disturbances such as wind, waves, and currents, a nonlinear extended state observer (NESO) is designed. Then, a controller based on Non-singular Terminal Sliding Mode (NTSM) is designed to resolve the problems of singular value and controller chattering and to improve the controller response speed. A BINN is introduced to simplify the process of differentiation, reduce the input values of the initial state, and solve the problem of thruster input saturation. Finally, the Lyapunov stability theory is utilized to analyze the stability of the proposed algorithm. The simulation results show that the proposed algorithm has a higher trajectory tracking accuracy and speed than traditional methods.

The effect of an improved passive bumper on the seismic response of the base-isolated structure: Numerical simulations and optimization design - Weijian Zhong; Binbin Li; Yanhui Liu; Ping Tan; Fulin Zhou (Soil Dynamics and Earthquake Engineering, 2024)

A new snow depth retrieval method by improved hybrid DEM differencing and coherence amplitude algorithm for PolInSAR - Haiwei Qiao; Ping Zhang; Zhen Li; Lei Huang; Shuo Gao; Chang Liu; Zhipeng Wu; Shuang Liang; Jianmin Zhou; Wei Sun; Jian Wang (Journal of Hydrology, 2024)

Multidentate anchoring strategy for synergistically modulating crystallization and stability towards efficient perovskite solar cells - Ping Hu; Wenbo Zhou; Junliang Chen; Xin Xie; Jingwei Zhu; Yuxin Zheng; Yafeng Li; Junming Li; Mingdeng Wei (Chemical Engineering Journal, 2024)

Rapid photothermal antibacterial and antifungal textiles through dynamic disulfide bond-assisted in-situ deposition of SeNPs - Leilei Wu; Xueming Bao; Zirong Li; Yuanyuan Yu; Ying Liu; Bo Xu; Man Zhou; Qiang Wang; Ping Wang (Chemical Engineering Journal, 2024)

Lipopolysaccharides from a Shiraia fruiting body-associated bacterium elicit host fungal hypocrellin A biosynthesis through nitric oxide generation - Xin Ping Li; Wen Hao Shen; Lu Lu Zhou; Qun Yan Huang; Rui Peng Cong; Li Ping Zheng; Jian Wen Wang (Carbohydrate Polymers, 2024)

The spatiotemporal variation of land surface heat fluxes in Tibetan Plateau during 2001–2022 - Na Li; Ping Zhao; Changyan Zhou (Atmospheric Research, 2024)

Vector-mediated viral exchange between crops and weedy plants - Xiao-bin Shi; Zhuo Zhang; Fan Li; Evan L. Preisser; Li-ping Huang; De-yong Zhang; Zhan-hong Zhang; Song-bai Zhang; Xu-guo Zhou; An-sheng Zhang; Hui Liu; Yuan-hua Wu; et al. (Journal of Pest Science, 2024)

The clinical trajectory of peripheral blood immune cell subsets, T-cell activation, and cytokines in septic patients - Xuan Lu; Cong-Ying Song; Ping Wang; Li Li; Li-Ying Lin; Shuai Jiang; Jia-Ning Zhou; Meng-Xiao Feng; Yun-Mei Yang; Yuan-Qiang Lu (Inflammation Research, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Effects of single and combined contamination of total petroleum hydrocarbons and heavy metals on soil microecosystems: Insights into bacterial diversity, assembly, and ecological function - Du Zhang; Qi Hu; Bing Wang; Junwen Wang; Can Li; Ping You; Rui Zhou; Weimin Zeng; Xueduan Liu; Qian Li (Chemosphere, 2023)

Environmental impact and optimization suggestions of pig manure and wastewater treatment systems from a life cycle perspective - Binbin Liu; Hao Zhou; Lanfeng Li; Jing Ai; Hang He; Junxia Yu; Ping Li; Weijun Zhang (Science of The Total Environment, 2023)

Chronic cadmium exposure triggered ferroptosis by perturbing the STEAP3-mediated glutathione redox balance linked to altered metabolomic signatures in humans - Ping Deng; Jingdian Li; Yonghui Lu; Rongrong Hao; Mindi He; Min Li; Miduo Tan; Peng Gao; Liting Wang; Huihui Hong; Jiawen Tao; Muxue Lu; et al. (Science of The Total Environment, 2023)

Microbial ecological clusters structured by environments drive maize residue decomposition at the continental scale - Meiling Zhang; Shiyu Wang; Liyu Zhang; Wentao Li; Mengmeng Cao; Shuyu Huang; Xinpeng Xu; Ping He; Wei Zhou; Laurent Philippot; Chao Ai (Science of The Total Environment, 2023)

Biotransformation of norethisterone by Rhizopus microsporus PT2906 - Xiulan Xin; Jia Liu; Shengqiao Luan; Meirong Zhou; Wenxin Wang; Yuzhuo Wu; Xiaochi Ma; Chao Wang; Ping Guo; Dawei Li (Phytochemistry Letters, 2023)

PI nanofiber membranes with pH-responsive wettability fabricated through solution blow spinning for efficient on-demand oil-water separation - Ziqiang Zhao; Jinhua Dong; Wenhao Dong; Lanlan Wang; Ping Wang; Yuqi Zhou; Haoxuan Li; Qingsheng Liu; Bingyao Deng; Dawei Li (Journal of Environmental Chemical Engineering, 2023)

Predicting genetic response to future climate change in Eucalyptus grandis by combining genomic data with climate models - Ping Wang; Cuirong Jia; David Bush; Changpin Zhou; Qijie Weng; Fagen Li; Haiwen Zhao; Hairun Zhang (Forest Ecology and Management, 2023)

Identifying priority PBT-like compounds from emerging PFAS by nontargeted analysis and machine learning models - Bao-Cang Han; Jin-Song Liu; Aaron Bizimana; Bo-Xuan Zhang; Sukhodolska Kateryna; Zhen Zhao; Li-Ping Yu; Zhong-Zeng Shen; Xiang-Zhou Meng (Environmental Pollution, 2023)

Investigation of the impact mechanisms and patterns of meteorological factors on air quality and atmospheric pollutant concentrations during extreme weather events in Zhengzhou city, Henan Province - Jinmian Ni; Yue Zhao; Bin Li; Jianhua Liu; Yinling Zhou; Ping Zhang; Jin Shao; Yanfei Chen; Jiming Jin; Chao He (Atmospheric Pollution Research, 2023)

Bamboo polysaccharides elicit hypocrellin A biosynthesis of a bambusicolous fungus Shiraia sp. S9 - Wen Hao Shen; Lu Lu Zhou; Xin Ping Li; Rui Peng Cong; Qun Yan Huang; Li Ping Zheng; Jian Wen Wang (World Journal of Microbiology and Biotechnology, 2023)

Genetic spectrums and clinical profiles of critically ill neonates with congenital auricular deformity in the China Neonatal Genomes Project - Feifan Xiao; Bingbing Wu; Chenbin Dong; Guoqiang Cheng; Yun Cao; Laishuan Wang; Xinran Dong; Yulan Lu; Lin Yang; Liping Chen; Long Li; Xinnian Pan; et al. (Human Genetics, 2023)

White matter alterations in mild cognitive impairment revealed by meta-analysis of diffusion tensor imaging using tract-based spatial statistics - Longfei Li; Wei Yang; Yu Wan; Hailong Shen; Ting Wang; Liangliang Ping; Chuanxin Liu; Min Chen; Hao Yu; Shushu Jin; Yuqi Cheng; Xiufeng Xu; et al. (Brain Imaging and Behavior, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

SIRT3-dependent mitochondrial redox homeostasis mitigates CHK1 inhibition combined with gemcitabine treatment induced cardiotoxicity in hiPSC-CMs and mice - Jia-Wen Chen; Tian-Kai Shan; Tian-Wen Wei; Qi-Qi Jiang; Chong Du; Ling-Feng Gu; Tong-Tong Yang; Liu-Hua Zhou; Si-Bo Wang; Yu-Lin Bao; Hao Wang; Yong Ji; et al. (Archives of Toxicology, 2023)

Role of APR3 in cancer: apoptosis, autophagy, oxidative stress, and cancer therapy - Ping Zhang; Chaoting Zhou; Qiangan Jing; Yan Gao; Lei Yang; Yanchun Li; Jing Du; Xiangmin Tong; Ying Wang (Apoptosis, 2023)

Cytotoxic phenyl polyketides from Hypericum curvisepalum N. Robson - Qiu-Ying He; Hong Zeng; Qiu-Lan Zhang; Guan-Fang Qin; He-Bin Wang; Li-Ping Teng; Zhong-Bo Zhou (Natural Product Research, 2023)

Recent advances in tea seeds (Camellia Sinensis (L.) O. Kuntze): Active ingredients, health effects, and potential applications - Su Zhou; Zhiying Li; Haizhao Song; Hao Hu; Shicheng Ma; Yike Tao; Zhilong Hao; Xinyu Feng; Yani Pan; Shuying Gong; Fangyuan Fan; Ping Chen; et al. (Trends in Food Science & Technology, 2023)

Environmental cadmium exposure facilitates mammary tumorigenesis via reprogramming gut microbiota-mediated glutamine metabolism in MMTV-Erbb2 mice - Yang Yue; Huadong Zhang; Ping Deng; Miduo Tan; Chengzhi Chen; Bo Tang; Jingdian Li; Fengqiong Chen; Qi Zhao; Ling Li; Rongrong Hao; Hui Wang; et al. (Science of The Total Environment, 2023)

Extraction and characterization of anti-virus anthraquinones from Nicotiana tabacum-derived Aspergillus oryzae YNCA1220 - Feng-Xian Yang; Yue-Yu Ma; Yu-Ping Wu; Gao-Kun Zhao; Yong-Ping Li; Zhen-Jie Li; Xue-Mei Li; Yin-Ke Li; Wei-Guang Wang; Min Zhou; Guang-Hui Kong; Qiu-Fen Hu (Pesticide Biochemistry and Physiology, 2023)

Biodegradation of polyvinyl chloride, polystyrene, and polylactic acid microplastics in Tenebrio molitor larvae: Physiological responses - Bo-Yu Peng; Ying Sun; Ping Li; Siran Yu; Yazhou Xu; Jiabin Chen; Xuefei Zhou; Wei-Min Wu; Yalei Zhang (Journal of Environmental Management, 2023)

Seismic design and experimental testing of precast tolerance concrete shear wall subject to cyclic load - Peng Mi; Ping Tan; Yiming Li; Zhibin Liu; Mengxiong Tang; Fulin Zhou (Engineering Structures, 2023)

The synergy between temporal and spatial effects of human activities on CO2 emissions in Chinese cities - Zhiwen Li; Jiandong Chen; Ping Wang; Ziqi Zhou; Xingyu Chen (Environmental Impact Assessment Review, 2023)

Laccase-triggered one-step fabrication of positively charged phenolic acid-amine networks for nanofiltration - Ping Fu; Di Zhou; Wan-Long Li; Wan-Ting Lin; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2023)

Uniform lithium deposition regulated by lithiophilic Mo3N2/MoN heterojunction nanobelts interlayer for stable lithium metal batteries - Xiaojuan Zhang; Liang Zhou; Kunpeng Hu; Dandan Gao; Shuo Tang; Li He; Yuanfu Chen; Ping Zhang; Zhigang Zhang (Chemical Engineering Journal, 2023)

Erratum to: Compound muscle action potential (CMAP) scan examination of paretic and contralateral muscles reveals motor unit alterations after stroke - Maoqi Chen; Zhiyuan Lu; Xiaoyan Li; Ya Zong; Qing Xie; Sheng Li; Ping Zhou (Science China Life Sciences, 2023)

Compound muscle action potential (CMAP) scan examination of paretic and contralateral muscles reveals motor unit alterations after stroke - Maoqi Chen; Zhiyuan Lu; Xiaoyan Li; Ya Zong; Qing Xie; Sheng Li; Ping Zhou (Science China Life Sciences, 2023)
This study presents a novel compound muscle action potential (CMAP) examination of motor unit changes in paretic muscle post stroke. CMAP scan of the first dorsal interosseous (FDI) muscle was performed bilaterally in 16 chronic stroke subjects. Various parameters were derived from the CMAP scan to examine paretic muscle changes, including CMAP amplitude, D50, step index (STEPIX) and amplitude index (AMPIX). A significant decrease in CMAP amplitude and STEPIX was observed in paretic muscles compared with contralateral muscles (CMAP amplitude: paretic (9.0±0.5) mV, contralateral (11.3±0.9) mV, P =0.024; STEPIX: paretic 101.2±7.6, contralateral 121.9±6.5, P =0.020). No significant difference in D50 and AMPIX was observed between the paretic and contralateral sides (P>0.05). The findings revealed complex paretic muscle changes including motor unit degeneration, muscle fiber denervation, reinnervation and atrophy, providing useful insights to help understand neuromuscular mechanisms associated with weakness and other functional deterioration post stroke. The CMAP scan experimental protocols and the applied processing methods are noninvasive, convenient, and automated, offering practical benefits for clinical application.

Arbuscular mycorrhiza changes plant facilitation patterns and increases resource use efficiency in intercropped annual plants - Shuang-Guo Zhu; Hai-Xia Duan; Hong-Yan Tao; Li Zhu; Rui Zhou; Yu-Miao Yang; Xiao-Lin Zhang; Wen-Ying Wang; Hao Zhu; Wei Zhang; Ren-Qing Wang; Xiu-Ping Tao; et al. (Applied Soil Ecology, 2023)

Improving soil phosphorus availability in saline areas by marine bacterium Bacillus paramycoides - Zhe Li; Zhe Liu; Ying Wang; Xiaofang Wang; Ping Liu; Mingyue Han; Weizhi Zhou (Environmental Science and Pollution Research, 2023)

Regulation of microbial metabolism on the formation of characteristic flavor and quality formation in the traditional fish sauce during fermentation: a review - Jiarun Han; Tao Kong; Qi Wang; Jialan Jiang; Qingqing Zhou; Ping Li; Beiwei Zhu; Qing Gu (Critical Reviews in Food Science and Nutrition, 2023)

Paternal cadmium exposure induces glucolipid metabolic reprogramming in offspring mice via PPAR signaling pathway - Ling Zeng; Jinzhao Zhou; Yanwei Zhang; Xiaofei Wang; Yamin Li; Jieping Song; JingFan Shao; Ping Su (Chemosphere, 2023)

Bi0·5Na0·5TiO3/ZnO Z-scheme heterojunction for piezo-photocatalytic water remediation: Mechanical energy harvesting and energy band configuration - Peng Wang; Wanqian Cai; Fangyuan Yu; Ping Zhou; Mei Lin; Cong Lin; Tengfei Lin; Min Gao; Chunlin Zhao; Xiangqi Li; Xiao Wu (Chemosphere, 2023)

Effects of interspecific interactions on soil carbon emission and efficiency in the semiarid intercropping systems - Wei Wang; Meng-Ying Li; Rui Zhou; Shuang-Guo Zhu; Hong-Yan Tao; Aziz Khan; Aimee Grace Uzamurera; Bao-Zhong Wang; Jun-Ming Jin; Yue Ma; Wen-Bo Li; Xiu-Ping Tao; et al. (Soil and Tillage Research, 2023)

Fabrication of multi-morphological Bi2O2(OH)NO3-BiVO4 Z-Scheme heterojunction for enhanced photocatalytic antibiotic removal performance - Jinhai Li; Chenyu Wang; Jianhai Zhou; Zhang Ping; Guopei Huang; Yuanhui Wu; Shuxing Luo; Dongmei Bao; Zhu Wen; Pili Lu (Journal of Environmental Chemical Engineering, 2023)

Fermentation of Rosa roxburghii Tratt by Limosilactobacillus fermentum NCU001464: Physicochemical characteristics and biological activity - Hai-Li Zhou; Fei Peng; Jia-Xin Lin; Li-Ping Hu; Mingyong Xie; Tao Xiong (Food Bioscience, 2023)

Leaf senescence, nitrogen remobilization, and productivity of maize in two semiarid intercropping systems - Wei Wang; Meng-Ying Li; Rui Zhou; Fei Mo; Aziz Khan; Asfa Batool; Wei Zhang; Jun-Sheng Lu; Ying Zhu; Bao-Zhong Wang; Yu-Miao Yang; Jing Wang; et al. (European Journal of Agronomy, 2023)

Synergization of an endoplasmic reticulum-targeted iridium(III) photosensitizer with PD-L1 inhibitor for oral squamous cell carcinoma immunotherapy - Jia-Ying Zhou; Qing-Hua Shen; Xiao-Jing Hong; Wu-Ya Zhang; Qiao Su; Wu-Guo Li; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2023)

Proteomic profile of the germinating seeds reveals enhanced seedling growth in Arabidopsis rpp1a mutant - Lu Zheng; Peijun Zhou; Yilin Pan; Bingjuan Li; Renfang Shen; Ping Lan (Plant Molecular Biology, 2023)

Prevalence and genomic analysis of t203-like G9 (G9-VI) rotaviruses circulating in children with gastroenteritis in Beijing, China - Hui-Jin Dong; Li-Ying Liu; Li-Ping Jia; Lin-Qing Zhao; Feng-Hua Jin; Lin Zhou; Yuan Qian (Archives of Virology, 2023)
Our previous surveillance revealed that t203-like G9 (tentatively designated subtype G9-VI) rotaviruses re-emerged in 2010 in Beijing and rapidly prevailed over the G9-III subtype (the most common G9 subtype globally) and previously predominant G genotypes over the following two years. G9-VI belongs to the VP7 evolutionary lineage VI, which includes unusual and sporadic human rotaviruses from China (t203) and Japan. To obtain insight into the epidemiology, evolution, and transmission advantages of G9-VI rotavirus, we performed follow-up surveillance (2014-2017) and whole-genome analysis of 12 representative G9 strains. The results showed that the G9 genotype was predominant (77.4%), with a marked increase in prevalence (previously 43.5%). Within the G9 genotype, subtype G9-VI accounted for the majority (98.3%) of cases. The most prevalent P-genotype was P[8] (93.7%), within which subtype P[8]b was rare (0.7%). Phylogenetically, the G9-VI subtype strains in this study clustered closely with contemporary emerging human rotaviruses from many other countries in VP7 lineage VI, indicating that this subtype is capable of spreading globally. These currently emerging G9-VI rotaviruses formed a distinct monophyletic subcluster when compared to early G9-VI rotaviruses. Furthermore, four specific amino acid substitutions and synonymous codon substitutions were observed in the VP7 genes between the current G9-VI and globally common G9-III rotaviruses. The remaining nine genes of all of the analyzed representative G9 strains, whether G9-VI or G9-III, combined with the P[8]a, P[8]b, or P[6] genotype and exhibited the same Wa-like backbone constellation.

Potentially migrating and residual components of biochar: Effects on phosphorus adsorption performance and storage capacity of black soil - Ping Xue; Renjie Hou; Qiang Fu; Tianxiao Li; Jinwu Wang; Wenqi Zhou; Weizheng Shen; Zhongbin Su; Yijia Wang (Chemosphere, 2023)

Functional evaluation of CYP2C19 and CYP3A4 gene polymorphism on ibuprofen metabolism - Ling-Jing Yuan; Xiang-Yu Li; Jin-Huan Ni; Jing Wang; Xiao-Yu Xu; Jian-Chao Luo; Qi Zhou; Guo-Xin Hu; Jian-Ping Cai; Jian-Chang Qian (Toxicology and Applied Pharmacology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

A novel global snow depth retrieval method considering snow metamorphism and forest influence - Shuo Gao; Zhen Li; Ping Zhang; Quan Chen; Lei Huang; Jianmin Zhou; Changjun Zhao; Haiwei Qiao; Zhaojun Zheng (Remote Sensing of Environment, 2023)

Comprehensive understanding of tetracycline hydrochloride adsorption mechanism onto biochar-based gel pellets based on the combination of characterization-based and approximate site energy distribution methods - Bai-Qin Zhou; Qian-Qian Sang; Yu-Jun Wang; Hui Huang; Fang-Jun Wang; Rui-Chun Yang; Yuan-Tian Zhao; Zi-Jie Xiao; Chun-Yue Zhang; Hui-Ping Li (Journal of Cleaner Production, 2023)

Numeric and nonnumeric information input to predict adsorption amount, capacity and kinetics of tetracyclines by biochar via machine learning - Bai-Qin Zhou; Rui-Chun Yang; Hui-Ping LI; Yu-Jun Wang; Chun-Yue Zhang; Zi-Jie Xiao; Zhong-Qi He; Wei-Hai Pang (Chemical Engineering Journal, 2023)

Inhibition of multiple uptake transporters in cardiomyocytes/mitochondria alleviates doxorubicin-induced cardiotoxicity - Yaodong Yi; Hengbin Zhang; Mingyang Chen; Binxin Chen; Yingchun Chen; Ping Li; Hui Zhou; Zhiyuan Ma; Huidi Jiang (Chemico-Biological Interactions, 2023)

Genome-Wide Identification of MabHLH Transcription Factors Family Response to Magnesium Deficiency Stress in Banana (Musa paradisiaca AA) - Ping Li; Xinping Li; Shihan Zhou; Haiyan Hu (Tropical Plant Biology, 2023)

Orally Induced High Serum Level of Trimethylamine N-oxide Worsened Glial Reaction and Neuroinflammation on MPTP-Induced Acute Parkinson’s Disease Model Mice - Chen-Meng Qiao; Wei Quan; Yu Zhou; Gu-Yu Niu; Hui Hong; Jian Wu; Li-Ping Zhao; Ting Li; Chun Cui; Wei-Jiang Zhao; Yan-Qin Shen (Molecular Neurobiology, 2023)

Associations between high-altitude adaptation and risk of cardiovascular diseases: a bidirectional Mendelian randomization study - Yuqing Jiang; Jie Ping; Hao Lu; Haoxiang Zhang; Mengyu Liu; Yuanfeng Li; Gangqiao Zhou (Molecular Genetics and Genomics, 2023)

Study of advanced dewatering and its influence on tunnel in water rich and sandy dolomite stratum - Yifan Jiang; Jinyi Li; Feicong Zhou; Qi Yongli; Hua Huang; Xiaobing Li; Zhijie Wang; Ping Zhou (Bulletin of Engineering Geology and the Environment, 2023)

Comparative research on the precursory characteristics of critical slowing down before the failure of raw coal and briquettes - Erhui Zhang; Baokun Zhou; Ping Li (Bulletin of Engineering Geology and the Environment, 2023)

Isoptericola croceus sp. nov., a novel actinobacterium isolated from saline–alkali soil - Yu-Ting OuYang; Ai-Ping Lv; Lan Liu; Ting-Ting Li; Yi Zhou; Ting-Ting She; Li-Xiang Cao; Jian-Yu Jiao; Shuang Wang; Wen-Jun Li (Antonie van Leeuwenhoek, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Metamorphic P–T evolution of the pelitic granulites from the Helanshan in the North China Craton revealed by phase equilibrium modeling and garnet trace elements: Implications for Paleoproterozoic collisional orogenesis - Xiao-Fei Xu; Long-Long Gou; Yun-Peng Dong; Cheng-Li Zhang; Xiao-Ping Long; Yu-Hang Zhao; Feng Zhou; Zhi-Bo Tian (Precambrian Research, 2023)

Liver-cell protective pyridones from the fungi Tolypocladium album dws120 - Xiao-Qian Wu; Jing Li; Xi Zhou; Jing Wang; Yu-Fen Tan; Ji-Song Mo; Shao Liu; Kang-Ping Xu; Gui-Shan Tan; Wei Zhang; Wen-Xuan Wang (Phytochemistry, 2023)

Melatonin-induced plant adaptation to cadmium stress involves enhanced phytochelatin synthesis and nutrient homeostasis in Solanum lycopersicum L. - Qufan Xing; Md. Kamrul Hasan; Zhichao Li; Ting Yang; Weiduo Jin; Zhenyu Qi; Ping Yang; Guanghui Wang; Golam Jalal Ahammed; Jie Zhou (Journal of Hazardous Materials, 2023)

Construction of PES mixed matrix membranes incorporating ZnFe2O4 @MXene composites with high permeability and antifouling performance - Ping Zhou; Ting Wang; Chun-Hui Du; Guo-qin Wang; Li-guang Wu; Xiao-jia Jiang; Hai-Chang Guo (Journal of Environmental Chemical Engineering, 2023)

The health risk of acetochlor metabolite CMEPA is associated with lipid accumulation induced liver injury - Wei-Guo Wang; Mu-Yao Li; Lin Diao; Cheng Zhang; Li-Ming Tao; Wei-Xing Zhou; Wen-Ping Xu; Yang Zhang (Environmental Pollution, 2023)

Transcriptomics integrated with metabolomics unravels the interweaving of inflammatory response and 1-stearoyl-2-arachidonoyl-sn-glycerol metabolic disorder in chronic cadmium exposure-induced hepatotoxicity - Rongrong Hao; Heng Xiao; Hui Wang; Ping Deng; Yang Yue; Jingdian Li; Yan Luo; Li Tian; Jia Xie; Mengyan Chen; Zhou Zhou; Fengqiong Chen; et al. (Environmental Toxicology and Pharmacology, 2023)

Irisin Attenuates Apoptosis Following Ischemia–Reperfusion Injury Through Improved Mitochondria Dynamics and ROS Suppression Mediated Through the PI3K/Akt/mTOR Axis - Ji-fei Liu; Gang Su; Li-xia Chen; Juan-ping Zhou; Juan Gao; Jia-jia Zhang; Qiong-hui Wu; Wei Chen; De-yi Chen; Zhen-chang Zhang (Molecular Neurobiology, 2023)

TFEB: a double-edged sword for tumor metastasis - Jun-Hu Hu; Shou-Ye Li; Li-Hua Yu; Zhen-Rong Guan; Ya-Ping Jiang; Die Hu; Hao-Jie Wang; Li-Ping Zhao; Zhao-Huang Zhou; Ya-Xin Yan; Tian Xie; Zhi-Hui Huang; et al. (Journal of Molecular Medicine, 2023)

Laboratory characterization of soft clay mixed with EPS, lime, fly ash, and sodium silicate - Ping Jiang; Wenqian Zheng; Lin Zhou; Na Li; Wei Wang (Bulletin of Engineering Geology and the Environment, 2023)

Straw return counteracts the negative effects of warming on microbial community and soil multifunctionality - Gong Wu; Jun Ling; De-Qiang Zhao; Zi-Xi Liu; Yi-Ping Xu; Yakov Kuzyakov; Karina Marsden; Yuan Wen; Shun-Li Zhou (Agriculture, Ecosystems & Environment, 2023)

Effects and mechanisms of natural products on Alzheimer’s disease - Zhijun Yang; Dan-Dan Zhou; Si-Yu Huang; Ai-Ping Fang; Hua-Bin Li; Hui-Lian Zhu (Critical Reviews in Food Science and Nutrition, 2023)

Linking DOM characteristics to microbial community: The potential role of DOM mineralization for arsenic release in shallow groundwater - Yanhong Wang; Xuege Tian; Tenglong Song; Zhou Jiang; Guanglong Zhang; Chen He; Ping Li (Journal of Hazardous Materials, 2023)

Heavy metals immobilization of ternary geopolymer based on nickel slag, lithium slag and metakaolin - Jinyuan Fan; Jiahao Yan; Mengya Zhou; Yuan Xu; Yuwei Lu; Ping Duan; Yingcan Zhu; Zuhua Zhang; Wengui Li; Aiguo Wang; Daosheng Sun (Journal of Hazardous Materials, 2023)

A photothermal cellulose-based material for rapid anti-bacteria and HCHO removal via sequential formation of MnO2 coatings and amine-quinone networks - Xueming Bao; Leilei Wu; Yuanyuan Yu; Bo Xu; Li Cui; Man Zhou; Qiang Wang; Ping Wang (Chemical Engineering Journal, 2023)

Baicalein sensitizes triple negative breast cancer MDA-MB-231 cells to doxorubicin via autophagy-mediated down-regulation of CDK1 - Fang Hua; Yi-Yi Xiao; Xin-Hui Qu; Shan-Shan Li; Kun Zhang; Chao Zhou; Jian-Le He; Ye Zhu; Yu-Ying Wan; Li-Ping Jiang; Fang-Fang Tou; Xiao-Jian Han (Molecular and Cellular Biochemistry, 2023)

Inactivation of epithelial sodium ion channel molecules serves as effective diagnostic biomarkers in clear cell renal cell carcinoma - Qian Zheng; Yifang Wang; Ran Zhao; Peipei Han; Jun Zhao; Limei Li; Xiaohui Zhou; Ping Li; Yingxi Mo; Xinli Pan; Wenqi Luo; Xiaoying Zhou (Genes & Genomics, 2023)

The spatial distribution, health risk, and cytotoxicity of metal(loid)s in contaminated field soils: The role of Cd in human gastric cells damage - Jiao-Yang Ma; Wei-Yu Li; Zi-Yue Yang; Jin-Zhou Su; Li Li; Yi-Rong Deng; Yun-Fei Tuo; You-Ya Niu; Ping Xiang (Science of The Total Environment, 2023)

Neuroprotective methylsuccinic acid and enoic acid derivatives from the fungus Xylaria longipes - Jing Li; Yu-Fen Tan; Si-Qian Zhou; Shao Liu; Wen-Xuan Wang; Yue-Ping Jiang; Hong-Ping Long; Ji-Kai Liu (Phytochemistry, 2023)

Transcriptomic and physiological analysis of the effect of octanoic acid on Meloidogyne incognita - Jian-Yu Wang; Qiu-Yue Li; Li Ren; Cheng Guo; Jian-Ping Qu; Zheng Gao; Hui-Fang Wang; Qian Zhang; Bo Zhou (Pesticide Biochemistry and Physiology, 2023)

Meta-analysis reveals cyanotoxins risk across African inland waters - Xu Zhao; Ying Liu; Yu-Ming Guo; Chi Xu; Liang Chen; Geoffrey A. Codd; Jun Chen; Ying Wang; Pu-Ze Wang; Li-Wei Yang; Long Zhou; Yan Li; et al. (Journal of Hazardous Materials, 2023)

Salinity variations of the inner Yangtze Sea during the Ordovician-Silurian transition and its influences on marginal marine euxinia - Guangyao Cao; Yu Liu; Chao Li; Ping'an Peng; Mingcai Hou; Gary G. Lash; Xiaolin Zhou; Yuanchun Li; Ying Song (Global and Planetary Change, 2023)

Confined and mediated intercalation of nanoparticles in graphene oxide membrane to fine-tune desalination performance - Siyu Zhou; Kecheng Guan; Zheng Wang; Qiangqiang Song; Zhan Li; Ping Xu; Luyao Deng; Shang Xiang; Hideto Matsuyama (Chemical Engineering Journal, 2023)

Ice monitoring of aluminum conductor steel-reinforced cables using guided waves - Yuqi Wu; Ping Lu; Wensong Zhou; Hui Li (Cold Regions Science and Technology, 2023)

Effect of co-inoculation of Lactobacillus plantarum and Lentilactobacillus buchneri on aerobic stability and microbial community composition of perennial sorghum silage - Maoya Li; Shufeng Zhou; Xiaolong Tang; Chaosheng Liao; Ping Li; Yixiao Xie; Qiming Cheng; Chao Chen (Biomass and Bioenergy, 2023)

Stellate ganglion block suppresses hippocampal ferroptosis to attenuate cerebral ischemia-reperfusion injury via the Hippo pathway - Chunwang Zhou; Mengyuan Li; Yingxin Chu; Liyan Zheng; Shubo Zhang; Xiujiang Gao; Ping Gao (Metabolic Brain Disease, 2023)

Vancomycin Pretreatment on MPTP-Induced Parkinson’s Disease Mice Exerts Neuroprotection by Suppressing Inflammation Both in Brain and Gut - Chun Cui; Hui Hong; Yun Shi; Yu Zhou; Chen-Meng Qiao; Wei-Jiang Zhao; Li-Ping Zhao; Jian Wu; Wei Quan; Gu-Yu Niu; Yi-Bo Wu; Chao-Sheng Li; et al. (Journal of Neuroimmune Pharmacology, 2023)

An Explainable Machine-Learning Model to Analyze the Effects of a PCSK9 Inhibitor on Thrombolysis in STEMI Patients - Pengyu Zhao; Jia Zhou; Chang Liu; Zhaoying Li; Ping He; Chunjie Li; Jia Zhao; Yonghong Hou (Journal of Medical and Biological Engineering, 2023)

Fermented foods and metabolic outcomes in diabetes and prediabetes: A systematic review and meta-analysis of randomized controlled trials - Xiao-Feng Zhang; Yue Qi; Yong-Ping Zhang; Jin-Lan Deng; Xiao-Li Chen; Ruo-Nan Li; Qi-Lun Zhou; Jian-Ming Fan (Critical Reviews in Food Science and Nutrition, 2023)

Study on the mechanism of tunnel catastrophe in Xigeda formation considering the interbed effect - Ping Zhou; Feicong Zhou; Yifan Jiang; Jinyi Li; Jiayong Lin; Ming Lin; Zhijie Wang (Tunnelling and Underground Space Technology, 2023)

Distribution characteristics and environmental effects of non-methane hydrocarbons in the East China Sea - Wen-Zhu Qiao; Ying-Cui Wu; Ping Wang; Jian Wang; Li-Min Zhou; Si-Tong Li; Hong-Hai Zhang (Continental Shelf Research, 2023)

Synthesis and biological evaluation of esculetin derivatives as potential anti-HBV agents - Zhen Ye; Tong-Shi-Yao Zhao; Shan-Bin Li; Xian-Li Zhou; Qin Luo; Jiang-Ke Qin; Cheng-Qin Liang; Ping Wang; Guang-Bo Ge (Medicinal Chemistry Research, 2023)

Association between the NEP rs701109 polymorphism and the clinical efficacy and safety of sacubitril/valsartan in Chinese patients with heart failure - Hong-Yu Luo; Li-Chen Gao; Hui-Zhi Long; Zi-Wei Zhou; Shuo-Guo Xu; Feng-Jiao Li; Hong-Li Li; Yan Cheng; Cai-Xia Li; Xing-Yu Peng; Liang Li; Ran Chen; et al. (European Journal of Clinical Pharmacology, 2023)

Experimental study on the microseismic response characteristics of coal and gas outbursts - Erhui Zhang; Baokun Zhou; Lei Yang; Changfeng Li; Ping Li (Process Safety and Environmental Protection, 2023)

Reliable spectroscopic identification of minerals associated with serpentinization: Relevance to Mars exploration - Wen-Ping Liu; Wei Yin; Bin-Long Ye; Tian-Lei Zhao; Qi-Zhi Yao; Yi-Liang Li; Sheng-Quan Fu; Gen-Tao Zhou (Icarus, 2023)

La2Ti2O7 nanosheets modified by Pt quantum dots for efficient NO removal avoiding NO2 secondary pollutant - Li Lv; Hong-Dan Yang; Qi-Wen Chen; Huiqing Fan; Jian-Ping Zhou (Environmental Research, 2023)

Single-base resolution mapping of 2′-O-methylation sites by an exoribonuclease-enriched chemical method - Ping Zhang; Junhong Huang; Wujian Zheng; Lifan Chen; Shurong Liu; Anrui Liu; Jiayi Ye; Jie Zhou; Zhirong Chen; Qiaojuan Huang; Shun Liu; Keren Zhou; et al. (Science China Life Sciences, 2023)

Correction to: Geographical, Sex, Age, and Seasonal Differences in Serum Manganese Status Among Chinese Adults with Hypertension - Hong Chen; Zhixin Cui; Wenhai Lu; Ping Wang; Jia Wang; Ziyi Zhou; Nan Zhang; Zhuo Wang; Tengfei Lin; Yun Song; Lishun Liu; Xiao Huang; et al. (Biological Trace Element Research, 2023)

Molybdenum fertilizer improved antioxidant capacity of Chinese Merino sheep under compound contamination - Yuanfeng Li; Ping Zhou; Xiaoyun Shen; Kui Zhao (Biological Trace Element Research, 2023)

Abamectin causes toxicity to the carp respiratory system by triggering oxidative stress, inflammation, and apoptosis and inhibiting autophagy - Huimiao Feng; Ping Zhou; Feixue Liu; Wei Zhang; Haitao Yang; Xueqing Li; Jingquan Dong (Environmental Science and Pollution Research, 2023)

Environmental regulation and corporate financialization: insight from Blue Sky Protection Campaign in China - Zhengqing Zhou; Li Xu; Ping Guo; Hongshan Ai (Environmental Science and Pollution Research, 2023)

Benzimidazole fungicide biotransformation by comammox Nitrospira bacteria: Transformation pathways and associated proteomic responses - Ping Han; Ana B. Rios-Miguel; Xiufeng Tang; Yaochun Yu; Li-Jun Zhou; Lijun Hou; Min Liu; Dongyao Sun; Mike S.M. Jetten; Cornelia U. Welte; Yujie Men; Sebastian Lücker (Journal of Hazardous Materials, 2023)

Deciphering the microbial community tolerance mechanism and alteration of antibiotic resistance genes during chloramphenicol wastewater treatment - Jia Zhou; Yan Chen; Wan-Xia Li; Jian-Hang Qu; Tian Chen; Yi-Ping Wang; Ning-Yu Geng (International Biodeterioration & Biodegradation, 2023)

Development of a Nafion-MWCNTs and in-situ generated Au nanopopcorns dual-amplification electrochemical aptasensor for ultrasensitive detection of OTA - Yujiao Hou; Nan Long; Qingbin Xu; Ying Li; Pengyue Song; Minghan Yang; Jiabo Wang; Lidong Zhou; Ping Sheng; Weijun Kong (Food Chemistry, 2023)

Liquid water determination by airborne millimeter cloud radar and in-situ size distribution measurements - Dongfei Zuo; Dantong Liu; Delong Zhao; Ling Yang; Yichen Chen; Wei Zhou; Mengyu Huang; Hui He; Ping Tian; Yuanmou Du; Wei Xiao; Ruijie Li; et al. (Atmospheric Research, 2023)

Correction to: Protective Effects of Chinese Herbal Medicine Rhizoma drynariae in Rats After Traumatic Brain Injury and Identification of Active Compound - Wenzhu Wang; Haigang Li; Jintao Yu; Michael Hong; Jing Zhou; Lin Zhu; Yang Wang; Min Luo; Zian Xia; Zeng-Jin Yang; Tao Tang; Ping Ren; et al. (Molecular Neurobiology, 2023)

Aerobic glycolysis in colon cancer is repressed by naringin via the HIF1A pathway - Guangtao Pan; Ping Zhang; Aiying Chen; Yu Deng; Zhen Zhang; Han Lu; Aoxun Zhu; Cong Zhou; Yanran Wu; Sen Li (Journal of Zhejiang University-SCIENCE B, 2023)

Erratum to: Rigid block characteristics on subaerial landslide-tsunamis using a 3D coupled Eulerian-Lagrangian model - Yi-ding Bao; Jian-ping Chen; Li-jun Su; Xin Zhou; Cheng-shan Yin (Journal of Mountain Science, 2023)

Gas in place and its controlling factors of deep shale of the Wufeng-Longmaxi Formations in the Dingshan area, Sichuan Basin - Ping Gao; Xianming Xiao; Dongfeng Hu; Ruobing Liu; Fei Li; Qin Zhou; Yidong Cai; Tao Yuan; Guangming Meng (Frontiers of Earth Science, 2023)

High biocompatible nitrogen and sulfur Co-doped carbon dots for Hg(II) detection and their long-term biological stability in living cells - Waheed Ullah Khan; Liying Qin; Lixin Chen; Wasim Ullah Khan; Shah Zeb; Asaf Khan; Shengzhen Li; Salim Ullah Khan; Sajid Kamal; Ping Zhou (Analytica Chimica Acta, 2023)

Transcriptomic analysis provides new insights into the secondary follicle growth in spotted scat (Scatophagus argus) - Mou-Yan Jiang; Yi-Fan Zhou; Hao Liu; You-Xing Peng; Yuan-Qing Huang; Si-Ping Deng; Yang Huang; Gang Shi; Chun-Hua Zhu; Guang-Li Li; Dong-Neng Jiang (Frontiers in Marine Science, 2023)
Spotted scat ( Scatophagus argus ) is an important mariculture fish that is of great economic significance in East and Southeast Asia. To date, there are no studies on ovary development and regulation in S. argus . Herein, the ovary transcriptome profiles of S. argus at different stages were constructed, and the genes and pathways potentially involved in secondary follicle growth were identified. A total of 25,426 genes were detected by sequencing the mRNAs from the ovary libraries at stage III (n=3) and IV (n=3). Notably, 2950 and 716 genes were up-regulated and down-regulated in the stage IV ovary, respectively, compared to the stage III ovary. The differentially expressed genes (DEGs) were found to be mostly involved in regulating steroidogenesis, vitellogenesis, lipid metabolism, and meiosis. Up-regulation of steroid hormone synthesis pathway genes ( fshr , cyp17a1 , and foxl2 ) and insulin-like growth factor pathway genes ( igf1r , ifg2r , igfbp1 , igfbp3 , and igfbp7 ) in the ovary at stage IV was possibly the reason for the increased serum estrogen. Moreover, ppara , ppard , fabp3 , and lpl were up-regulated in the stage IV ovary and were potentially involved in the lipid droplet formation in the oocyte. Many DEGs were involved in the cellular cycle, meiosis, and cAMP or cGMP synthesis and hydrolysis, indicating that meiosis was restarted at stage IV ovary. In addition, numerous TGF-beta signal pathway genes were up-regulated in the stage IV ovary. This ovary transcript dataset forms a baseline for investigating functional genes associated with oogenesis in S. argus .

Performance and mechanism of GO removal by gypsum from aqueous solution - Ping Jiang; Guanzhong Zhou; Cuihong Li; Yanfei Yu; Lin Zhou; Haibo Kang (Environmental Science and Pollution Research, 2023)

Long-term cadmium exposure impairs cognitive function by activating lnc-Gm10532/m6A/FIS1 axis-mediated mitochondrial fission and dysfunction - Ping Deng; Huadong Zhang; Liting Wang; Sheng Jie; Qi Zhao; Fengqiong Chen; Yang Yue; Hui Wang; Li Tian; Jia Xie; Mengyan Chen; Yan Luo; et al. (Science of The Total Environment, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Effect of phenol formaldehyde-associated microplastics on soil microbial community, assembly, and functioning - Hu Li; Qiu-Ping Luo; Sha Zhao; Yan-Yan Zhou; Fu-Yi Huang; Xiao-Ru Yang; Jian-Qiang Su (Journal of Hazardous Materials, 2023)

Research on the hydrothermal regeneration of powdered activated coke in wastewater treatment - Zhanyao Li; Guifang Chen; Huiru Ma; Fuyu Huang; Hao Xu; Liqiang Zhang; Xueliang Yuan; Xinyan Zhang; Shouyan Chen; Ping Zhou (Journal of Environmental Chemical Engineering, 2023)

Microporous three dimensional ordered zeolite-templated carbon for efficient removal of VOCs: Experimental study and molecular dynamics simulation - Hantian Li; Xishan Zhou; Tao Wang; Jiawei Wang; Yongsheng Zhang; Wei-Ping Pan (Fuel, 2023)

Aggregation-induced emission luminogens-encoded microspheres preparation and flow-through immunoaffinity chromatographic assay development for microcystin-LR analysis - Peng Zhai; Chen Liu; Gang Feng; Yuanhao Cao; Lei Xiang; Keshi Zhou; Ping Guo; Jianqing Li; Wenxiao Jiang (Food Chemistry, 2023)

Effect of Tribute citrus essential oil nanoemulsion-loaded gelatin on the gel behavior and gelation surface morphologies - Guoqiang Li; Qingqing Zhou; Shuxun Liu; Cheng Qian; Jiarun Han; Tao Zhou; Ping Li; Qing Gu (Food Bioscience, 2023)

Phospholipase A2 induces acute kidney injury by complement mediated mitochondrial apoptosis via TNF-α/NF-κB signaling pathway - Xin Tang; Tiantian Wei; Mingjing Guan; Peiyun Li; Yajun Pu; Lixin Cheng; Zhifeng Zhou; Ping Fu; Ling Zhang (Food and Chemical Toxicology, 2023)

Caenorhabditis elegans: a nature present for advanced food science - Yonglu Li; Yadi Wang; Ping Li; Qingqing Zhou; Xiaodong Zheng; Qing Gu (Current Opinion in Food Science, 2023)

Efficient fabrication of desert beetle-inspired micro/nano-structures on polypropylene/graphene surface with hybrid wettability, chemical tolerance, and passive anti-icing for quantitative fog harvesting - Wei-long Zhou; Ting Wu; Yu Du; Xiao-hu Zhang; Xin-chang Chen; Jin-bo Li; Heng Xie; Jin-ping Qu (Chemical Engineering Journal, 2023)

Micropyrones A and B, two new α -pyrones from the actinomycete Microbacterium sp. GJ312 isolated from Glycyrrhiza uralensis Fisch - Ying-Ting Xu; Yu-Cai Luo; Jing-Hua Xue; Yu-Ping Li; Lei Dong; Wen-Jun Li; Zhong-Yu Zhou; Xiao-Yi Wei (Natural Product Research, 2023)

A glyoxylate-containing benzene derivative and butenolides from a marine algicolous fungus Aspergillus sp. SCSIO 41304 - Xin Qi; Wei-Hao Chen; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Xue-Feng Zhou; Yong-Hong Liu; Jun-Feng Wang; Yong Li (Natural Product Research, 2023)

Coexistence of antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) and IgA nephropathy - Qi Xiong; Wei Lin; Chanjuan Shen; Ting Meng; Rong Tang; Joshua D. Ooi; Peter J. Eggenhuizen; Jinbiao Chen; Wannian Nie; Xia Li; Qiaoling Zhou; Ping Xiao; et al. (Immunologic Research, 2023)

Rigid block characteristics on subaerial landslide-tsunamis using a 3D coupled Eulerian-Lagrangian model - Yi-ding Bao; Jian-ping Chen; Li-jun Su; Xin Zhou; Cheng-shan Yin (Journal of Mountain Science, 2023)

Effects of bepridil on early cardiac development of zebrafish - Ya-Lan Wei; Yu-Qing Lei; Zhou-Jie Ye; Xu-Dong Zhuang; Li-Ping Zhu; Xin-Rui Wang; Hua Cao (Cell and Tissue Research, 2023)

Flood risk assessment of loss of life for a coastal city under the compound effect of storm surge and rainfall - Yan Li; Wan-Huan Zhou; Ping Shen (Urban Climate, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Ultra-depleted melt product preserved in the Ladong ophiolitic peridotites of the North Qilian Orogenic Belt, Northern Tibet - Xiang Zhou; Jian-Ping Zheng; Zeng-Bao Huang; Zhi-Yong Li; Wei-Qi Zhang; Hong-Da Zheng; Qing Xiong; Hong-Kun Dai (Lithos, 2023)

Characteristics and origin of Lower Triassic Feixianguan Formation dolostones on the west side of Kaijiang–Liangping Trough, northeastern Sichuan Basin, China - Ling Zhou; Guangwei Wang; Ya Zhang; Yanping Qiao; Fang Hao; Rui Xu; Li Quan; Ping Wang (Marine and Petroleum Geology, 2023)

Response of ecosystem gross primary productivity to drought in northern China based on multi-source remote sensing data - Ting Zhang; Junzhi Zhou; Ping Yu; Jianzhu Li; Yanfu Kang; Bo Zhang (Journal of Hydrology, 2023)

Methane recovery from low-grade unconventional natural gas by the integrated mode of the conventional/improved vacuum pressure swing adsorption processes - Zhiling Qian; Yiwei Zhou; Ying Yang; Ping Li (Fuel, 2023)

Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale - Tin-Long Wong; Li-Feng Li; Ji-Xia Zhang; Quan-Wei Zhang; Xue-Ting Zhang; Li-Shuang Zhou; Hau-Yee Fung; Lei Feng; Hui-Yuan Cheng; Chu-Ying Huo; Man Liu; Wan-Rong Bao; et al. (Food Hydrocolloids, 2023)

Dysfunction of DNA repair for boosted tumor cell cycle arrest based on NIR-II biodegradable Te-prussian blue nanorod - Xiaoyang Liang; Ping Liu; Wen Li; Long Binh Vong; Tingting Wang; Lujing Geng; Yue Zhou; Siyu Wang; Qiang Lu; Fengping Tan; Xinxing Wang; Nan Li (Chemical Engineering Journal, 2023)

Sn2P2S6: A lead-free reversible thermochromic ferroelectric with high near-infrared reflectance - Meixia Wu; Xiao Zhou; Xihui Liang; Yifeng Han; Yonghong Li; Xingan Jiang; Xueyun Wang; Yisheng Chai; Xiang Zhou; Hui Yang; Dan Lin; Ping Xu; et al. (Chemical Engineering Journal, 2023)

Highly conductive, stretchable, durable, breathable electrodes based on electrospun polyurethane mats superficially decorated with carbon nanotubes for multifunctional wearable electronics - Guoxi Luo; Jiaqi Xie; Jielun Liu; Qiankun Zhang; Yunyun Luo; Min Li; Wenke Zhou; Ke Chen; Zhikang Li; Ping Yang; Libo Zhao; Kwok Siong Teh; et al. (Chemical Engineering Journal, 2023)

c-kit+VEGFR-2+ Mesenchymal Stem Cells Differentiate into Cardiovascular Cells and Repair Infarcted Myocardium after Transplantation - Pei Zhou; Shu-na Yu; Hai-feng Zhang; Yong-li Wang; Ping Tao; Yu-zhen Tan; Hai-jie Wang (Stem Cell Reviews and Reports, 2023)
Resent study suggests that c-kit + cells in bone marrow-derived MSCs may differentiate toward cardiamyocytes. However, the properties of c-kit + MSCs remain unclear. This study isolated c-kit + VEGFR-2 + cells from rat bone marrow-derived MSCs, and assessed potential of c-kit + VEGFR-2 + MSCs to differentiate towards cardiovascular cells and their efficiency of repairing the infarcted myocardium after transplantation. Gene expression profile of the cells was analyzed with RNA-sequencing. Potential of differentiation of the cells was determined after induction. Rat models of myocardial infarction were established by ligation of the left anterior descending coronary artery. The cells were treated with hypoxia and serum deprivation for four hours before transplantation. Improvement of cardiac function and repair of the infarcted myocardium were assessed at four weeks after transplantation. Gene expression profile revealed that c-kit + VEGFR-2 + MSCs expressed most smooth muscle-specific and myocardium-specific genes, while expression of endothelium-specific genes was upregulated significantly. After induction with VEGF or TGF-β for two weeks, the cells expressed CD31 and α-SMA respectively. At three weeks, BMP-2-induced cells expressed cTnT. After transplantation of the cells, cardiac function was improved, scar size of the infarcted myocardium was decreased, and angiogenesis and myocardial regeneration were enhanced significantly. Moreover, paracrine in the myocardium was increased after transplantation. These results suggest that c-kit + VEGFR-2 + MSCs have a potential of differentiation towards cardiovascular cells. Transplantation of c-kit + VEGFR-2 + MSCs is effective for repair of the infarcted myocardium. c-kit + VEGFR-2 + MSCs may be a reliable source for cell therapy of ischaemic diseases. Graphical abstract

Correction to: Gpx4, Selenov, and Txnrd3 Are Three Most Testis-Abundant Selenogenes Resistant to Dietary Selenium Concentrations and Actively Expressed During Reproductive Ages in Rats - Aiping Liu; Fengna Li; Ping Xu; Yanmei Chen; Xiongshun Liang; Shijie Zheng; Huicui Meng; Yumei Zhu; Junluan Mo; Chunmei Gong; Ji-Chang Zhou (Biological Trace Element Research, 2023)

Geographical, Sex, Age, and Seasonal Differences in Serum Manganese Status Among Chinese Adults with Hypertension - Hong Chen; Zhixin Cui; Wenhai Lu; Ping Wang; Jia Wang; Ziyi Zhou; Nan Zhang; Zhuo Wang; Tengfei Lin; Yun Song; Lishun Liu; Xiao Huang; et al. (Biological Trace Element Research, 2023)

Gpx4, Selenov, and Txnrd3 Are Three Most Testis-Abundant Selenogenes Resistant to Dietary Selenium Concentrations and Actively Expressed During Reproductive Ages in Rats - Aiping Liu; Fengna Li; Ping Xu; Yanmei Chen; Xiongshun Liang; Shijie Zheng; Huicui Meng; Yumei Zhu; Junluan Mo; Chunmei Gong; Ji-Chang Zhou (Biological Trace Element Research, 2023)

Cryo-EM structures reveal the dynamic transformation of human alpha-2-macroglobulin working as a protease inhibitor - Xiaoxing Huang; Youwang Wang; Cong Yu; Hui Zhang; Qiang Ru; Xinxin Li; Kai Song; Min Zhou; Ping Zhu (Science China Life Sciences, 2022)

Ginsenoside Rb1 inhibits oxidative stress-induced ovarian granulosa cell injury through Akt-FoxO1 interaction - Ping Zhou; Feng Deng; Zi Yang; Canhui Cao; Hongcui Zhao; Fenting Liu; Ke Zhong; Lin Fu; Tianliu Peng; Di Sun; Hui Liu; Rong Li; et al. (Science China Life Sciences, 2022)

Application of regional citrate anticoagulation in patients at high risk of bleeding during intermittent hemodialysis: a prospective multicenter randomized controlled trial - Xiaoyan Tang; Dezheng Chen; Ling Zhang; Ping Fu; Yanxia Chen; Zhou Xiao; Xiangcheng Xiao; Weisheng Peng; Li Cheng; Yanmin Zhang; Hongbo Li; Kehui Li; et al. (Journal of Zhejiang University-SCIENCE B, 2022)

Streptomyces: Derived Active Extract Inhibits Candida albicans Biofilm Formation - Sheng-qiang Yang; Hui-jie Zhou; Li-ping Teng; Hong Zeng (Current Microbiology, 2022)

Paenibacillus hamazuiensis sp. nov., a bacterium isolated from Hamazui hot spring in Yunnan province, south-west China - Juan Wang; Ming Deng; En-Min Zhou; Lei Ran; Cui-Ping Miao; Yi-Qing Li; Jun-Mei Ding; Shu-Kun Tang (Archives of Microbiology, 2022)

Theoretical analysis on influence factors of anchor cable internal force under over-excavation considering earth berm - Jiayong Lin; Feicong Zhou; Wenhao Fan; Mao Chen; Jinyi Li; Yifan Jiang; Ming Lin; Ping Zhou; Zhijie Wang (Arabian Journal of Geosciences, 2022)

Monoterpenoid indole alkaloids with potential neuroprotective activities from the stems and leaves of Melodinus cochinchinensis - Yu-Jie Li; Juan Li; Lan Xie; Jun-Yu Zhou; Qiu-Xuan Li; Rui-Yuan Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2022)

Bioclogging alleviation for constructed wetland based on the interaction among biofilm growth and hydrodynamics - Ping Tang; Li Chen; Wenming Zhang; Yongchao Zhou (Environmental Science and Pollution Research, 2022)

Streptomyces akebiae sp. nov., a novel actinomycete isolated from rhizosphere soil of Akebia trifoliate - Ping Mo; Kaiqin Li; Jinhua Zhou; Fumin Zhou; Yazhi Chen; Xiaojia Lin; Xiaoyu Liu; Kerui Huang; Wansheng Zou; Jian Gao (Antonie van Leeuwenhoek, 2022)

Exploring the R-ISS stage-specific regular networks in the progression of multiple myeloma at single-cell resolution - Ling Zhong; Xiao Yang; Yu Zhou; Jialing Xiao; Huan Li; Jiang Tao; Qian Xi; Chen Chu; Chenglong Li; Xi Yang; Chen Yang; Yi Zhang; et al. (Science China Life Sciences, 2022)

Dissecting the role of cell signaling versus CD8+ T cell modulation in propranolol antitumor activity - Wei Li; Jielin Wan; Cuiyu Chen; Chengfang Zhou; Ping Liao; Qian Hu; Jiali Hu; Yang Wang; Yu Zhang; Cong Peng; Yuanfei Huang; Weihua Huang; et al. (Journal of Molecular Medicine, 2022)

Transport process and mechanism of the Hongshiyan rock avalanche triggered by the 2014 Ludian earthquake, China - Shi-lin Zhang; Yue-ping Yin; Hai-bo Li; Wen-pei Wang; Jia-wen Zhou (Landslides, 2022)

On the Mechanism of Stress Superposition Inducing Outburst Under the Influence of Blind Fault Instability - Xun Zhao; Tao Feng; Ping Wang; Pengfei Wang; Ze Liao; Hongsheng Li; Ze Zhou (Geotechnical and Geological Engineering, 2022)

Degradation mechanism of HCN by electrochemically coupled copper-loaded magnetic nanoparticles in a liquid phase pseudo-homogeneous system - Guangfei Qu; Wei Ji; Junyan Li; Shuaiyu Liang; Zhishuncheng Li; Huimin Tang; Junhong Zhou; Ping Ning (Environmental Science and Pollution Research, 2022)

Deepened snow loosens temporal coupling between plant and microbial N utilization and induces ecosystem N losses - Zhou Jia; Ping Li; Yuntao Wu; Pengfei Chang; Meifeng Deng; Luyin Liang; Sen Yang; Chengzhang Wang; Bin Wang; Lu Yang; Xin Wang; Zhenhua Wang; et al. (Global Change Biology, 2022)
Seasonal differences in plant and microbial nitrogen (N) acquisition are believed to be a major mechanism that maximizes ecosystem N retention. There is also a concern that climate change may interrupt the delicate balance in N allocation between plants and microbes. Yet, convincing experimental evidence is still lacking. Using a 15 N tracer, we assessed how deepened snow affects the temporal coupling between plant and microbial N utilization in a temperate Mongolian grassland. We found that microbial 15 N recovery peaked in winter, accounting for 22% of the total ecosystem 15 N recovery, and then rapidly declined during the spring thaw. By stimulating N loss via N 2 O emission and leaching, deepened snow reduced the total ecosystem 15 N recovery by 42% during the spring thaw. As the growing season progresses, the 15 N released from microbial biomass was taken up by plants, and the competitive advantage for N shifted from microbes to plants. Plant 15 N recovery reached its peak in August, accounting for 17% of the total ecosystem 15 N recovery. The Granger causality test showed that the temporal dynamics of plant 15 N recovery can be predicted by microbial 15 N recovery under ambient snow but not under deepened snow. In addition, plant 15 N recovery in August was positively correlated with and best explained by microbial 15 N recovery in March. The lower microbial 15 N recovery under deepened snow in March reduced plant 15 N recovery by 73% in August. Together, our results provide direct evidence of seasonal differences in plant and microbial N utilization that are conducive to ecosystem N retention; however, deepened snow disrupted the temporal coupling between plant–microbial N use and turnover. These findings suggest that changes in snowfall patterns may significantly alter ecosystem N cycling and N‐based greenhouse gas emissions under future climate change. We highlight the importance of better representing winter processes and their response to winter climate change in biogeochemical models when assessing N cycling under global change.

Sandstorms cause shrinkage of Haloxylon ammodendron shrubs and limit their self-renewal - Sheng-bo Shi; Dang-wei Zhou; Fang-lin Wang; Rui Shi; Tao Sun; Tian-cai Li; Jia-lin Ma; Xiang Wan; Jian-ping Ma; Jing-nian Tang (Theoretical and Experimental Plant Physiology, 2022)
Haloxylon ammodendron is an excellent windproof and sand-fixing species whose shrubs are widely cultivated in arid desert areas of northwest China but are now at risk of degradation and shrinkage. Using the chlorophyll fluorescence image analysis technique, the response of photosystem II (PSII) photochemical efficiency and non-photochemical quenching capacity to sediment-carrying wind and sand-free wind (both 12 m s −1 ) lasting for 10, 20, and 40 min were studied with seedlings in a wind tunnel. The results indicated that the sand-free wind had little influence on the maximum quantum efficiency of PSII photochemistry, F v / F m , which was approximately 0.80 on average; however, the F v / F m decreased over exposure time in the sediment-carrying wind group, with values smaller than those in the wind-only group. The non-photochemical quenching was sensitive to wind erosion, and sediment-carrying wind could aggravate the reduction in non-photochemical quenching ( NPQ ). Except for the 10 min duration, the maximum quantum efficiency of PSII photochemistry after dark recovery for 15 min, F v r / F m r , was lower in seedlings exposed to sediment-carrying wind than in those in the wind-only group. Compared to wind-only, wind-blown sand led to a water imbalance and withering in seedlings, causing the concentration of photosynthetic pigments (when based on the fresh mass of green branches) to not decrease. With a longer exposure time to sediment-carrying wind, both the probability and extent of lignified spots occurring increased in green assimilative branches. Our results demonstrated that sediment-carrying wind at 12 m s −1 lasting for 20 min or more could cause irreversible damage to the photosynthetic apparatus of H. ammodendron seedlings. Therefore, frequent and strong sandstorms are the main disturbance factors leading to shrinkage of shrubs and limiting their self-renewal.

Prognostic Value of miR-137 in Children with Medulloblastoma and its Regulatory Effect on Tumor Progression - Wenyuan Ji; Xuan Zhe; Lusheng Li; Yang Cheng; Xueling Zhao; Ping Liang; Chunxi Long; Jianjun Zhou (NeuroMolecular Medicine, 2022)

Components Analysis of Recycled Alkali Black Liquor Combined with Corn Straw Under Ozone Pretreatment - Xiaohong Lu; Fei Li; Yiming Li; Shuo Fang; Xia Zhou; Zhezhen Zhao; Ping Liu (BioEnergy Research, 2022)

Diverse grouping and mating strategies in the Critically Endangered Hainan gibbon (Nomascus hainanus) - Ping Li; Paul A. Garber; Yu Bi; Kun Jin; Xuming Qi; Jiang Zhou (Primates, 2022)
Understanding flexibility in the social structure and mating strategies of the world’s last remaining population (35 individuals) of wild Hainan gibbons ( Nomascus hainanus ) is critical for developing effective management plans to aid in their population recovery. Three of the five remaining Hainan gibbon groups (A, B, and C) currently live in a social unit characterized by two or three adult males, two reproducing adult females, and offspring. A fourth group (D) contains one adult male, two adult females, and offspring, and Group E contains a single adult male–adult female pair with a young infant. In this study, we describe observations of copulations between multiple resident males and one of the two resident females in Group C. Group C is best described as a small multi-male/multi-female group. We found that this breeding female (F2) solicited copulations from two resident adult males (M1 and M2) on the same day, and also mated with each of these two males on different days. Resident males were not observed to interrupt the mating pair. Although factors such as a biased adult sex ratio, severe population disruption, and habitat degradation can help explain variation in group composition and mating strategies in Hainan gibbons, we argue that there exists considerable mating system variability across gibbon species, and that this variability offers important insights into male and female Hainan gibbon group structure and reproductive strategies.

The Effects of Ground and Treadmill Running on Energy Metabolism and Muscle Contractile Properties: A Randomized Cross-Over Study - Yuan Zhou; Jian-gang Chen; Xiao-long Li; Xin-liang Pan; Yi-zheng Zhou; Zheng-ao Li; Zhi-cheng Liang; Jia-min Long; Ming-ze Qin; Jing Zhang; Bing Shi; Bing-jun Wan; et al. (Journal of Science in Sport and Exercise, 2022)
Purpose This study aimed to compare the effects of ground and treadmill running on energy metabolism and muscle contractile properties, providing a basis for the general public to choose running venues. Methods Ten male college students (age, 20.10 ± 1.53 years; height, 176.20 ± 5.49 cm; weight, 72.14 ± 8.25 kg; body fat percent, 12.41% ± 4.65%) were recruited in this study. Energy expenditure (EE) was measured using the accelerometer (GT9X) combined with specific estimation equations. Average heart rate (HR) was measured using a heart rate band (Polar). Muscle contractile properties were assessed by measuring muscle displacement (Dm) and contraction velocity (Vc) using tensiomyography (TMG-S1). Blood glucose (Glu) and lactate (Lac) were measured by portable devices (eB-G and Lactate Scout). The running speed was 9 km/h and the duration was 25 min. Two-way ANOVA (protocol × time) was used to analyze the effect of running protocols on energy metabolism and muscle contractile properties. Results EE of treadmill running was significantly higher than EE of ground running (protocol main effect, P < 0.001), and HR of treadmill running was significantly higher than that of ground running in the first testing time (protocol simple effect, P = 0.026; protocol × time interaction P = 0.043). The decrease in Dm of the rectus femoris after treadmill running was significantly higher than that of ground running (protocol main effect, P = 0.009). The interaction of different running protocols and testing times on Lac was significant ( P = 0.025), but all results of the simple effects analysis were not statistically significant ( P > 0.05). Conclusion Our study found a difference in energy expenditure between treadmill and ground running at 9 km/h with duration of 25 min. In addition, treadmills are more likely to cause a decrease in muscle displacement distance of the rectus femoris measured after exercise than ground running. Future studies are needed to further investigate whether the differences are induced by internal metabolism or the environmental conditions of running.

Study on pressure arch effect of xigeda strata tunnel based on experiment and discrete element simulation - Ping Zhou; Yifan Jiang; Feicong Zhou; Jinyi Li; Ming Lin; Jiayong Lin; Zhijie Wang (Bulletin of Engineering Geology and the Environment, 2022)

Genome-based reclassification of the genus Meiothermus along with the proposal of a new genus Allomeiothermus gen. nov - Jian-Yu Jiao; Zheng-Han Lian; Ze-Tao Liu; Lan Liu; Meng-Meng Li; Ai-Ping Lv; Wen-Dong Xian; Ting Zhou; Zhitang Lyu; Nimaichand Salam; Wen-Jun Li (Antonie van Leeuwenhoek, 2022)

Two new dammarane-type triterpenoids from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hui-Rui Gao; Hong-Juan Song; Dan-Da Ma; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Xiao-Li Wang; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

Correction to: Spindle‑related brain activation in patients with insomnia disorder: An EEG‑fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Spindle-related brain activation in patients with insomnia disorder: An EEG-fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Epigenetic inactivation of ACAT1 promotes epithelial-mesenchymal transition of clear cell renal cell carcinoma - Peipei Han; Shu Wu; Limei Li; Danping Li; Jun Zhao; Haishan Zhang; Yifang Wang; Xuemin Zhong; Zhe Zhang; Ping Li; Liudmila Matskova; Xiaoying Zhou (Genes & Genomics, 2022)

LncRNA NEAT1 ameliorate ischemic stroke via promoting Mfn2 expression through binding to Nova and activates Sirt3 - Zhi-Wen Zhou; Xiang Ren; Li-Jun Zheng; Ai-Ping Li; Wen-Sheng Zhou (Metabolic Brain Disease, 2022)

Mutation of a prenyltransferase results in accumulation of subglutinols and destruxins and enhanced virulence in the insect pathogen, Metarhizium anisopliae - Chengzhou Li; Wenyou Huang; Tingting Zhou; Qian Zhao; Peiquan Huang; Ping Qi; Song Huang; Shuaishuai Huang; Nemat O. Keyhani; Zhen Huang (Environmental Microbiology, 2022)
Summary The insect pathogenic fungus, Metarhizium anisopliae is a commercialized microbial agent used in biological control efforts targeting a diverse range of agricultural and other insect pests. The second step in the synthesis of a group of M . anisopliae α‐pyrone diterpenoids (termed subglutinols) involves the activity of a prenyltransferase family geranylgeranyl diphosphate synthase (product of the subD / MaGGPPS5 gene). Here, we show that targeted gene disruption of MaGGPPS 5 results in earlier conidial germination and faster greater vegetative growth compared to the wild type (WT) parent and complemented strains. In addition, insect bioassays revealed that the Δ MaGGPPS5 mutant strain displayed significantly increased virulence, with a ~50% decrease in the mean lethal time (LT 50 , from 6 to 3 days) to kill (50% of) target insects, and an ~15–40‐fold decrease in the mean lethal dose (LC 50 ). Metabolite profiling indicated increased accumulation in the Δ MaGGPPS5 mutant of select subglutinols (A, B and C) and destruxins (A, A2, B and B2), the latter a set of fungal secondary metabolites that act as insect toxins, with a concomitant loss of production of subglutinol ‘analogue 45’. These data suggest that the increased virulence phenotype seen for the Δ MaGGPPS5 strain can, at least in part, be attributed to a combination of faster growth and increased insect toxin production, linking the production of two different secondary metabolite pathways, and represent a novel approach for the screening of isolates with enhanced virulence via modulation of terpenoid secondary metabolite biosynthesis.

Effects of temperature, moisture, substrates and soil coverage on sclerotium germination and hyphal growth of Southern blight of apple in China - Xiang-li Dong; Chang-yan Gao; Ping-liang Li; Sen Lian; Shan-yue Zhou; Bao-hua Li (European Journal of Plant Pathology, 2022)

Oxidative degradation/mineralization of dimethyl phthalate (DMP) from plastic industrial wastewater using ferrate(VI)/TiO2 under ultraviolet irradiation - Ping Wang; Yi Ding; Liting Zhu; Yunhao Zhang; Sijie Zhou; Linbei Xie; Ao Li (Environmental Science and Pollution Research, 2022)

Comparative Genomic Analysis of Streptococcus pneumoniae Strains: Penicillin Non-susceptible Multi-drug-Resistant Serotype 19A Isolates - Lifeng Li; Juanjuan Zhou; Mingchao Li; Zengyuan Yu; Kaijie Gao; Junwen Yang; Ping Cheng; Junmei Yang; Wancun Zhang; Zhidan Yu; Huiqing Sun (Current Microbiology, 2022)

Aberrant functional and effective connectivity of the frontostriatal network in unilateral acute tinnitus patients with hearing loss - Gang-Ping Zhou; Yu-Chen Chen; Wang-Wei Li; Heng-Le Wei; Yu-Sheng Yu; Qing-Qing Zhou; Xindao Yin; Yue-Jin Tao; Hong Zhang (Brain Imaging and Behavior, 2022)

A new indole alkaloid from the stems of Glycosmis puberula var . craibii - Qi Zhou; Chun-Xiao Jiang; Shou-Yuan Wu; Zi-Ming Chen; Li-Ping Huang (Natural Product Research, 2022)

Genetic improvement of grain quality traits in indica inbred rice cultivars developed in South China during 1956–2020 - Xin-Qiao Zhou; Da-Gang Chen; Jie Guo; Ping-Li Chen; Li-Jun Li; Ke Chen; You-Ding Chen; Chuan-Guang Liu; Ze-Min Zhang (Euphytica, 2022)

Performance and mechanisms of fly ash for graphene oxide removal from aqueous solution - Ping Jiang; Lin Zhou; Wei Wang; Na Li; Fang Zhang (Environmental Science and Pollution Research, 2022)

Subproteomic profiling from renal cortices in OLETF rats reveals mutations of multiple novel genes in diabetic nephropathy - Zhiguo Li; Hong Shen; Yeqiang Liu; Xuefeng Zhou; Meihua Yan; Hailan He; Tingting Zhao; Haojun Zhang; Ping Li (Genes & Genomics, 2022)

Antioxidant CPA-type indole alkaloids produced from the deep-sea derived fungus Aspergillus sp. SCSIO 41024 - Wei-Hao Chen; Kun-Long Li; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Xue-Feng Zhou; Jun-Jian Wang; Yong-Hong Liu; Jun-Feng Wang (Natural Product Research, 2021)

Retraction Note: Coastal meteorological characteristics based on big data and financial tax optimization of urban enterprises - Zhou Li; Che Ping (Arabian Journal of Geosciences, 2021)

Stress response mechanisms and description of three novel species Shewanella avicenniae sp. nov., Shewanella sedimentimangrovi sp. nov. and Shewanella yunxiaonensis sp. nov., isolated from mangrove ecosystem - Guo-Hong Liu; Qi Zhang; Manik Prabhu Narsing Rao; Shang Yang; Rong Tang; Huai Shi; Jie-Ping Wang; Guan-Min Huang; Bo Liu; Shun-Gui Zhou; Wen-Jun Li (Antonie van Leeuwenhoek, 2021)

Genetic Prion Disease: Insight from the Features and Experience of China National Surveillance for Creutzfeldt-Jakob Disease - Qi Shi; Cao Chen; Kang Xiao; Wei Zhou; Li-Ping Gao; Dong-Dong Chen; Yue-Zhang Wu; Yuan Wang; Chao Hu; Chen Gao; Xiao-Ping Dong (Neuroscience Bulletin, 2021)

Rapid visual genotyping method for germline mutants with small genomic fragment deletion by allele-specific PCR and lateral flow nucleic acid biosensor - Qiuju Su; Xiang Zhou; Tianwen Wu; Kui Li; Wentao Xu; Zhenyu Lin; Ping Shen; Bang Liu (Molecular Biology Reports, 2021)

Spatiotemporal change of vegetation coverage recovery and its driving factors in the Wenchuan earthquake-hit areas - Xiao-fei Sun; Lin-guo Yuan; Ying-zhi Zhou; Huai-yong Shao; Xian-feng Li; Ping Zhong (Journal of Mountain Science, 2021)

Two new biflavanoids from Selaginella trichoclada Alsto - Yang Xie; Ping-Sheng Xu; Kang-Ping Xu; Zhen-Xing Zou; Gan Zhou; Dai Li; Dan Li; Xiao-Min Li; Jing Li; Gui-Shan Tan (Natural Product Research, 2021)

Two new cephalochromin derivative from the Alternaria sp. ZG22 - Xin-Ming Song; Xue-Ming Zhou; Ya-Ling Li; Li-Bing Huang; Cai-Cui Chen; Yan Gao; Lin He; Xiao-qun Mao; Bing Chen; Jing-Wen Liu; Hui-Jie Liu; Xiao-Ping Song; et al. (Natural Product Research, 2021)

MiR-590-5p inhibits pathological hypertrophy mediated heart failure by targeting RTN4 - Ping Fan; Likun Zhang; Tianyu Cheng; Jing Wang; Junyun Zhou; Li Zhao; Cuie Hua; Quan Xia (Journal of Molecular Histology, 2021)

Globular adiponectin inhibits osteoblastic differentiation of vascular smooth muscle cells through the PI3K/AKT and Wnt/β-catenin pathway - Yun Zhou; Li-Long Wei; Rui-Ping Zhang; Cheng-Wu Han; Yongtong Cao (Journal of Molecular Histology, 2021)
Lipid metabolism is closely related to the improvement of vascular calcification (VC) in chronic kidney disease (CKD). Globular adiponectin (gAd) has been reported to be involved in the development of VC in CKD, but the detailed regulatory role remains unclear. The present study is aimed to investigate the biological function and the underlying regulation mechanism of gAd in the process of VC during CKD. Vascular smooth muscle cells (VSMCs) calcification was determined by Alizarin Red S staining. Protein signaling related with VC was tested by western blotting. The expression and intracellular localization of runt-related transcription factor 2 (Runx2) was detected by immunofluorescence and uraemic rat with VC was established by a two-step nephrectomy. Combined with the results of Alizarin Red S staining, we discovered that β-glycerophosphate (β-Gp)-induced the osteoblastic differentiation of VSMCs was significantly reversed by gAd treatment. Along with the VSMCs calcification and the increase of Runx2 in β-Gp-exposed VSMCs, the activities of protein kinase B (AKT) and Wnt/β-catenin pathway were enhanced, but that were counteracted by the exposure of gAd in rat and human VSMCs. After administration with agonists of the Wnt (SKL2001) and AKT (SC79), there appeared more osteoblastic differentiation and higher expression of Runx2 in gAd-treated VSMCs, but showing lower impact in the presence of SC79 than that in the presence of SKL2001. In the in vivo experiments, intravenous injection of gAd also significantly inhibited VC and Runx2 level in uraemic rat in a dose-dependent manner, possibly through regulating Wnt/β-catenin pathway. This study demonstrates that gAd ameliorates osteoblastic differentiation of VSMCs possibly by blocking PI3K/AKT and Wnt/β-catenin signaling transduction. The findings provide an important foundation for gAd in treating VC in kidney diseases.

Diversity and arsenic-metabolizing gene clusters of indigenous arsenate-reducing bacteria in high arsenic groundwater of the Hetao Plain, Inner Mongolia - Yanhong Wang; Dazhun Wei; Ping Li; Zhou Jiang; Han Liu; Chun Qing; Helin Wang (Ecotoxicology, 2021)

Damage mechanism of tunnels in the high-content salt rock stratum - Ping Zhou; Jinyi Li; Yifan Jiang; Feicong Zhou; Ming Lin; Jiayong Lin; Zhijie Wang (Bulletin of Engineering Geology and the Environment, 2021)

Aberrant activity within auditory network is associated with psychiatric comorbidities in interictal migraineurs without aura - Heng-Le Wei; Yu-Chen Chen; Yu-Sheng Yu; Xi Guo; Gang-Ping Zhou; Qing-Qing Zhou; Li-Jie Qu; Xindao Yin; Junrong Li; Hong Zhang (Brain Imaging and Behavior, 2021)

RETRACTED ARTICLE: Coastal meteorological characteristics based on big data and financial tax optimization of urban enterprises - Zhou Li; Che Ping (Arabian Journal of Geosciences, 2021)

Long‐term nitrogen input alters plant and soil bacterial, but not fungal beta diversity in a semiarid grassland - Weixing Liu; Lingli Liu; Xian Yang; Meifeng Deng; Zhou Wang; Pandeng Wang; Sen Yang; Ping Li; Ziyang Peng; Lu Yang; Lin Jiang (Global Change Biology, 2021)
Anthropogenic nitrogen (N) input is known to alter plant and microbial α‐diversity, but how N enrichment influences β‐diversity of plant and microbial communities remains poorly understood. Using a long‐term multilevel N addition experiment in a temperate steppe, we show that plant, soil bacterial and fungal communities exhibited different responses in their β‐diversity to N input. Plant β‐diversity decreased linearly as N addition increased, as a result of increased directional environmental filtering, where soil environmental properties largely explained variation in plant β‐diversity. Soil bacterial β‐diversity first increased then decreased with increasing N input, which was best explained by corresponding changes in soil environmental heterogeneity. Soil fungal β‐diversity, however, remained largely unchanged across the N gradient, with plant β‐diversity, soil environmental properties, and heterogeneity together explaining an insignificant fraction of variation in fungal β‐diversity, reflecting the importance of stochastic community assembly. Our study demonstrates the divergent effect of N enrichment on the assembly of plant, soil bacterial and fungal communities, emphasizing the need to examine closely associated fundamental components (i.e., plants and microorganisms) of ecosystems to gain a more complete understanding of ecological consequences of anthropogenic N enrichment.

First report of Bacillus altitudinis causing seed rot of pomegranate in China - Qili Liu; Dongxiao Li; Haiyan Hu; Qianqian Huang; Yongheng Zhang; Feng Zhou; Puwen Song; Yuanyuan Guan; Ruifang Bu; Ping Hu; Jianjun Hao; Chengwei Li (Australasian Plant Pathology, 2021)

Detecting freeze–thaw damage degradation of sandstone with initial damage using NMR technology - Taoying Liu; Chaoyang Zhang; Jiangteng Li; Keping Zhou; Cao Ping (Bulletin of Engineering Geology and the Environment, 2021)

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)

Comparison of in Vascular Bioreactors and In Vivo Models of Degradation and Cellular Response of Mg–Zn–Mn Stents - Ningling Zhou; Ping Li; Hua Qiu; Jin Wang; Nan Huang; Ansha Zhao; Juan Wang (Annals of Biomedical Engineering, 2021)

Exposed to Mercury-Induced Oxidative Stress, Changes of Intestinal Microflora, and Association between them in Mice - Yulan Zhao; Changming Zhou; Xiaoquan Guo; Guoliang Hu; Guyue Li; Yu Zhuang; Huabin Cao; Lin Li; Chonghong Xing; Caiying Zhang; Fan Yang; Ping Liu (Biological Trace Element Research, 2021)

Emergent chikungunya fever and vertical transmission in Yunnan Province, China, 2019 - XiaoXiong Yin; Ting-Song Hu; HaiLin Zhang; YongHua Liu; ZhiJian Zhou; LeBin Liu; Ping Li; YiYin Wang; ZhaoLan Yang; Jing Yu; SiYu Chen; Fu-Qiang Zhang (Archives of Virology, 2021)

Influence of major water conservation projects on river channels and shorelines in the middle and lower reaches of the Yangtze River - Yue-hua Jiang; He-qin Cheng; Quan-ping Zhou; Yun Li; Guo-qiang Yang; Yang Jin; Shi-jia Mei; Xuan Gu; Hong Zhang (Arabian Journal of Geosciences, 2021)

miR-20a Promotes the Axon Regeneration of DRG Neurons by Targeting Nr4a3 - Lili Zhao; Leilei Gong; Ping Li; Jing Qin; Lingchi Xu; Qiyao Wei; Huimin Xie; Susu Mao; Bin Yu; Xiaosong Gu; Songlin Zhou (Neuroscience Bulletin, 2021)

Not vegetation itself but mis-revegetation reduces water resources - Guoyi Zhou; Jun Xia; Ping Zhou; Tingting Shi; Lin Li (Science China Earth Sciences, 2021)

Exploring soil erosion trajectories and their divergent responses to driving factors: a model-based contrasting study in highly eroded mountain areas - Chong Jiang; Zhiyuan Yang; Minting Li; Jialing Dai; Xinchi Wang; Haiyan Zhang; Long Yang; Lingling Zhao; Meili Wen; Ping Zhou (Environmental Science and Pollution Research, 2021)

Suppression of miR-4463 promotes phenotypic switching in VSMCs treated with Ox-LDL - Xueqin Wang; Hui Li; Yuetian Zhang; Qi Liu; Xiaolei Sun; Xuemei He; Qian Yang; Ping Yuan; Xiangyu Zhou (Cell and Tissue Research, 2021)

SIMS U-Pb geochronology for the Jurassic Yanliao Biota from Bawanggou section, Qinglong (northern Hebei Province, China) - Zhiqiang Yu; Huaiyu He; Gang Li; Chenglong Deng; Haibing Wang; Xinxin Zhang; Qing Yang; Xiao-Ping Xia; Zhonghe Zhou; Rixiang Zhu (International Geology Review, 2021)

Altered BMP-Smad4 signaling causes complete cleft palate by disturbing osteogenesis in palatal mesenchyme - Nan Li; Jing Liu; Han Liu; Shangqi Wang; Ping Hu; Hailing Zhou; Jing Xiao; Chao Liu (Journal of Molecular Histology, 2021)

The role of MYB proto-oncogene like 2 in tamoxifen resistance in breast cancer - Xia Li; Xi Zhang; Cong-Cong Wu; Ping-Ping Li; Yi-Mou Fu; Li-Hua Xie; Shuang-Shuang Sun; Ying-Ying Zhou; Bao-Ling Zhu (Journal of Molecular Histology, 2021)

Mass balance reconstruction for Shiyi Glacier in the Qilian Mountains, Northeastern Tibetan Plateau, and its climatic drivers - Hui Zhang; Zhongqin Li; Ping Zhou (Climate Dynamics, 2021)

Deepened snow cover alters biotic and abiotic controls on nitrogen loss during non-growing season in temperate grasslands - Zhou Jia; Ping Li; Yuntao Wu; Sen Yang; Chengzhang Wang; Bin Wang; Lu Yang; Xin Wang; Jing Li; Ziyang Peng; Lulu Guo; Weixing Liu; et al. (Biology and Fertility of Soils, 2021)

Sesquiterpenoids and meroterpenoids from a mangrove derived fungus Diaporthe sp. SCSIO 41011 - Xiao-Wei Luo; Chun-Mei Chen; Kun-Long Li; Xiu-Ping Lin; Cheng-Hai Gao; Xue-Feng Zhou; Yong-Hong Liu (Natural Product Research, 2021)

Correction to: Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Chang-Qi Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Tau Accumulation via Reduced Autophagy Mediates GGGGCC Repeat Expansion-Induced Neurodegeneration in Drosophila Model of ALS - Xue Wen; Ping An; Hexuan Li; Zijian Zhou; Yimin Sun; Jian Wang; Lixiang Ma; Boxun Lu (Neuroscience Bulletin, 2020)

SUMOylation of Pdia3 exacerbates proinsulin misfolding and ER stress in pancreatic beta cells - Na Li; Xi Luo; Qilin Yu; Ping Yang; Zhishui Chen; Xinqiang Wang; Jipin Jiang; Jing Xu; Quan Gong; Decio L. Eizirik; Zhiguang Zhou; Jiajun Zhao; et al. (Journal of Molecular Medicine, 2020)

Dietary lipid concentrations influence growth, body composition, morphology of the liver and mid-intestine, and antioxidant status of marbled eel (Anguilla marmorata) - Shi-Jun Chen; Peng Liu; You-Ming Jia; Hong-Ping Liao; Shao-Xuan Zhu; Li-Liu Zhou; Xue-Ming Dan; Li Liu; Jia-Hao Li; Su-Bi Zheng; Jun-Jiang Yang; Lian Gan (Aquaculture International, 2020)

Genetic diversity analysis reveals new badnaviruses infecting banana in South China - Xue-Qin Rao; Zi-Lin Wu; Wan Wang; Lin Zhou; Jie Sun; Hua-Ping Li (Journal of Plant Pathology, 2020)

Highly sensitive serological approaches for Pepino mosaic virus detection - Wan-qin He; Jia-yu Wu; Yi-yi Ren; Xue-ping Zhou; Song-bai Zhang; Ya-juan Qian; Fang-fang Li; Jian-xiang Wu (Journal of Zhejiang University-SCIENCE B, 2020)

Integrated biomarker parameters response to the toxic effects of high stocking density, CuSO4, and trichlorfon on fish and protective role mediated by Angelica sinensis extract - HuaTao Li; YuTing Ma; Ying Liu; Min Wu; Jiao Long; XiaoQin Jing; SiShun Zhou; Ping Yuan; Jun Jiang (Fish Physiology and Biochemistry, 2020)

Pre-symptomatic local brain activity and functional connectivity alterations in nasopharyngeal carcinoma patients who developed radiation encephalopathy following radiotherapy - You-ming Zhang; Jian-ming Gao; Hong Zhou; Li Li; Li-zhi Liu; Zai-de Han; Xiao-ping Yi; Wei-hua Liao (Brain Imaging and Behavior, 2020)

Impaired functional connectivity of limbic system in migraine without aura - Heng-Le Wei; Jinan Chen; Yu-Chen Chen; Yu-Sheng Yu; Gang-Ping Zhou; Li-Jie Qu; Xindao Yin; Junrong Li; Hong Zhang (Brain Imaging and Behavior, 2020)

Comparative iTRAQ Proteomics Reveals Multiple Effects of Selenium Yeast on Dairy Cows in Parturition - Zhi-hua Ren; Li-peng Bai; Liu-hong Shen; Zheng-zhong Luo; Zi-han Zhou; Zhi-cai Zuo; Xiao-ping Ma; Jun-liang Deng; Ya Wang; Sheng-yu Xu; Yu-heng Luo; Sui-zhong Cao; et al. (Biological Trace Element Research, 2020)

Model test of the stability degradation of a prestressed anchored rock slope system in a corrosive environment - Cong Li; Rong-tang Zhang; Jie-bing Zhu; Zhi-jun Liu; Bo Lu; Bin Wang; Yu-zhou Jiang; Jie-sheng Liu; Ping Zeng (Journal of Mountain Science, 2020)

Constraints of salinity- and sediment-induced stratification on the turbidity maximum in a tidal estuary - Ting Lu; Hao Wu; Fan Zhang; Jiasheng Li; Liang Zhou; Jianjun Jia; Zhanhai Li; Ya Ping Wang (Geo-Marine Letters, 2020)

Characterization of the promoter of the nitrate transporter-encoding gene nrtA in Aspergillus nidulans - Yangyi Liu; Haoxiang Li; Jingyi Li; Yao Zhou; Zhemin Zhou; Ping Wang; Shengmin Zhou (Molecular Genetics and Genomics, 2020)

Fluorescence in situ hybridization of 35S rDNA sites and karyotype of wild Lilium (Liliaceae) species from China: taxonomic and phylogenetic implications - Yan-Ping Zhou; Zhong-Xuan Wang; Yun-Peng Du; Jie-Wen Li; Heng-bin He; Gui-Xia Jia (Genetic Resources and Crop Evolution, 2020)

Altered Energy Metabolism During Early Optic Nerve Crush Injury: Implications of Warburg-Like Aerobic Glycolysis in Facilitating Retinal Ganglion Cell Survival - Jingyi Zhu; Ping Li; Yuan-Guo Zhou; Jian Ye (Neuroscience Bulletin, 2020)
Neurons, especially axons, are metabolically demanding and energetically vulnerable during injury. However, the exact energy budget alterations that occur early after axon injury and the effects of these changes on neuronal survival remain unknown. Using a classic mouse model of optic nerve-crush injury, we found that traumatized optic nerves and retinas harbor the potential to mobilize two primary energetic machineries, glycolysis and oxidative phosphorylation, to satisfy the robustly increased adenosine triphosphate (ATP) demand. Further exploration of metabolic activation showed that mitochondrial oxidative phosphorylation was amplified over other pathways, which may lead to decreased retinal ganglion cell (RGC) survival despite its supplement to ATP production. Gene set enrichment analysis of a microarray (GSE32309) identified significant activation of oxidative phosphorylation in injured retinas from wild-type mice compared to those from mice with deletion of phosphatase and tensin homolog (PTEN), while PTEN-/- mice had more robust RGC survival. Therefore, we speculated that the oxidation-favoring metabolic pattern after optic nerve-crush injury could be adverse for RGC survival. After redirecting metabolic flux toward glycolysis (magnifying the Warburg effect) using the drug meclizine, we successfully increased RGC survival. Thus, we provide novel insights into a potential bioenergetics-based strategy for neuroprotection.

Biofertilizers with beneficial rhizobacteria improved plant growth and yield in chili (Capsicum annuum L.) - Jing-Yi Gou; Sheng-Zhou Suo; Kun-Zhong Shao; Qi Zhao; Dan Yao; Hui-Ping Li; Jin-Lin Zhang; Christopher Rensing (World Journal of Microbiology and Biotechnology, 2020)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

Deepened winter snow cover enhances net ecosystem exchange and stabilizes plant community composition and productivity in a temperate grassland - Ping Li; Emma J. Sayer; Zhou Jia; Weixing Liu; Yuntao Wu; Sen Yang; Chengzhang Wang; Lu Yang; Dima Chen; Yongfei Bai; Lingli Liu (Global Change Biology, 2020)
Global warming has greatly altered winter snowfall patterns, and there is a trend towards increasing winter snow in semi‐arid regions in China. Winter snowfall is an important source of water during early spring in these water‐limited ecosystems, and it can also affect nutrient supply. However, we know little about how changes in winter snowfall will affect ecosystem productivity and plant community structure during the growing season. Here, we conducted a 5‐year winter snow manipulation experiment in a temperate grassland in Inner Mongolia. We measured ecosystem carbon flux from 2014 to 2018 and plant biomass and species composition from 2015 to 2018. We found that soil moisture increased under deepened winter snow in early growing season, particularly in deeper soil layers. Deepened snow increased the net ecosystem exchange of CO 2 (NEE) and reduced intra‐ and inter‐annual variation in NEE. Deepened snow did not affect aboveground plant biomass (AGB) but significantly increased root biomass. This suggested that the enhanced NEE was allocated to the belowground, which improved water acquisition and thus contributed to greater stability in NEE in deep‐snow plots. Interestingly, the AGB of grasses in the control plots declined over time, resulting in a shift towards a forb‐dominated system. Similar declines in grass AGB were also observed at three other locations in the region over the same time frame and are attributed to 4 years of below‐average precipitation during the growing season. By contrast, grass AGB was stabilized under deepened winter snow and plant community composition remained unchanged. Hence, our study demonstrates that increased winter snowfall may stabilize arid grassland systems by reducing resource competition, promoting coexistence between plant functional groups, which ultimately mitigates the impacts of chronic drought during the growing season.

Tenuazonic acid-induced change in volatile emission from rose plants and its chemometrical analysis - Fa-zhong Yang; Yun-xian Li; Min Tang; Guo-lei Zhu; Shi-ping Zhou; Bin Yang (Journal of Plant Diseases and Protection, 2020)

Outbreak of carp edema virus disease in cultured ornamental koi in a lower temperature in China - Ping Ouyang; Yaojia Zhou; Ruixue Yang; Zhuangzhi Yang; Kaiyu Wang; Yi Geng; Weiming Lai; Xiaoli Huang; Defang Chen; Jing Fang; Zhengli Chen; Li Tang; et al. (Aquaculture International, 2020)

Evolution of the novel coronavirus from the ongoing Wuhan outbreak and modeling of its spike protein for risk of human transmission - Xintian Xu; Ping Chen; Jingfang Wang; Jiannan Feng; Hui Zhou; Xuan Li; Wu Zhong; Pei Hao (Science China Life Sciences, 2020)

Roles of PTBP1 in alternative splicing, glycolysis, and oncogensis - Wei Zhu; Bo-lun Zhou; Li-juan Rong; Li Ye; Hong-juan Xu; Yao Zhou; Xue-jun Yan; Wei-dong Liu; Bin Zhu; Lei Wang; Xing-jun Jiang; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2020)

Three Chemosensory Proteins Involved in Chemoreception of Oedaleus asiaticus (Orthopera: Acridoidea) - Yuan-Tao Zhou; Ling Li; Xiao-Rong Zhou; Yao Tan; Bao-Ping Pang (Journal of Chemical Ecology, 2020)

The false smut pathogen Ustilaginoidea virens requires rice stamens for false smut ball formation - Jing Fan; Jie Liu; Zhi‐You Gong; Pei‐Zhou Xu; Xiao‐Hong Hu; Jin‐Long Wu; Guo‐Bang Li; Juan Yang; Yu‐Qiu Wang; Yu‐Feng Zhou; Shuang‐Cheng Li; Li Wang; et al. (Environmental Microbiology, 2020)
Summary Rice false smut has emerged as a serious grain disease in rice production worldwide. The disease is characterized by the transformation of individual rice florets into false smut balls, which is caused by the fungal pathogen Ustilaginoidea virens . To date, little is known about the host factors required for false smut ball formation by U . virens . In this study, we identified histological determinants for the formation of false smut balls by inoculating U . virens into rice floral mutants defective with respect to individual floral parts. The results showed that U . virens could form mature false smut balls in rice floral mutants with defective pistils, but failed to develop false smut balls in the superwoman mutant lacking stamens, identifying that U . virens requires rice stamens to complete its infection cycle. Comparative transcriptome analysis indicated a list of candidate host genes that may facilitate nutrient acquisition by U . virens from the rice stamens, such as SWEET11 , SWEET14 and SUT5 , and genes involved in the biosynthesis of trehalose and raffinose family sugars. These data pinpoint rice stamens as the key target organ of U . virens infection and provide a valuable starting point for dissecting the molecular mechanism of false smut ball formation.

Relative energy zero ratio-based approach for identifying pulse-like ground motions - Ping Liu; Ning Li; Hua Ma; Lili Xie; Baofeng Zhou (Earthquake Engineering and Engineering Vibration, 2020)

Paramyxoviruses respiratory syncytial virus, parainfluenza virus, and human metapneumovirus infection in pediatric hospitalized patients and climate correlation in a subtropical region of southern China: a 7-year survey - Wen-Kuan Liu; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Li Zhang; Shu-Jun Gu; Rong Zhou; Qian Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Thermus caldilimi sp. nov., a thermophilic bacterium isolated from a geothermal area - Meng-Meng Li; Wen-Dong Xian; Xiao-Tong Zhang; Yi-Rui Yin; En-Min Zhou; Yi-Ping Ding; Lan Liu; Bao-Zhu Fang; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Genome-based reclassification of Bacillus plakortidis Borchert et al. 2007 and Bacillus lehensis Ghosh et al. 2007 as a later heterotypic synonym of Bacillus oshimensis Yumoto et al. 2005; Bacillus rhizosphaerae Madhaiyan et al. 2011 as a later heterotypic synonym of Bacillus clausii Nielsen et al. 1995 - Guo-Hong Liu; Manik Prabhu Narsing Rao; Zhou-Yan Dong; Jie-Ping Wang; Jian-Mei Che; Qian-Qian Chen; Cetin Sengonca; Bo Liu; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Multi‐model analysis of climate impacts on plant photosynthesis in China during 2000–2015 - Hao Yan; Shao‐Qiang Wang; Jun‐Bang Wang; Yun Cao; Ling‐Ling Xu; Men‐Xin Wu; Lu Cheng; Liu‐Xi Mao; Feng‐Hua Zhao; Xian‐Zhou Zhang; Yun‐Fen Liu; Yan‐Fen Wang; et al. (International Journal of Climatology, 2019)
Differences, arising from differences in gross primary production (GPP) model structures and driving forces, have fuelled arguments concerning interannual changes of GPP in China since 2000. To better investigate the interannual variability of GPP and its covariance with climate factors in China, this study adopted a multi‐model analysis based on three GPP models (i.e., Terrestrial Ecosystem Carbon flux model [TEC], Breathing Earth System Simulator model [BESS], and MOD17 GPP model). The results show that annual GPP in China increased by 0.021–0.057 Pg C year −1 from 2000 to 2015 attributable to atmospheric‐CO 2 fertilization effects and favourable climate change, that is, increasing precipitation ( P r ) and temperature ( T a ). However, northern China and southern China had a large difference in the amplitude of these GPP changes; annual GPP increased by 0.017–0.039 Pg C year −1 in northern China but only 0.001–0.018 Pg C year −1 in southern China. Northern China and southern China occupy contrasting climate zones and this contrast produced different interannual variability of GPP through different mechanisms. Northern China has a dry climate with GPP changes sensitive to P r . As a result, more P r along with higher T a in northern China produced the strong uptrend of GPP from 2000 to 2015. In contrast, southern China has a wet climate with its GPP sensitive to solar radiation and T a . For the interval of 2000–2015, decreasing radiation plus drought exerted a negative influence on GPP in southern China. This study highlights the diverse mechanisms in which climate change affects GPP in dry and wet climate zones. A robust multi‐model analysis is preferred to reduce uncertainties arising from a single GPP model and its driving data.

The Verticillium dahliae Sho1‐MAPK pathway regulates melanin biosynthesis and is required for cotton infection - Jun‐Jiao Li; Lei Zhou; Chun‐Mei Yin; Dan‐Dan Zhang; Steven J. Klosterman; Bao‐Li Wang; Jian Song; Dan Wang; Xiao‐Ping Hu; Krishna V. Subbarao; Jie‐Yin Chen; Xiao‐Feng Dai (Environmental Microbiology, 2019)
Summary Verticillium dahliae is a soil‐borne fungus that causes vascular wilt on numerous plants worldwide. The fungus survives in the soil for up to 14 years by producing melanized microsclerotia. The protective function of melanin in abiotic stresses is well documented. Here, we found that the V . dahliae tetraspan transmembrane protein VdSho1, a homolog of the Saccharomyces cerevisiae Sho1, acts as an osmosensor, and is required for plant penetration and melanin biosynthesis. The deletion mutant Δ Sho1 was incubated on a cellophane membrane substrate that mimics the plant epidermis, revealing that the penetration of Δ Sho1 strain was reduced compared to the wild‐type strain. Furthermore, VdSho1 regulates melanin biosynthesis by a signalling mechanism requiring a kinase‐kinase signalling module of Vst50‐Vst11‐Vst7. Strains, Δ Vst50 , Δ Vst7 and Δ Vst11 also displayed defective penetration and melanin production like the Δ Sho1 strain. Defects in penetration and melanin production in Δ Sho1 were restored by overexpression of Vst50 , suggesting that Vst50 lies downstream of VdSho1 in the regulatory pathway governing penetration and melanin biosynthesis. Data analyses revealed that the transmembrane portion of VdSho1 was essential for both membrane penetration and melanin production. This study demonstrates that Vst50‐Vst11‐Vst7 module regulates VdSho1‐mediated plant penetration and melanin production in V . dahliae , contributing to virulence.

Correction to: Vertical Distributions of Suspended Sediment Concentrations in the Turbidity Maximum Zone of the Periodically and Partially Stratified Changjiang Estuary - Zhanhai Li; Jianjun Jia; Yongsheng Wu; Haibo Zong; Guoan Zhang; Ya Ping Wang; Yang Yang; Liang Zhou; Shu Gao (Estuaries and Coasts, 2019)

Wind and sand control by an oasis protective system: a case from the southeastern edge of the Tengger Desert, China - Yun-hu Xie; Xiao-hong Dang; Zhong-ju Meng; Hong-tao Jiang; Xiao-jia Li; Rui-ping Zhou; Dan-dan Zhou; Xiao-xi Liu; Jing Ding; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai; et al. (Journal of Mountain Science, 2019)

Two novel alkaliphiles, Bacillus alkalisoli sp. nov., and Bacillus solitudinis sp. nov., isolated from saline-alkali soil - Guo-Hong Liu; Manik Prabhu Narsing Rao; Zhou-Yan Dong; Jie-Ping Wang; Zheng Chen; Bo Liu; Wen-Jun Li (Extremophiles, 2019)

Upregulation of proBDNF in the Mesenteric Lymph Nodes in Septic Mice - Zhe Wang; Jia-Li Wu; Feng Zhong; Yu Liu; Yun-Qing Yu; Jing-Jing Sun; Shuang Wang; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2019)

Genome-wide association analysis of salt tolerance QTLs with SNP markers in maize (Zea mays L.) - Yonghong Xie; Yan Feng; Qi Chen; Feike Zhao; Shuijuan Zhou; Ying Ding; Xianliang Song; Ping Li; Baohua Wang (Genes & Genomics, 2019)

Application of gradient structure tensor method in CBM fracture identification and sweet spot prediction - Chengqiang Zhao; Yubang Zhou; Yong Li; Ping Zhao; Lingling Huang (Arabian Journal of Geosciences, 2019)

Comparative effects of some extraction solvents on the antimicrobial activity of Eucalyptus camaldulensis leaf, bud, capsule and seed crude extracts - Alyaa Nasr; Xinxin Zhou; Shi-Ping Huang; Yuan Wang; Xiaoning Li; Guo-Ping Zhu (Natural Product Research, 2019)

Vertical Distributions of Suspended Sediment Concentrations in the Turbidity Maximum Zone of the Periodically and Partially Stratified Changjiang Estuary - Zhanhai Li; Jianjun Jia; Yongsheng Wu; Haibo Zong; Guoan Zhang; Yax Ping Wang; Yang Yang; Liang Zhou; Shu Gao (Estuaries and Coasts, 2019)

Identification of cis-regulatory regions responsible for developmental and hormonal regulation of HbHMGS1 in transgenic Arabidopsis thaliana - Xiao-Xiao Gong; Bing-Yu Yan; Yu-Rong Tan; Xuan Gao; Dan Wang; Heng Zhang; Peng Wang; Shuang-Jiang Li; Yi Wang; Lu-Yao Zhou; Jin-Ping Liu (Biotechnology Letters, 2019)

Comparative Transcriptome Analysis Reveals Differentially Expressed Genes and Signaling Pathways Between Male and Female Red-Tail Catfish (Mystus wyckioides) - Jun-Jie Wu; Yu-Lin Zhou; Zhong-Wei Wang; Guang-Hua Li; Fang-Peng Jin; Li-Li Cui; Hai-Tao Gao; Xin-Ping Li; Li Zhou; Jian-Fang Gui (Marine Biotechnology, 2019)

Molecular detection and identification of phytoplasmas in a novel 16SrI subgroup in sunflowers and cocklebur weeds - Lei Zhang; Ping-ping Sun; Qiang Ma; Xiao-zhao Xu; Hong-you Zhou; Zheng-nan Li (Journal of Plant Pathology, 2019)

Correction to: Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2019)

The effects of conditioning startling acoustic stimulation (SAS) on the corticospinal motor system: a SAS–TMS study - Yen-Ting Chen; Shengai Li; Ping Zhou; Sheng Li (Experimental Brain Research, 2019)

New adenine analogues and a pyrrole alkaloid from Selaginella delicatula - Cai-Ping Yao; Zhen-Xing Zou; Yan Zhang; Jing Li; Fei Cheng; Ping-Sheng Xu; Gan Zhou; Xiao-Min Li; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2019)

The role of MAPK signaling pathway in formation of EMT in oral squamous carcinoma cells induced by TNF-α - Xiao-Wei Zhao; Jing-Ping Zhou; Yu-Lan Bi; Jia-Ying Wang; Rui Yu; Chao Deng; Wei-Kang Wang; Xian-Zhen Li; Rui Huang; Jili Zhang; De-Tao Tao (Molecular Biology Reports, 2019)

Combined expression and prognostic significance of PPFIA1 and ALG3 in head and neck squamous cell carcinoma - Hong Zhou; Ting Cao; Wen Ping Li; Gang Wu (Molecular Biology Reports, 2019)

The Tibetan Plateau Surface-Atmosphere Coupling System and Its Weather and Climate Effects: The Third Tibetan Plateau Atmospheric Science Experiment - Ping Zhao; Yueqing Li; Xueliang Guo; Xiangde Xu; Yimin Liu; Shihao Tang; Wenming Xiao; Chunxiang Shi; Yaoming Ma; Xing Yu; Huizhi Liu; La Jia; et al. (Journal of Meteorological Research, 2019)

Characteristics of runoff processes and nitrogen loss via surface flow and interflow from weathered granite slopes of Southeast China - Long-zhou Deng; Kai Fei; Tian-yu Sun; Li-ping Zhang; Xiao-juan Fan; Liang Ni (Journal of Mountain Science, 2019)

Four new phenolic constituents from the rhizomes of Gastrodia elata Blume - Zhi-Wei Wang; Yun Li; Da-Hui Liu; Yan Mu; Hong-Jing Dong; Hong-Lei Zhou; Lan-Ping Guo; Xiao Wang (Natural Product Research, 2019)

Characteristics of single atmospheric particles in a heavily polluted urban area of China: size distributions and mixing states - Li Li; Qiyuan Wang; Xu Zhang; Yuanyuan She; Jiamao Zhou; Yang Chen; Ping Wang; Suixin Liu; Ting Zhang; Wenting Dai; Yongming Han; Junji Cao (Environmental Science and Pollution Research, 2019)

Enhanced water solubility, antioxidant activity, and oral absorption of hesperetin by D-α-tocopheryl polyethylene glycol 1000 succinate and phosphatidylcholine - Su-Fang Gu; Li-Ying Wang; Ying-Jie Tian; Zhu-Xian Zhou; Jian-Bin Tang; Xiang-Rui Liu; Hai-Ping Jiang; You-Qing Shen (Journal of Zhejiang University-SCIENCE B, 2019)

Real-time monitoring and quantification of organic by-products and mechanism study of acetone decomposition in a dielectric barrier discharge reactor - Xueshuang Li; Teng Guo; Zhen Peng; Li Xu; Junguo Dong; Ping Cheng; Zhen Zhou (Environmental Science and Pollution Research, 2019)

Synthesis and biological evaluation of novel SIPI-7623 derivatives as farnesoid X receptor (FXR) antagonists - Si-Yun Nian; Guo-Ping Wang; Zheng-Li Jiang; Ying Xiao; Mo-Han Huang; Yi-Huan Zhou; Xiang-Duan Tan (Molecular Diversity, 2019)

Impact of surfactant and dissolved organic matter on uptake of atrazine in maize and its mobility in soil - Bing Bing Tian; Jing Hua Zhou; Fei Xie; Qian Nan Guo; Ai Ping Zhang; Xin Qiang Wang; Qian Qian Yu; Na Li; Hong Yang (Journal of Soils and Sediments, 2019)

The effects of ethoxyquin and Angelica sinensis extracts on lipid oxidation in fish feeds and growth, digestive and absorptive capacities and antioxidant status in juvenile red carp (Cyprinus carpio var. xingguonensis): a comparative study - HuaTao Li; SiYi Tang; WenHao Du; Jun Jiang; PeiYuan Peng; Ping Yuan; YiHong Liao; Jiao Long; SiShun Zhou (Fish Physiology and Biochemistry, 2019)

HERV-W env regulates calcium influx via activating TRPC3 channel together with depressing DISC1 in human neuroblastoma cells - Yatang Chen; Qiujin Yan; Ping Zhou; Shan Li; Fan Zhu (Journal of NeuroVirology, 2019)

Determining Osteogenic Differentiation Efficacy of Pluripotent Stem Cells by Telomerase Activity - Siqi Zhang; Yuhua Sun; Yi Sui; Yan Li; Zuyuan Luo; Xiao Xu; Ping Zhou; Shicheng Wei (Tissue Engineering and Regenerative Medicine, 2018)

Decreased takeoff performance of aircraft due to climate change - Yuntao Zhou; Nan Zhang; Chao Li; Yong Liu; Ping Huang (Climatic Change, 2018)

Molecular and Functional Characterization of ZmNF-YC14 in Transgenic Arabidopsis - Xiupeng Mei; Ping Li; Lu Wang; Chaoxian Liu; Lian Zhou; Yilin Cai (Journal of Plant Biology, 2018)

Correction to: Molecular characterization of a novel citrivirus from citrus using next‑generation sequencing - Mengji Cao; Ping Li; Song Zhang; Fangyun Yang; Yan Zhou; Xuefeng Wang; Ruhui Li; Zhongan Li (Archives of Virology, 2018)

Molecular characterization of a novel citrivirus from citrus using next-generation sequencing - Mengji Cao; Ping Li; Song Zhang; Fangyun Yang; Yan Zhou; Xuefeng Wang; Ruhui Li; Zhongan Li (Archives of Virology, 2018)

Dietary strategies to reduce the oral bioaccessibility of cadmium and arsenic in rice - Ping Zhuang; Shuo Sun; Feng Su; Feng Li; Xiaofang Zhou; Peng Mao; Yingwen Li; Zhian Li; Chaosheng Zhang (Environmental Science and Pollution Research, 2018)

Thermus sediminis sp. nov., a thiosulfate-oxidizing and arsenate-reducing organism isolated from Little Hot Creek in the Long Valley Caldera, California - En-Min Zhou; Wen-Dong Xian; Chrisabelle C. Mefferd; Scott C. Thomas; Arinola L. Adegboruwa; Nathan Williams; Senthil K. Murugapiran; Jeremy A. Dodsworth; Rakesh Ganji; Meng-Meng Li; Yi-Ping Ding; Lan Liu; et al. (Extremophiles, 2018)

DEM generation using Ziyuan-3 mapping satellite imagery without ground control points - Ping Zhou; Xinming Tang; Li Guo; Xia Wang; Wenfeng Fan (International Journal of Remote Sensing, 2018)

Divergence in larval diapause induction between the rice and water-oat populations of the striped stem borer, Chilo suppressalis (Walker) (Lepidoptera: Crambidae) - Yuan Zhou; Dan Sun; Wei-Li Quan; Nan Ding; Wen Liu; Wei-Hua Ma; Xiao-Ping Wang (Environmental Science and Pollution Research, 2018)

Diversity and abundance of arsenic methylating microorganisms in high arsenic groundwater from Hetao Plain of Inner Mongolia, China - Yanhong Wang; Ping Li; Zhou Jiang; Han Liu; Dazhun Wei; Helin Wang; Yanxin Wang (Ecotoxicology, 2018)

The Protective Role of Selenium in AFB1-Induced Tissue Damage and Cell Cycle Arrest in Chicken’s Bursa of Fabricius - Ping Hu; Zhicai Zuo; Fengyuan Wang; Xi Peng; Ke Guan; Hang Li; Jing Fang; Hengmin Cui; Gang Su; Ping Ouyang; Yi Zhou (Biological Trace Element Research, 2018)

Optimisation of extraction conditions for total saponins from Cynanchum wallichii using response surface methodology and its anti-tumour effects - Kun-jun Mao; Ping Huang; Li- Zhang; Hai-sheng Yu; Xing-zhuo Zhou; Xi-yong Ye (Natural Product Research, 2018)

Low-Cd tomato cultivars (Solanum lycopersicum L.) screened in non-saline soils also accumulated low Cd, Zn, and Cu in heavy metal-polluted saline soils - Zhi-Min Xu; Xiao-Qi Tan; Xiu-Qin Mei; Qu-Sheng Li; Chu Zhou; Li-Li Wang; Han-Jie Ye; Ping Yang (Environmental Science and Pollution Research, 2018)

The complete mitochondrial genome of Pseudocrossocheilus bamaensis (Cypriniformes: Cyprinidae: Labeoninae) - Man Zhang; Bo-wen Liu; Guang-ping Cheng; Li Bian; Qi-jia Zhou; Wei-jie Yan; Wen-hong Li (Conservation Genetics Resources, 2018)

The importance of accounting for imperfect detection when estimating functional and phylogenetic community structure - Xingfeng Si; Marc W. Cadotte; Yuhao Zhao; Haonan Zhou; Di Zeng; Jiaqi Li; Tinghao Jin; Peng Ren; Yanping Wang; Ping Ding; Morgan W. Tingley (Ecology, 2018)
Incorporating imperfect detection when estimating species richness has become commonplace in the past decade. However, the question of how imperfect detection of species affects estimates of functional and phylogenetic community structure remains untested. We used long‐term counts of breeding bird species that were detected at least once on islands in a land‐bridge island system, and employed multi‐species occupancy models to assess the effects of imperfect detection of species on estimates of bird diversity and community structure by incorporating species traits and phylogenies. Our results showed that taxonomic, functional, and phylogenetic diversity were all underestimated significantly as a result of species’ imperfect detection, with taxonomic diversity showing the greatest bias. The functional and phylogenetic structure calculated from observed communities were both more clustered than those from the detection‐corrected communities due to missed distinct species. The discrepancy between observed and estimated diversity differed according to the measure of biodiversity employed. Our study demonstrates the importance of accounting for species’ imperfect detection in biodiversity studies, especially for functional and phylogenetic community ecology, and when attempting to infer community assembly processes. With datasets that allow for detection‐corrected community structure, we can better estimate diversity and infer the underlying mechanisms that structure community assembly, and thus make reliable management decisions for the conservation of biodiversity.

A New Advance Classification Method for Surrounding Rock in Tunnels Based on the Set-Pair Analysis and Tunnel Seismic Prediction System - Lin Bu; Shu-cai Li; Shao-shuai Shi; Xiao-kun Xie; Li-ping Li; Zong-qing Zhou; Zhi-jie Wen (Geotechnical and Geological Engineering, 2018)

Design of a Displacement Monitoring System Based on Optical Grating and Numerical Verification in Geomechanical Model Test of Water Leakage of Tunnel - Shang-qu Sun; Shu-cai Li; Li-ping Li; Shao-shuai Shi; Zong-qing Zhou; Cheng-lu Gao (Geotechnical and Geological Engineering, 2018)

Repaglinide-irbesartan drug interaction: effects of SLCO1B1 polymorphism on repaglinide pharmacokinetics and pharmacodynamics in Chinese population - Qi Pei; Jun-Yan Liu; Ji-Ye Yin; Guo-Ping Yang; Shi-Kun Liu; Yi Zheng; Pan Xie; Cheng-Xian Guo; Mi Luo; Hong-Hao Zhou; Xi Li; Zhao-Qian Liu (European Journal of Clinical Pharmacology, 2018)

Segmentation by domestic visitor motivation: Changbai Mountain Biosphere Reserve, China - Xiao-ping Gu; Bernard J. Lewis; Li-jun Niu; Da-pao Yu; Li Zhou; Wang-ming Zhou; Zhen-cai Gong; Zhi-juan Tai; Li-min Dai (Journal of Mountain Science, 2018)

The role of HMGB1 in BMSC transplantation for treating MODS in rats - Guanghui Xiu; Jie Sun; Xiuling Li; Hua Jin; Yichao Zhu; Xia Zhou; Ping Liu; Xinghua Pan; Jian Li; Bin Ling (Cell and Tissue Research, 2018)

Climatology of tracked persistent maxima of 500-hPa geopotential height - Ping Liu; Yuejian Zhu; Qin Zhang; Jon Gottschalck; Minghua Zhang; Christopher Melhauser; Wei Li; Hong Guan; Xiaqiong Zhou; Dingchen Hou; Malaquias Peña; Guoxiong Wu; et al. (Climate Dynamics, 2018)

Joint structural and physiological control on the interannual variation in productivity in a temperate grassland: A data‐model comparison - Zhongmin Hu; Hao Shi; Kaili Cheng; Ying‐Ping Wang; Shilong Piao; Yue Li; Li Zhang; Jianyang Xia; Lei Zhou; Wenping Yuan; Steve Running; Longhui Li; et al. (Global Change Biology, 2018)
Given the important contributions of semiarid region to global land carbon cycle, accurate modeling of the interannual variability (IAV) of terrestrial gross primary productivity (GPP) is important but remains challenging. By decomposing GPP into leaf area index (LAI) and photosynthesis per leaf area (i.e., GPP_leaf), we investigated the IAV of GPP and the mechanisms responsible in a temperate grassland of northwestern China. We further assessed six ecosystem models for their capabilities in reproducing the observed IAV of GPP in a temperate grassland from 2004 to 2011 in China. We observed that the responses to LAI and GPP_leaf to soil water significantly contributed to IAV of GPP at the grassland ecosystem. Two of six models with prescribed LAI simulated of the observed IAV of GPP quite well, but still underestimated the variance of GPP_leaf, therefore the variance of GPP. In comparison, simulated pattern by the other four models with prognostic LAI differed significantly from the observed IAV of GPP. Only some models with prognostic LAI can capture the observed sharp decline of GPP in drought years. Further analysis indicated that accurately representing the responses of GPP_leaf and leaf stomatal conductance to soil moisture are critical for the models to reproduce the observed IAV of GPP_leaf. Our framework also identified that the contributions of LAI and GPP_leaf to the observed IAV of GPP were relatively independent. We conclude that our framework of decomposing GPP into LAI and GPP_leaf has a significant potential for facilitating future model intercomparison, benchmarking and optimization should be adopted for future data‐model comparisons.

42,573 cases of hepatectomy in China: a multicenter retrospective investigation - Binhao Zhang; Bixiang Zhang; Zhiwei Zhang; Zhiyong Huang; Yifa Chen; Minshan Chen; Ping Bie; Baogang Peng; Liqun Wu; Zhiming Wang; Bo Li; Jia Fan; et al. (Science China Life Sciences, 2018)

Diversity effect of capsaicin on different types of skeletal muscle - Gan Zhou; Lina Wang; Yaqiong Xu; Kelin Yang; Lv Luo; Leshan Wang; Yongxiang Li; Jiawen Wang; Gang Shu; Songbo Wang; Ping Gao; Xiaotong Zhu; et al. (Molecular and Cellular Biochemistry, 2018)

Analysis of DNA Methylation of Gracilariopsis lemaneiformis Under Temperature Stress Using the Methylation Sensitive Amplification Polymorphism (MSAP) Technique - Chong Peng; Zhenghong Sui; Wei Zhou; Yiyi Hu; Ping Mi; Minjie Jiang; Xiaodong Li; Xudong Ruan (Journal of Ocean University of China, 2018)

Wideband dipole logging based on segment linear frequency modulation excitation - Xue-Shen Cao; Hao Chen; Ping Li; Hong-Bin He; Yin-Qiu Zhou; Xiu-Ming Wang (Applied Geophysics, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Effect of UGT2B7 genotypes on plasma concentration of valproic acid: a meta-analysis - Ping Wang; Xiao-Qian Lin; Wen-Ke Cai; Gui-Li Xu; Meng-Di Zhou; Mei Yang; Gong-Hao He (European Journal of Clinical Pharmacology, 2018)

Genome-wide genetic variation and comparison of fruit-associated traits between kumquat (Citrus japonica) and Clementine mandarin (Citrus clementina) - Tian-Jia Liu; Yong-Ping Li; Jing-Jing Zhou; Chun-Gen Hu; Jin-Zhi Zhang (Plant Molecular Biology, 2018)

Hsp90 regulation affects the treatment of glucocorticoid for pancreatitis-induced lung injury - Yan Zhao; Ren-Ping Xiong; Xing Chen; Ping Li; Ya-Lei Ning; Nan Yang; Yan Peng; Yu-Lin Jiang; Yuan-Guo Zhou (Molecular and Cellular Biochemistry, 2018)

Molecular characterization of a novel luteovirus infecting apple by next-generation sequencing - Pan Shen; Xin Tian; Song Zhang; Fang Ren; Ping Li; Yun-qi Yu; Ruhui Li; Changyong Zhou; Mengji Cao (Archives of Virology, 2018)

Temporal patterns and processes of genetic differentiation of the Brachionus calyciflorus (Rotifera) complex in a subtropical shallow lake - Ye Zhang; Ao Zhou; Yi-Long Xi; Qiang Sun; Le-Feng Ning; Ping Xie; Xin-Li Wen; Xian-Ling Xiang (Hydrobiologia, 2018)

Epidemiology and clinical characteristics of human coronaviruses OC43, 229E, NL63, and HKU1: a study of hospitalized children with acute respiratory tract infection in Guangzhou, China - Zhi-Qi Zeng; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Huan-Xi Liang; Mei-Xin Chen; Xiao Li; Zheng-Shi Lin; Wen-Kuan Liu; Rong Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Electrical conductivity of the plagioclase–NaCl–water system and its implication for the high conductivity anomalies in the mid-lower crust of Tibet Plateau - Ping Li; Xinzhuan Guo; Sibo Chen; Chao Wang; Junlong Yang; Xingfan Zhou (Contributions to Mineralogy and Petrology, 2018)

Submarine landslide identified in DLW3102 core of the northern continental slope, South China Sea - Yuanqin Xu; Lejun Liu; Hang Zhou; Baoqi Huang; Ping Li; Xiudong Ma; Feiyin Dong (Journal of Ocean University of China, 2018)

Xylastriasan A, a new cytochalasan from the fungus Xylaria striata - Chuan-Wen Lei; Zhi-Qin Yang; Yan-Ping Zeng; Yun Zhou; Yi Huang; Xin-Sheng He; Guo-You Li; Xiao-Hong Yuan (Natural Product Research, 2018)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

RETRACTED ARTICLE: Downregulation of the Long Non-Coding RNA Meg3 Promotes Angiogenesis After Ischemic Brain Injury by Activating Notch Signaling - Juan Liu; Qing Li; Kun-shan Zhang; Bin Hu; Xin Niu; Shu-min Zhou; Si-guang Li; Yu-ping Luo; Yang Wang; Zhi-feng Deng (Molecular Neurobiology, 2017)
Angiogenesis after ischemic brain injury contributes to the restoration of blood supply in the ischemic zone. Strategies to improve angiogenesis may facilitate the function recovery after stroke. Recent researches have demonstrated that dysfunction of long non-coding RNAs are associated with angiogenesis. We have previously reported that long non-coding RNAs (lncRNAs) are aberrantly expressed in ischemic stroke. However, little is known about long non-coding RNAs and theirs role in angiogenesis after stroke. In this study, we identified a rat lncRNAs, Meg3, and found that Meg3 was significantly decreased after ischemic stroke. Overexpression of Meg3 suppressed functional recovery and decreased capillary density after ischemic stroke. Downregulation of Meg3 ameliorated brain lesion and increased angiogenesis after ischemic stroke. Silencing of Meg3 resulted in a proangiogenic effect evidenced by increased endothelial cell migration, proliferation, sprouting, and tube formation. Mechanistically, we showed that Meg3 negatively regulated notch pathway both in vivo and in vitro. Inhibition of notch signaling in endothelial cells reversed the proangiogenic effect induced by Meg3 downregulation. This study revealed the function of Meg3 in ischemic stroke and elucidated its mechanism in angiogenesis after ischemic stroke.

Morphological and molecular divergence of Rhipicephalus turanicus tick from Albania and China - Hong-Yu Li; Shan-Shan Zhao; Sándor Hornok; Róbert Farkas; Li-Ping Guo; Chuang-Fu Chen; Ren-Fu Shao; Ji-Zhou Lv; Yuan-Zhi Wang (Experimental and Applied Acarology, 2017)

Rapid response to changing environments during biological invasions: DNA methylation perspectives - Xuena Huang; Shiguo Li; Ping Ni; Yangchun Gao; Bei Jiang; Zunchun Zhou; Aibin Zhan (Molecular Ecology, 2017)
Dissecting complex interactions between species and their environments has long been a research hot spot in the fields of ecology and evolutionary biology. The well‐recognized Darwinian evolution has well‐explained long‐term adaptation scenarios; however, “rapid” processes of biological responses to environmental changes remain largely unexplored, particularly molecular mechanisms such as DNA methylation that have recently been proposed to play crucial roles in rapid environmental adaptation. Invasive species, which have capacities to successfully survive rapidly changing environments during biological invasions, provide great opportunities to study molecular mechanisms of rapid environmental adaptation. Here, we used the methylation‐sensitive amplified polymorphism (MSAP) technique in an invasive model ascidian, Ciona savignyi , to investigate how species interact with rapidly changing environments at the whole‐genome level. We detected quite rapid DNA methylation response: significant changes of DNA methylation frequency and epigenetic differentiation between treatment and control groups occurred only after 1 hr of high‐temperature exposure or after 3 hr of low‐salinity challenge. In addition, we detected time‐dependent hemimethylation changes and increased intragroup epigenetic divergence induced by environmental stresses. Interestingly, we found evidence of DNA methylation resilience, as most stress‐induced DNA methylation variation maintained shortly (~48 hr) and quickly returned back to the control levels. Our findings clearly showed that invasive species could rapidly respond to acute environmental changes through DNA methylation modifications, and rapid environmental changes left significant epigenetic signatures at the whole‐genome level. All these results provide fundamental background to deeply investigate the contribution of DNA methylation mechanisms to rapid contemporary environmental adaptation.

Age, nature, and origin of early cretaceous plutons in the Dabie Mo Mineralization belt: the Xinxian example - Qing-quan Liu; Yu Zhang; Yong-jun Shao; Ke-Ping Zhou; Yong-feng Li; Zheng-zhuan Luo (International Geology Review, 2017)

Comparison of infrared canopy temperature in a rubber plantation and tropical rain forest - Qing-Hai Song; Yun Deng; Yi -Ping Zhang; Xiao-Bao Deng; You-Xing Lin; Li-Guo Zhou; Xue-Hai Fei; Li-Qing Sha; Yun-Tong Liu; Wen-Jun Zhou; Jin-Bo Gao (International Journal of Biometeorology, 2017)

Total and settling velocity-fractionated pollution potential of sewer sediments in Jiaxing, China - Yongchao Zhou; Ping Zhang; Yiping Zhang; Jin Li; Tuqiao Zhang; Tingchao Yu (Environmental Science and Pollution Research, 2017)

Long-term grazing affects relationships between nitrogen form uptake and biomass of alpine meadow plants - Yu Guo; Li-Ping Liu; Li-Li Zheng; Fei-Hai Yu; Ming-Hua Song; Xian-Zhou Zhang (Plant Ecology, 2017)

The biogeographical distribution of tree species-abundance and its relation to climatic factors in mass islands - Xiaoming Li; Chengzhen Wu; Wu Gu; Ran Ye; Haibo Zhang; Ping Qi; Shengqiang Wang; Siying Zhou; Yongjie Wei; Yanhong Cai (Acta Oceanologica Sinica, 2017)

Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2017)
Cystatin SN (CST1) belongs to the type 2 cystatin (CST) superfamily, which restricts the proteolytic activities of cysteine proteases. CST1 has been recently considered to be involved in the development of several human cancers. However, the prognostic significance and function of CST1 in breast cancer remains unknown. In the current study, we found that CST1 was generally upregulated in breast cancer at both mRNA and protein level. Furthermore, overall survival (OS) and disease-free survival (DFS) in the low CST1 expression subgroup were significantly superior to the high CST1 expression subgroup (OS, p < 0.001; DFS, p < 0.001), which indicated that CST1 expression level was closely correlated to the survival risk of these patients. Univariate and multivariate analyses demonstrated that CST1 expression was an independent prognostic factor, the same as ER status and nodal status. Next, CST1 overexpression promoted breast cancer cell proliferation, clonogenicity, migration, and invasion abilities. By contrast, knockdown of CST1 attenuated these malignant characteristics in breast cancer cells. Collectively, our study indicates that CST1 cannot only serve as a significant prognostic indicator but also as a potential therapeutic target for breast cancer. Key messages High CST1 expression is negatively correlated with survival of breast cancer patients. CST1 promotes cell proliferation, clone formation, and metastasis in breast cancer cells. CST1 is a novel potential prognostic biomarker and therapeutic target for breast cancer.

TGF-β1-miR-200a-PTEN induces epithelial–mesenchymal transition and fibrosis of pancreatic stellate cells - Min Xu; Guoying Wang; Hailang Zhou; Jing Cai; Ping Li; Meng Zhou; Ying Lu; Xiaomeng Jiang; Hongmei Huang; Youli Zhang; Aihua Gong (Molecular and Cellular Biochemistry, 2017)

Response of linear and cyclic electron flux to moderate high temperature and high light stress in tomato - Tao Lu; Jie-wei Shi; Zhou-ping Sun; Ming-fang Qi; Yu-feng Liu; Tian-lai Li (Journal of Zhejiang University-SCIENCE B, 2017)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

Identification of manganese-toxicity-responsive genes in roots of two citrus species differing in manganese tolerance using cDNA-AFLP - Chen-Ping Zhou; Chun-Ping Li; Wei-Wei Liang; Peng Guo; Lin-Tong Yang; Li-Song Chen (Trees, 2017)

Heavy metal-polluted aerosols collected at a rural site, Northwest China - Xiaoyu Zhang; Zhongqin Li; Nozomu Takeuchi; Feiteng Wang; Shengjie Wang; Xiaoni You; Ping Zhou (Journal of Earth Science, 2017)

The Adsorption Behavior of Pb2+ and Cd2+ in the Treated Black Soils with Different Freeze-Thaw Frequencies - Xu Wang; Yueming Li; Na Mao; Yanqiu Zhou; Ping Guo (Water, Air, & Soil Pollution, 2017)

A Point Mutation in SCN1A 5′ Genomic Region Decreases the Promoter Activity and Is Associated with Mild Epilepsy and Seizure Aggravation Induced by Antiepileptic Drug - Qu-Wen Gao; Li-Dong Hua; Jie Wang; Cui-Xia Fan; Wei-Yi Deng; Bin Li; Wen-Jun Bian; Chuan-Xing Shao; Na He; Peng Zhou; Wei-Ping Liao; Yi-Wu Shi (Molecular Neurobiology, 2017)

Antidepressant-like effects of saringosterol, a sterol from Sargassum fusiforme by performing in vivo behavioral tests - Hong-Guo Jin; Min Zhou; Qing-Hao Jin; Bing-Yu Liu; Li-Ping Guan (Medicinal Chemistry Research, 2017)

Genetic variation and population structure of Cucumber green mottle mosaic virus - Li-xia Rao; Yushuang Guo; Li-li Zhang; Xue-ping Zhou; Jian Hong; Jian-xiang Wu (Archives of Virology, 2017)

Cd Content in Sugarcane and Its Relationship with Soil Factors - Hui-Ping Ou; Liu-Qiang Zhou; Xi-Hui Liu; Jin-Sheng Huang; Yan Zeng; Ru-Lin Xie; Xiao-Hui Zhu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2017)

Transient Receptor Potential-canonical 1 is Essential for Environmental Enrichment-Induced Cognitive Enhancement and Neurogenesis - Lai-Ling Du; Lin Wang; Xi-Fei Yang; Ping Wang; Xiao-Hong Li; Da-Min Chai; Bing-Jin Liu; Yun Cao; Wei-Qi Xu; Rong Liu; Qing Tian; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2017)

The Brain NO Levels and NOS Activities Ascended in the Early and Middle Stages and Descended in the Terminal Stage in Scrapie-Infected Animal Models - Li-Na Chen; Jing Sun; Xiao-Dong Yang; Kang Xiao; Yan Lv; Bao-Yun Zhang; Wei Zhou; Cao Chen; Chen Gao; Qi Shi; Xiao-Ping Dong (Molecular Neurobiology, 2017)

Clogging development and hydraulic performance of the horizontal subsurface flow stormwater constructed wetlands: a laboratory study - Ping Tang; Bohai Yu; Yongchao Zhou; Yiping Zhang; Jin Li (Environmental Science and Pollution Research, 2017)

Novel compound heterozygous mutations in ZAP70 in a Chinese patient with leaky severe combined immunodeficiency disorder - Qing Liu; Yan-Ping Wang; Qiao Liu; Qin Zhao; Xue-Mei Chen; Xiu-Hong Xue; Li-Na Zhou; Yuan Ding; Xue-Mei Tang; Xiao-Dong Zhao; Zhi-Yong Zhang (Immunogenetics, 2017)

The critical role of ABCG1 and PPARγ/LXRα signaling in TLR4 mediates inflammatory responses and lipid accumulation in vascular smooth muscle cells - Xiaojie Cao; Lili Zhang; Chunhai Chen; Qingsong Wang; Lu Guo; Qinlong Ma; Ping Deng; Gang Zhu; Binghu Li; Yan Pi; Chunyan Long; Lei Zhang; et al. (Cell and Tissue Research, 2017)

Genetic characterization of H9N2 avian influenza virus in plateau pikas in the Qinghai Lake region of China - Yan Yan; Jin-Yan Gu; Zhuang-Chuan Yuan; Xin-Yu Chen; Zeng-Kui Li; Jing Lei; Bo-li Hu; Li-Ping Yan; Gang Xing; Min Liao; Ji-Yong Zhou (Archives of Virology, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Morphogenesis and Gene Mapping of deformed interior floral organ 1 (difo1), a Novel Mutant Associated with Floral Organ Development in Rice - Lianping P. Sun; Yingxin X. Zhang; Peipei P. Zhang; Zhengfu F. Yang; Xiaoxiao X. Zhou; Dandan D. Xuan; Md Habibur H. Rahman; Zihe H. Li; Weixun X. Wu; Xiaodeng D. Zhan; Xihong H. Shen; Ping Yu; et al. (Plant Molecular Biology Reporter, 2017)

A preliminary study of the role of extracellular -5′- nucleotidase in breast cancer stem cells and epithelial-mesenchymal transition - Jiangang Yu; Xiaohong Liao; Luying Li; Lei Lv; Xiuling Zhi; Jerry Yu; Ping Zhou (In Vitro Cellular & Developmental Biology - Animal, 2017)

Thermal effects on development and adult longevity of endoparasitoid Chelonus murakatae Munakata (Hymenoptera: Braconidae) - Sundas Rana Qureshi; Wei-Li Quan; Rui-Qi Zhou; Fen Zhu; Xiao-Ping Wang (Environmental Science and Pollution Research, 2017)

Analgesic Effects of Danggui-Shaoyao-San on Various “Phenotypes” of Nociception and Inflammation in a Formalin Pain Model - Jun-Bin Yin; Ke-Cheng Zhou; Huang-Hui Wu; Wei Hu; Tan Ding; Ting Zhang; Li-Ying Wang; Jun-Ping Kou; Alan David Kaye; Wen Wang (Molecular Neurobiology, 2016)

Astrocytes Regulate Angiogenesis Through the Jagged1-Mediated Notch1 Pathway After Status Epilepticus - Xuan Zhai; Ping Liang; Yingliang Li; Lusheng Li; Yudong Zhou; Xuanxuan Wu; Jinmu Deng; Li Jiang (Molecular Neurobiology, 2016)

Changes in subcellular distribution and antioxidant compounds involved in Pb accumulation and detoxification in Neyraudia reynaudiana - Chuifan Zhou; Meiying Huang; Ying Li; Jiewen Luo; Li ping Cai (Environmental Science and Pollution Research, 2016)

RhoB/ROCK mediates oxygen–glucose deprivation-stimulated syncytiotrophoblast microparticle shedding in preeclampsia - Jian Han; Bo-ping Yang; Yi-lin Li; Hong-mei Li; Xiu-hui Zheng; Li-li Yu; Qiong Zhang; Ying-ru Zheng; Ping Yi; Li Li; Jian-xin Guo; Yuan-guo Zhou (Cell and Tissue Research, 2016)

One new berberine from the branches and leaves of Polyalthia obliqua Hook.f. & Thomson - Li-Jun Wu; Cai-Juan Zheng; Liu-Kai Wang; Chang-Ri Han; Xiao-Ping Song; Guang-Ying Chen; Xue-ming Zhou; Shou-yuan Wu; Xiao-bao Li; Meng Bai; Chun-xin Liu; Jun Yao (Natural Product Research, 2016)

Proteomic Analyses for the Global S-Nitrosylated Proteins in the Brain Tissues of Different Human Prion Diseases - Li-Na Chen; Qi Shi; Bao-Yun Zhang; Xiao-Mei Zhang; Jing Wang; Kang Xiao; Yan Lv; Jing Sun; Xiao-Dong Yang; Cao Chen; Wei Zhou; Jun Han; et al. (Molecular Neurobiology, 2016)

Synergistic antitumor activity of triple-regulated oncolytic adenovirus with VSTM1 and daunorubicin in leukemic cells - Jiao Zhou; Qiu-Mei Yao; Jin-Lan Li; Yan Chang; Ting Li; Wen-Ling Han; Hong-Ping Wu; Lin-Fang Li; Qi-Jun Qian; Guo-Rui Ruan (Apoptosis, 2016)

Ancient DNA analysis of Panicum miliaceum (broomcorn millet) from a Bronze Age cemetery in Xinjiang, China - Chunxiang Li; Yu Dong; Minxuan Liu; Ping Lu; Wenying Li; Yingnan Wang; Xiyan Cui; Hui Zhou; Yue Xu (Vegetation History and Archaeobotany, 2016)

How Much Surface Coating of Hydrophobic Azithromycin Is Sufficient to Prevent Moisture-Induced Decrease in Aerosolisation of Hygroscopic Amorphous Colistin Powder? - Qi Zhou; Zhi Hui Loh; Jiaqi Yu; Si-ping Sun; Thomas Gengenbach; John A. Denman; Jian Li; Hak-Kim Chan (The AAPS Journal, 2016)

Protective Effects of Chinese Herbal Medicine Rhizoma drynariae in Rats After Traumatic Brain Injury and Identification of Active Compound - Wenzhu Wang; Haigang Li; Jintao Yu; Michael Hong; Jing Zhou; Lin Zhu; Yang Wang; Min Luo; Zian Xia; Zeng-Jin Yang; Tao Tang; Ping Ren; et al. (Molecular Neurobiology, 2016)

Se Enhances MLCK Activation by Regulating Selenoprotein T (SelT) in the Gastric Smooth Muscle of Rats - Jia-ping Li; Jing-xuan Zhou; Qi Wang; Gao-qin Gu; Shi-jin Yang; Cheng-ye Li; Chang-wei Qiu; Gan-zhen Deng; Meng-yao Guo (Biological Trace Element Research, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Genetic Diversity Analysis of Sugarcane Germplasm Based on Fluorescence-Labeled Simple Sequence Repeat Markers and a Capillary Electrophoresis-based Genotyping Platform - Qian You; Yong-Bao Pan; Li-Ping Xu; Shi-Wu Gao; Qin-Nan Wang; Ya-Chun Su; Yong-Qing Yang; Qi-Bin Wu; Ding-Gang Zhou; You-Xiong Que (Sugar Tech, 2016)

Acne-Like Subcutaneous Phaeohyphomycosis Caused by Cladosporium cladosporioides: A Rare Case Report and Review of Published Literatures - Ya Bin Zhou; Ping Chen; Ting Ting Sun; Xing Jia Wang; Dong Ming Li (Mycopathologia, 2016)

The Levels of Tau Isoforms Containing Exon-2 and Exon-10 Segments Increased in the Cerebrospinal Fluids of the Patients with Sporadic Creutzfeldt-Jakob Disease - Cao Chen; Wei Zhou; Yan Lv; Qi Shi; Jing Wang; Kang Xiao; Li-Na Chen; Bao-Yun Zhang; Xiao-Ping Dong (Molecular Neurobiology, 2016)

Male-Biased Capture in Light Traps in Spodoptera exigua (Lepidoptera: Noctuidae): Results from the Studies of Reproductive Activities - Wen-Jie Cheng; Xia-Lin Zheng; Pan Wang; Li-Lin Zhou; Sheng-Yun Si; Xiao-Ping Wang (Journal of Insect Behavior, 2016)

Delta-like 1 homolog in Capra hircus: molecular characteristics, expression pattern and phylogeny - Jiangtao Hu; Wei Zhao; Siyuan Zhan; Ping Xiao; Jingxuan Zhou; Linjie Wang; Li Li; Hongping Zhang; Lili Niu; Tao Zhong (Molecular Biology Reports, 2016)

Inhibitory effect of Gardenblue blueberry (Vaccinium ashei Reade) anthocyanin extracts on lipopolysaccharide-stimulated inflammatory response in RAW 264.7 cells - Wei Xu; Qing Zhou; Yong Yao; Xing Li; Jiu-liang Zhang; Guan-hua Su; Ai-ping Deng (Journal of Zhejiang University-SCIENCE B, 2016)

Exogenous Diethyl Aminoethyl Hexanoate, a Plant Growth Regulator, Highly Improved the Salinity Tolerance of Important Medicinal Plant Cassia obtusifolia L. - Chunping Zhang; Ping He; Yicun Li; Yan Li; Huankai Yao; Jingyu Duan; Shijun Hu; Hui Zhou; Shuo Li (Journal of Plant Growth Regulation, 2016)

Study on Longitudinal Deformation Profile of Rock Mass in a Subsea Tunnel - Shu-Guang Song; Shu-Cai Li; Li-Ping Li; Qian-Qing Zhang; Kai Wang; Yi Zhou; Hong-Liang Liu (Marine Georesources & Geotechnology, 2016)

Expression, purification and characterization of a thermostable leucine dehydrogenase from the halophilic thermophile Laceyella sacchari - Wenjun Zhu; Yan Li; Honghua Jia; Ping Wei; Hua Zhou; Min Jiang (Biotechnology Letters, 2016)

PD-1/PD-L1 signal pathway participates in HCV F protein-induced T cell dysfunction in chronic HCV infection - Wen Xiao; Long Feng Jiang; Xiao Zhao Deng; Dan Yan Zhu; Jia Ping Pei; Mao Lei Xu; Bing Jun Li; Chang Jun Wang; Jing Hai Zhang; Qi Zhang; Zhen Xian Zhou; Wei Liang Ding; et al. (Immunologic Research, 2016)

On the variability of near-bed floc size due to complex interactions between turbulence, SSC, settling velocity, effective density and the fractal dimension of flocs - Yang Yang; Ya Ping Wang; Chunyan Li; Shu Gao; Benwei Shi; Liang Zhou; Dandan Wang; Gaocong Li; Chen Dai (Geo-Marine Letters, 2016)

Fine genetic mapping of spot blotch resistance gene Sb3 in wheat (Triticum aestivum) - Ping Lu; Yong Liang; Delin Li; Zhengzhong Wang; Wenbin Li; Guoxin Wang; Yong Wang; Shenghui Zhou; Qiuhong Wu; Jingzhong Xie; Deyun Zhang; Yongxing Chen; et al. (Theoretical and Applied Genetics, 2016)

Effects of Surface Composition on the Aerosolisation and Dissolution of Inhaled Antibiotic Combination Powders Consisting of Colistin and Rifampicin - Wenbo Wang; Qi Tony Zhou; Si-Ping Sun; John A. Denman; Thomas R. Gengenbach; Nicolas Barraud; Scott A. Rice; Jian Li; Mingshi Yang; Hak-Kim Chan (The AAPS Journal, 2016)

Sediment resuspension in tidally dominated coastal environments: new insights into the threshold for initial movement - Yang Yang; Ya Ping Wang; Shu Gao; Xiao Hua Wang; Ben Wei Shi; Liang Zhou; Dan Dan Wang; Chen Dai; Gao Cong Li (Ocean Dynamics, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Single-nucleotide polymorphisms in the PLA2R1 gene are associated with systemic lupus erythematosus and lupus nephritis in a Chinese Han population - Yuan Li; Aihong Zhou; Guanting Lv; Ping Li; Si Chen; Jing Li; Xiaoting Wen; Ziyan Wu; Shulan Zhang; Jibo Wang; Fengchun Zhang; Yongzhe Li (Immunologic Research, 2016)

Differential effects of general anesthetics on anxiety-like behavior in formalin-induced pain: involvement of ERK activation in the anterior cingulate cortex - Cong Luo; Yan-Ling Zhang; Wei Luo; Fiona H Zhou; Chang-Qi Li; Jun-Mei Xu; Ru-Ping Dai (Psychopharmacology, 2015)

Overexpression of a phospholipase Dα gene from Ammopiptanthus nanus enhances salt tolerance of phospholipase Dα1-deficient Arabidopsis mutant - Hao Qiang Yu; Tai Ming Yong; Hong Jie Li; Yan Ping Liu; Shu Feng Zhou; Feng Ling Fu; Wan Chen Li (Planta, 2015)

Total glycosides of Yupingfeng protects against bleomycin-induced pulmonary fibrosis in rats associated with reduced high mobility group box 1 activation and epithelial–mesenchymal transition - Wenhui Cui; Liucheng Li; Delin Li; Xiaoting Mo; Wencheng Zhou; Zhihui Zhang; Liang Xu; Ping Zhao; Lianwen Qi; Ping Li; Jian Gao (Inflammation Research, 2015)

The roles of methanogens and acetogens in dechlorination of trichloroethene using different electron donors - Li-Lian Wen; Yin Zhang; Ya-Wei Pan; Wen-Qi Wu; Shao-Hua Meng; Chen Zhou; Youneng Tang; Ping Zheng; He-Ping Zhao (Environmental Science and Pollution Research, 2015)

The role of KCa3.1 channels in cardiac fibrosis induced by pressure overload in rats - Li-Mei Zhao; Li-Ping Wang; Hui-Fang Wang; Xiao-Zhen Ma; Dang-Xia Zhou; Xiu-Ling Deng (Pflügers Archiv - European Journal of Physiology, 2015)

Travel motivation of domestic tourists to the Changbai Mountain Biosphere Reserve in Northeastern China: A comparative study - Xiao-ping Gu; Bernard J. Lewis; Yan-quan Li; Da-pao Yu; Li Zhou; Wang-ming Zhou; Sheng-nan Wu; Li-min Dai (Journal of Mountain Science, 2015)

Effects of pre-harvest chemical application on rice desiccation and seed quality - Yong-qi He; Jin-ping Cheng; Liang-feng Liu; Xiao-dan Li; Bin Yang; Hong-sheng Zhang; Zhou-fei Wang (Journal of Zhejiang University-SCIENCE B, 2015)

Grass-legume mixtures impact soil N, species recruitment, and productivity in temperate steppe grassland - Qiang Li; Yantao Song; Guangdi Li; Pujia Yu; Ping Wang; Daowei Zhou (Plant and Soil, 2015)

Lipophilic constituents from two processed products and three different parts of Changium smyrnioides Wolff. - Gang-Gang Bai; Fei Yuan; Fu-Qiang Li; Kun-Jun Mao; Ping Zhou; Jian-Wei Chen; Xiang Li (Natural Product Research, 2015)

Identification of volatile and softening-related genes using digital gene expression profiles in melting peach - Xiong-wei Li; Jun Jiang; Li-ping Zhang; Yi Yu; Zheng-wen Ye; Xiu-min Wang; Jing-yi Zhou; Ming-liang Chai; Hui-qin Zhang; Pere Arús; Hui-juan Jia; Zhong-shan Gao (Tree Genetics & Genomes, 2015)

Activation of VEGF/Flk-1-ERK Pathway Induced Blood–Brain Barrier Injury After Microwave Exposure - Li-Feng Wang; Xiang Li; Ya-Bing Gao; Shui-Ming Wang; Li Zhao; Ji Dong; Bin-Wei Yao; Xin-Ping Xu; Gong-Min Chang; Hong-Mei Zhou; Xiang-Jun Hu; Rui-Yun Peng (Molecular Neurobiology, 2015)

Cloning and functional validation of molybdenum cofactor sulfurase gene from Ammopiptanthus nanus - Hao Qiang Yu; Yuan Yuan Zhang; Tai Ming Yong; Yan Ping Liu; Shu Feng Zhou; Feng Ling Fu; Wan Chen Li (Plant Cell Reports, 2015)

All-trans retinoic acid up-regulates the human CD2AP gene expression through Sp1/Sp3 binding sites - Hua-Guo Xu; Rui Jin; Shan Gao; Wei Ren; Li Zou; Lifei Liu; Guo-Ping Zhou (Immunologic Research, 2015)

Potent CDC25B and PTP1B phosphatase inhibitors: 2′,4′,6′-trihydroxylchalcone derivatives - Shui-Lian Zhao; Zhou Peng; Xing-Hua Zhen; Hong-Guo Jin; Yan Han; You-Le Qu; Li-Ping Guan (Medicinal Chemistry Research, 2015)

Heterologous biosynthesis of costunolide in Escherichia coli and yield improvement - Hua Yin; Yi-bin Zhuang; E-e Li; Hui-ping Bi; Wei Zhou; Tao Liu (Biotechnology Letters, 2015)

A numerical study on the density driven circulation in the Yellow Sea Cold Water Mass - Chunyan Zhou; Ping Dong; Guangxue Li (Journal of Ocean University of China, 2015)

Establishment and maintenance of a standardized glioma tissue bank: Huashan experience - Abudumijiti Aibaidula; Jun-feng Lu; Jin-song Wu; He-jian Zou; Hong Chen; Yu-qian Wang; Zhi-yong Qin; Yu Yao; Ye Gong; Xiao-ming Che; Ping Zhong; Shi-qi Li; et al. (Cell and Tissue Banking, 2015)

Erratum to: Elevated Cerebral Cortical CD24 Levels in Patients and Mice with Traumatic Brain Injury: A Potential Negative Role in Nuclear Factor Kappa B/Inflammatory Factor Pathway - Wei Li; Hai-Ping Ling; Wan-Chun You; Huan-Dong Liu; Qing Sun; Meng-Liang Zhou; Wei Shen; Jin-Bing Zhao; Lin Zhu; Chun-Hua Hang (Molecular Neurobiology, 2015)

Phylogenetic and recombination analysis of rice black-streaked dwarf virus segment 9 in China - Yu Zhou; Jian-Feng Weng; Yan-Ping Chen; Chang-Lin Liu; Xiao-Hua Han; Zhuan-Fang Hao; Ming-Shun Li; Hong-Jun Yong; De-Gui Zhang; Shi-Huang Zhang; Xin-Hai Li (Archives of Virology, 2015)

Effect of dietary Chinese tea on growth performance, disease resistance and muscle fatty acid profile of channel catfish (Ictalurus punctatus) - Yao-bei-ping Zhang; Yi-bin Zhou; Ba-yi Sang; Xiao-chun Wan; Yan-ou Yang; Jian-li Zhang; Thomas L. Welker; Keshun Liu (Aquaculture International, 2015)

The roles of IL-2 and IL-10 enhance anti-CD45RBmAb immune inhibition in allograft skin - Wei-Jian Guo; Hui Qi; Chun-Yan Deng; Han-Xin Zhou; Shao-Ping Deng; Fu-Rong Li (Immunologic Research, 2015)

Characteristics of water isotopes and hydrograph separation during the spring flood period in Yushugou River basin, Eastern Tianshans, China - Xiaoyan Wang; Zhongqin Li; Edwards Ross; Ruozihan Tayier; Ping Zhou (Journal of Earth System Science, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Introducing a salt bridge into the lipase of Stenotrophomonas maltophilia results in a very large increase in thermal stability - Jian-Ping Wu; Mu Li; Yong Zhou; Li-Rong Yang; Gang Xu (Biotechnology Letters, 2015)

Paleoclimate modeling in China: A review - Dabang Jiang; Ge Yu; Ping Zhao; Xing Chen; Jian Liu; Xiaodong Liu; Shaowu Wang; Zhongshi Zhang; Yongqiang Yu; Yuefeng Li; Liya Jin; Ying Xu; et al. (Advances in Atmospheric Sciences, 2015)

Contamination of commercially available seafood by key diarrhetic shellfish poisons along the coast of China - Chao Lin; Zeng-Shan Liu; Cai-Yun Tan; Yi-Ping Guo; Lin Li; Hong-Lin Ren; Yan-Song Li; Pan Hu; Sheng Gong; Yu Zhou; Shi-Ying Lu (Environmental Science and Pollution Research, 2015)

Gelsolin: Role of a Functional Protein in Mitigating Radiation Injury - Mingjuan Li; Fengmei Cui; Ying Cheng; Ling Han; Jia Wang; Ding Sun; Yu-long Liu; Ping-kun Zhou; Rui Min (Cell Biochemistry and Biophysics, 2015)

Free radical-scavenging activities of oligomeric proanthocyanidin from Rhodiola rosea L. and its antioxidant effects in vivo - Qian Zhou; Zhi-Ping Yin; Lei Ma; Wen Zhao; Hong-Wei Hao; Hui-Ling Li (Natural Product Research, 2014)

Association of IL-18 promoter gene polymorphisms with rheumatoid arthritis: a meta-analysis - Li-Ping Cai; Li-Juan Zhou; Shun-Yu Lu; Ying-E Liang; Xiao-Ying Chen; Lin Liu; Jun Lin (Molecular Biology Reports, 2014)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

Gene expression pattern of insect fat body cells from in vitro challenge to cell line establishment - Huan Zhang; Qian Meng; Ping Tang; Xuan Li; Wei Zhu; Guiling Zhou; Ruihao Shu; Jihong Zhang; Qilian Qin (In Vitro Cellular & Developmental Biology - Animal, 2014)

Vertical distribution of bacterial communities in high arsenic sediments of Hetao Plain, Inner Mongolia - Yanhong Wang; Ping Li; Dawei Jiang; Bing Li; Xinyue Dai; Zhou Jiang; Yanxin Wang (Ecotoxicology, 2014)

Comparative survey of bacterial and archaeal communities in high arsenic shallow aquifers using 454 pyrosequencing and traditional methods - Ping Li; Dawei Jiang; Bing Li; Xinyue Dai; Yanhong Wang; Zhou Jiang; Yanxin Wang (Ecotoxicology, 2014)

RS analysis of glaciers change in the Heihe River Basin, Northwest China, during the recent decades - Baojuan Huai; Zhongqin Li; Shengjie Wang; Meiping Sun; Ping Zhou; Yan Xiao (Journal of Geographical Sciences, 2014)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

Effect of two-linked mutations of the FMO3 gene on itopride metabolism in Chinese healthy volunteers - Li-Ping Zhou; Zhi-Rong Tan; Hao Chen; Dong Guo; Yao Chen; Wei-Hua Huang; Lian-Sheng Wang; Guo-Gang Zhang (European Journal of Clinical Pharmacology, 2014)

Epidemiological situation and genetic analysis of H7N9 influenza viruses in Shanghai in 2013 - Fei-Fei Ge; Hou-Bin Ju; De-Quan Yang; Jian Liu; Jian Wang; Jun Lu; Xin Li; Wei-Yi Zhang; Pei-Hong Liu; Jin-Ping Zhou (Archives of Virology, 2014)

Analysis of the ground settlement control of a large span metro station in Dalian city using the Centre Drift Method - Xin-Bo Ji; Wen Zhao; Shen-Gang Li; Yong-Wei Zhou; Yong-Ping Guan (European Journal of Environmental and Civil Engineering, 2014)

Soil bacterial communities of different natural forest types in Northeast China - Hui Li; Dandan Ye; Xugao Wang; Matthew Lee Settles; Jun Wang; Zhanqing Hao; Lisha Zhou; Ping Dong; Yong Jiang; Zhanshan Ma (Plant and Soil, 2014)

IL-17A promotes ventricular remodeling after myocardial infarction - Su-Feng Zhou; Jing Yuan; Meng-Yang Liao; Ni Xia; Ting-Ting Tang; Jing-Jing Li; Jiao Jiao; Wen-Yong Dong; Shao-Fang Nie; Zheng-Feng Zhu; Wen-Cai Zhang; Bing-Jie Lv; et al. (Journal of Molecular Medicine, 2014)

Assessment of chlorpyrifos exposure and absorbed daily doses among infants living in an agricultural area of the Province of Jiangsu, China - Ping Liu; Chun-hua Wu; Xiu-li Chang; Xiao-juan Qi; Ming-lan Zheng; Zhi-jun Zhou (International Archives of Occupational and Environmental Health, 2014)

Bio-beads with immobilized anaerobic bacteria, zero-valent iron, and active carbon for the removal of trichloroethane from groundwater - Ya-Zhen Zhou; Jie Yang; Xiao-Li Wang; Yue-Qing Pan; Hui Li; Dong Zhou; Yong-Di Liu; Ping Wang; Ji-Dong Gu; Qiang Lu; Yue-Feng Qiu; Kuang-Fei Lin (Environmental Science and Pollution Research, 2014)

Recycling of sediment into the mantle source of K-rich mafic rocks: Sr–Nd–Hf–O isotopic evidence from the Fushui complex in the Qinling orogen - Hao Wang; Yuan-Bao Wu; Chao-Ran Li; Tian-Yu Zhao; Zheng-Wei Qin; Liu-Qin Zhu; Shan Gao; Jian-Ping Zheng; Xiao-Ming Liu; Lian Zhou; Yang Zhang; Sai-Hong Yang (Contributions to Mineralogy and Petrology, 2014)

The Melanogenesis-Inhibitory Effect and the Percutaneous Formulation of Ginsenoside Rb1 - Lin Wang; Ai-Ping Lu; Zhi-Ling Yu; Ricky N. S. Wong; Zhao-Xiang Bian; Hoi-Hin Kwok; Patrick Ying-Kit Yue; Li-Min Zhou; HuBiao Chen; Min Xu; Zhijun Yang (AAPS PharmSciTech, 2014)

The Effects of Hispidulin on Bupivacaine-Induced Neurotoxicity: Role of AMPK Signaling Pathway - Xinhuan Niu; Jie Chen; Ping Wang; Hui Zhou; Song Li; Mengyuan Zhang (Cell Biochemistry and Biophysics, 2014)

Comparative genetic mapping and genomic region collinearity analysis of the powdery mildew resistance gene Pm41 - Zhenzhong Wang; Yu Cui; Yongxing Chen; Deyun Zhang; Yong Liang; Dong Zhang; Qiuhong Wu; Jingzhong Xie; Shuhong Ouyang; Delin Li; Yinlian Huang; Ping Lu; et al. (Theoretical and Applied Genetics, 2014)

Influence of ciprofloxacin on microbial community structure and function in soils - Hao Cui; Shu-Ping Wang; Jin Fu; Zhi-Qiang Zhou; Na Zhang; Li Guo (Biology and Fertility of Soils, 2014)

Bimodal voltage dependence of TRPA1: mutations of a key pore helix residue reveal strong intrinsic voltage-dependent inactivation - Xia Wan; Yungang Lu; Xueqin Chen; Jian Xiong; Yuanda Zhou; Ping Li; Bingqing Xia; Min Li; Michael X. Zhu; Zhaobing Gao (Pflügers Archiv - European Journal of Physiology, 2014)

Solid-phase extraction for selective determination of bisphenol A in drinks and fruits by dummy surface molecularly imprinted polymer with direct synthetic method - Jin Li; Hong Zhou; Yu-Xin Liu; Xiang-Yang Yan; Ye-Ping Xu; Shao-Min Liu (Food Additives & Contaminants: Part A, 2014)

Wnt-promoted Isl1 expression through a novel TCF/LEF1 binding site and H3K9 acetylation in early stages of cardiomyocyte differentiation of P19CL6 cells - Huafei Lu; Yanming Li; Yang Wang; Yinan Liu; Weiping Wang; Zhuqing Jia; Ping Chen; Kangtao Ma; Chunyan Zhou (Molecular and Cellular Biochemistry, 2014)

Infection of Prions and Treatment of PrP106–126 Alter the Endogenous Status of Protein 14-3-3 and Trigger the Mitochondrial Apoptosis Possibly via Activating Bax Pathway - Qi Shi; Qin-Qin Song; Peng Sun; Jin Zhang; Juan Song; Li-Na Chen; Kang Xiao; Shao-Bin Wang; Ya-Zhou Zhang; Gong-Qi Li; Lin-Jun Sheng; Bao-Dong Wang; et al. (Molecular Neurobiology, 2014)

Ice thickness, volume and subglacial topography of Urumqi Glacier No. 1, Tianshan mountains, central Asia, by ground penetrating radar survey - PUYU WANG; ZHONGQIN LI; SHUANG JIN; PING ZHOU; HONGBING YAO; WENBIN WANG (Journal of Earth System Science, 2014)

Geochronology and geochemistry of the Late Triassic Longtan pluton in South China: termination of the crustal melting and Indosinian orogenesis - Liang Qiu; Dan-Ping Yan; Mei-Fu Zhou; Nicholas T. Arndt; Shuang-Li Tang; Liang Qi (International Journal of Earth Sciences, 2014)

Effect of Zinc-Bearing Zeolite Clinoptilolite on Growth Performance, Nutrient Retention, Digestive Enzyme Activities, and Intestinal Function of Broiler Chickens - Zhigang Tang; Chao Wen; Ping Li; Tian Wang; Yanmin Zhou (Biological Trace Element Research, 2014)

Photosynthetic activity and efficiency of Bothriochloa ischaemum and Lespedeza davurica in mixtures across growth periods under water stress - Wei-Zhou Xu; Xi-Ping Deng; Bing-Cheng Xu; Zhi-Juan Gao; Wen-Li Ding (Acta Physiologiae Plantarum, 2014)

Antitumor Activity of Gemcitabine Can Be Potentiated in Pancreatic Cancer through Modulation of TLR4/NF-κB signaling by 6-Shogaol - Ling Zhou; Lianwen Qi; Lifeng Jiang; Ping Zhou; Jiang Ma; Xiaojun Xu; Ping Li (The AAPS Journal, 2014)

Characteristics of gas disaster in the Huaibei coalfield and its control and development technologies - Liang Wang; Yuan-ping Cheng; Feng-hua An; Hong-xing Zhou; Sheng-li Kong; Wei Wang (Natural Hazards, 2014)

Mas-related G protein-coupled receptor D is coupled to endogenous calcium-activated chloride channel in Xenopus oocytes - Ren-Gong Zhuo; Xiao-Yun Ma; Pei-Lan Zhou; Xiao-Yan Liu; Kang Zhang; Xiao-Li Wei; Hai-Tao Yan; Jiang-Ping Xu; Jian-Quan Zheng (Journal of Physiology and Biochemistry, 2014)

Anchored periplasmic expression (APEx)-based bacterial display for rapid and high-throughput screening of B cell epitopes - Mo Guo; Li-Ming Xu; Bing Zhou; Jie-Chao Yin; Xian-Long Ye; Gui-Ping Ren; De-Shan Li (Biotechnology Letters, 2014)

Elevated Cerebral Cortical CD24 Levels in Patients and Mice with Traumatic Brain Injury: A Potential Negative Role in Nuclear Factor Kappa B/Inflammatory Factor Pathway - Wei Li; Hai-Ping Ling; Wan-Chun You; Huan-Dong Liu; Qing Sun; Meng-Liang Zhou; Wei Shen; Jin-Bing Zhao; Lin Zhu; Chun-Hua Hang (Molecular Neurobiology, 2014)

Analysis of the promoter region of the RuBisCO gene of Arthrospira (Spirulina) platensis - Peizhen Li; Liang Zhao; Xiaomin Xu; Chenyang Xu; Chunlei Jin; Yi Xu; Jiaopeng Zhou; Ying Zhang; Kangfu Lei; Jun Ying; Ping Ren; Lei Yang; et al. (Journal of Applied Phycology, 2014)

Preparation and Pharmacokinetic Study of Aprepitant–Sulfobutyl Ether-β-Cyclodextrin Complex - Lili Ren; Yu Zhou; Ping Wei; Min Li; Guoguang Chen (AAPS PharmSciTech, 2014)

Organic carbon mineralization responses to temperature increases in subtropical paddy soils - Ping Zhou; Yong Li; Xiu’e Ren; He’ai Xiao; Chengli Tong; Tida Ge; Philip C. Brookes; Jianlin Shen; Jinshui Wu (Journal of Soils and Sediments, 2014)

Morin Inhibits Sortase A and Subsequent Biofilm Formation in Streptococcus mutans - Ping Huang; Ping Hu; Su Yun Zhou; Qian Li; Wei Min Chen (Current Microbiology, 2014)

Diversity and abundance of the arsenite oxidase gene aioA in geothermal areas of Tengchong, Yunnan, China - Zhou Jiang; Ping Li; Dawei Jiang; Geng Wu; Hailiang Dong; Yanhong Wang; Bing Li; Yanxin Wang; Qinghai Guo (Extremophiles, 2014)

Chromium level and intake from Chinese made tea - Wei-hao Li; Hai-ping Zhou; Ning Li; Sai-di Wang; Xiao-juan Liu; Zeng-jun Jin; Yan-zhen Bu; Zhi-xue Liu (Food Additives & Contaminants Part B-Surveillance, 2013)

Regulation of Autophagy and Ubiquitinated Protein Accumulation by bFGF Promotes Functional Recovery and Neural Protection in a Rat Model of Spinal Cord Injury - Hong-Yu Zhang; Zhou-Guang Wang; Fen-Zan Wu; Xiao-Xia Kong; Jie Yang; Bei-Bei Lin; Shi-Ping Zhu; Li Lin; Chao-Shi Gan; Xiao-Bing Fu; Xiao-Kun Li; Hua-Zi Xu; et al. (Molecular Neurobiology, 2013)

Damage and Permeability Development in Coal During Unloading - Hai-Dong Chen; Cheng Yuan-Ping; Hong-Xing Zhou; Wei Li (Rock Mechanics and Rock Engineering, 2013)

Identification of wheat-Secale africanum chromosome 2Rafr introgression lines with novel disease resistance and agronomic characteristics - Meng-Ping Lei; Guang-Rong Li; Li Zhou; Cheng-Hui Li; Cheng Liu; Zu-Jun Yang (Euphytica, 2013)

Protective Effect of FTY720 Against Sevoflurane-Induced Developmental Neurotoxicity in Rats - Hui Zhou; Song Li; Xinhuan Niu; Ping Wang; Junnan Wang; Mengyuan Zhang (Cell Biochemistry and Biophysics, 2013)

Genetic variability and evolution of rice stripe virus - Ling-zhe Huang; Li-xia Rao; Xue-ping Zhou; Jian-xiang Wu (Journal of Zhejiang University-SCIENCE B, 2013)

Immunologic Mechanism of Patchouli Alcohol Anti-H1N1 Influenza Virus May Through Regulation of the RLH Signal Pathway In Vitro - Xian-Lin Wu; Da-Hong Ju; Jia Chen; Bin Yu; Kang-Li Liu; Jin-Xiong He; Cong-Qi Dai; Sha Wu; Zhou Chang; You-Ping Wang; Xiao-Yin Chen (Current Microbiology, 2013)

Abundance and diversity of archaeal accA gene in hot springs in Yunnan Province, China - Zhao-Qi Song; Li Wang; Feng-Ping Wang; Hong-Chen Jiang; Jin-Quan Chen; En-Min Zhou; Feng Liang; Xiang Xiao; Wen-Jun Li (Extremophiles, 2013)

Stereoselective syntheses of functionalized spirocyclopenteneoxindoles via triphenylphosphine-catalyzed [3+2] cycloaddition reactions - Qing-Fa Zhou; Xue-Ping Chu; Fei-Fei Ge; Cheng Li; Tao Lu (Molecular Diversity, 2013)

Promotion of autophagy at the maturation step by IL-6 is associated with the sustained mitogen-activated protein kinase/extracellular signal-regulated kinase activity - Xue-zhong Li; Chen-yan Sui; Qiang Chen; Xiong-peng Chen; Hong Zhang; Xiao-ping Zhou (Molecular and Cellular Biochemistry, 2013)

β-Glucanase specific expression in the parotid gland of transgenic mice - Li-zheng Guan; Yu-ping Sun; Qian-yun Xi; Jing-lan Wang; Jun-yun Zhou; Gang Shu; Qing-yan Jiang; Yong-liang Zhang (Transgenic Research, 2013)

Ecto-5′-nucleotidase (CD73) promotes tumor angiogenesis - Li Wang; Shaoxian Tang; Yingjian Wang; Siguang Xu; Jerry Yu; Xiuling Zhi; Zhouluo Ou; Jiayin Yang; Ping Zhou; Zhimin Shao (Clinical & Experimental Metastasis, 2013)

Musca Domestica Larva Lectin Induces Apoptosis in BEL-7402 Cells Through a Ca2+/JNK-mediated Mitochondrial Pathway - Chun-Ling Wang; Yan Xia; Jian-Zeng Nie; Minghui Zhou; Rong-Ping Zhang; Li-Li Niu; Li-Hua Hou; Xiao-Hong Cao (Cell Biochemistry and Biophysics, 2013)

The presence of Genogroup II Norovirus in Retail Shellfish from Seven Coastal Cities in China - Li-ping Ma; Feng Zhao; Lin Yao; Xin-guang Li; De-qing Zhou; Rui-ling Zhang (Food and Environmental Virology, 2013)

Bacterial and archaeal diversities in Y unnan and T ibetan hot springs, C hina - Zhao‐Qi Song; Feng‐Ping Wang; Xiao‐Yang Zhi; Jin‐Quan Chen; En‐Min Zhou; Feng Liang; Xiang Xiao; Shu‐Kun Tang; Hong‐Chen Jiang; Chuanlun L. Zhang; Hailiang Dong; Wen‐Jun Li (Environmental Microbiology, 2013)
Summary Thousands of hot springs are located in the north‐eastern part of the Y unnan– T ibet geothermal zone, which is one of the most active geothermal areas in the world. However, a comprehensive and detailed understanding of microbial diversity in these hot springs is still lacking. In this study, bacterial and archaeal diversities were investigated in 16 hot springs ( pH 3.2–8.6; temperature 47–96° C ) in Y unnan P rovince and T ibet, C hina by using a barcoded 16 S rRNA gene‐pyrosequencing approach. A quificae , P roteobacteria , F irmicutes , D einococcus‐ T hermus and B acteroidetes comprised the large portion of the bacterial communities in acidic hot springs. Non‐acidic hot springs harboured more and variable bacterial phyla than acidic springs. D esulfurococcales and unclassified C renarchaeota were the dominated groups in archaeal populations from most of the non‐acidic hot springs; whereas, the archaeal community structure in acidic hot springs was simpler and characterized by S ulfolobales and T hermoplasmata . The phylogenetic analyses showed that A quificae and C renarchaeota were predominant in the investigated springs and possessed many phylogenetic lineages that have never been detected in other hot springs in the world. Thus findings from this study significantly improve our understanding of microbial diversity in terrestrial hot springs.

Increasing phosphorus limitation along three successional forests in southern China - Wenjuan Huang; Juxiu Liu; Ying Ping Wang; Guoyi Zhou; Tianfeng Han; Yin Li (Plant and Soil, 2013)

Analysis of selected singleton transposable elements (SSTEs) and their application for the development of land PATE markers in Magnaporthe oryzae - Hong-yan Zhang; Dong-yang He; Teerapong Kasetsomboon; Heng Zhou; Ping Li; Xiang-long Li; Chatchawan Jantasuriyarat; Bo Zhou (Journal of General Plant Pathology, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Ventral medial prefrontal functional connectivity and emotion regulation in chronic schizophrenia: A pilot study - Feng-Mei Fan; Shu-Ping Tan; Fu-De Yang; Yun-Long Tan; Yan-Li Zhao; Nan Chen; Bin-Bin Li; Chong-Sheng Song; Yun-Hui Wang; Zhen Jin; Dong-Feng Zhou; Michael P. Milham; et al. (Neuroscience Bulletin, 2013)

Wnt/β-catenin signaling induces the aging of mesenchymal stem cells through promoting the ROS production - Da-yong Zhang; Yu Pan; Chong Zhang; Bing-xi Yan; Shan-shan Yu; Dong-ling Wu; Meng-meng Shi; Kai Shi; Xin-xiao Cai; Shuang-shuang Zhou; Jun-bo Wang; Jian-ping Pan; et al. (Molecular and Cellular Biochemistry, 2013)

Fractal characteristics and stability of soil aggregates in karst rocky desertification areas - Yiqun Tang; Jun Li; Xiaohui Zhang; Ping Yang; Jianxiu Wang; Nianqing Zhou (Natural Hazards, 2013)

Biomass accumulation and partitioning, photosynthesis, and photosynthetic induction in field-grown maize (Zea mays L.) under low- and high-nitrogen conditions - Jun-Wen Chen; Zhi-Qing Yang; Ping Zhou; Mei-Rong Hai; Tian-Xiang Tang; Yan-Li Liang; Tong-Xin An (Acta Physiologiae Plantarum, 2013)

Rapid odor perception in rat olfactory bulb by microelectrode array - Jun Zhou; Qi Dong; Liu-jing Zhuang; Rong Li; Ping Wang (Journal of Zhejiang University-SCIENCE B, 2012)

Influence of UDP-glucuronosyltransferase polymorphisms on valproic acid pharmacokinetics in Chinese epilepsy patients - Xiao-Man Chu; Li-Fang Zhang; Guang-Ji Wang; Shen-Ning Zhang; Jia-Hui Zhou; Hai-Ping Hao (European Journal of Clinical Pharmacology, 2012)

Correlation between serum CA724 and gastric cancer: multiple analyses based on Chinese population - Xin-Zu Chen; Wei-Ke Zhang; Kun Yang; Lan-Lan Wang; Jin Liu; Li Wang; Jian-Kun Hu; Bo Zhang; Zhi-Xin Chen; Jia-Ping Chen; Zong-Guang Zhou; Xian-Ming Mo (Molecular Biology Reports, 2012)

The expression of pentraxin 3 and tumor necrosis factor-alpha is increased in preeclamptic placental tissue and maternal serum - Ping Zhou; Xin Luo; Hong-bo Qi; Wen-jun Zong; Hua Zhang; Dan-dan Liu; Qing-shu Li (Inflammation Research, 2012)

Analyses of n-alkanes degrading community dynamics of a high-temperature methanogenic consortium enriched from production water of a petroleum reservoir by a combination of molecular techniques - Lei Zhou; Kai-Ping Li; Serge Maurice Mbadinga; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (Ecotoxicology, 2012)

Highly Sensitive Detection of Residual Chlorpromazine Hydrochloride with Solid Substrate Room Temperature Phosphorimetry - Jia-Ming Liu; Li-ping Lin; Xin-Xing Wang; Xuan Lin; Ping Zhou; Shao-Qin Lin; Zhi-Yong Zheng (Journal of Fluorescence, 2012)

Polymorphisms in the XPG gene and risk of gastric cancer in Chinese populations - Jing He; Li-Xin Qiu; Meng-Yun Wang; Rui-Xi Hua; Ruo-Xin Zhang; Hong-Ping Yu; Ya-Nong Wang; Meng-Hong Sun; Xiao-Yan Zhou; Ya-Jun Yang; Jiu-Cun Wang; Li Jin; et al. (Human Genetics, 2012)

Genomic organization and sequence dynamics of the AvrPiz-t locus in Magnaporthe oryzae - Ping Li; Bin Bai; Hong-yan Zhang; Heng Zhou; Bo Zhou (Journal of Zhejiang University-SCIENCE B, 2012)

Prevention and treatment of allergic inflammation by an Fcγ-Der f2 fusion protein in a murine model of dust mite-induced asthma - Li-hui Lin; Ping Zheng; John W. M. Yuen; Juan Wang; Juan Zhou; Cun-quan Kong; Xia Peng; Jia Li; Li Li (Immunologic Research, 2012)

A role for anti-CD45RB monoclonal antibody treatment upon dendritic cells - Hui Qi; Jin-Peng Liu; Chun-Yan Deng; Han-Xin Zhou; Shao-Ping Deng; Fu-Rong Li (Immunologic Research, 2012)

Identification of a new Bombyx mori nucleopolyhedrovirus and analysis of its bro gene family - Jing-Bo Zhou; Xing-Qi Li; Wanchai De-Eknamkul; Siripuk Suraporn; Jia-Ping Xu (Virus Genes, 2012)

Proteomic Analysis of Osmotic Stress-Responsive Proteins in Sugarcane Leaves - Gui Zhou; Li-Tao Yang; Yang-Rui Li; Cheng-Lin Zou; Li-Ping Huang; Li-Hang Qiu; Xing Huang; Manoj Kumar Srivastava (Plant Molecular Biology Reporter, 2012)

Genetic Overlap in the Quantitative Resistance of Rice at the Seedling and Adult Stages to Xanthomonas oryzae pv. oryzae - Yong-Li Zhou; Xue-Wen Xie; Mei-Rong Xu; Jin-Ping Zang; Ling-Hua Zhu; Jian-Long Xu; Zhi-Kang Li (Journal of Plant Biology, 2012)

At-line monitoring of key parameters of nisin fermentation by near infrared spectroscopy, chemometric modeling and model improvement - Wei-Liang Guo; Yi-Ping Du; Yong-Can Zhou; Shuang Yang; Jia-Hui Lu; Hong-Yu Zhao; Yao Wang; Li-Rong Teng (World Journal of Microbiology and Biotechnology, 2012)

Begomovirus–whitefly mutualism is achieved through repression of plant defences by a virus pathogenicity factor - TONG ZHANG; JUN‐BO LUAN; JIN‐FENG QI; CHANG‐JUN HUANG; MENG LI; XUE‐PING ZHOU; SHU‐SHENG LIU (Molecular Ecology, 2012)
Plant‐mediated interactions between herbivorous arthropods and pathogens transmitted by herbivores are important determinants of the population dynamics of both types of organisms in the field. The role of plant defence in mediating these types of tripartite interactions have been recognized but rarely examined especially at the physiological and molecular levels. Our previous work shows that a worldwide invasive whitefly can establish mutualism with the begomovirus Tomato yellow leaf curl China virus (TYLCCNV) via crop plants. Here, we show that TYLCCNV and betasatellite co‐infection suppresses jasmonic acid defences in the plant. Impairing or enhancing defences mediated by jasmonic acid in the plant enhances or depresses the performance of the whitefly. We further demonstrate that the pathogenicity factor βC1 encoded in the betasatellite is responsible for the initiation of suppression on plant defences and contributes to the realization of the virus–vector mutualism. By integrating ecological, mechanistic and molecular approaches, our study reveals a major mechanism of the plant‐mediated mutualism between a virus and its vector. As the test plant is an important economic crop, the results also have substantial implications for developing novel strategies for management of crop viruses and the insect vectors associated with them.

The reduction of reactive oxygen species formation by mitochondrial alternative respiration in tomato basal defense against TMV infection - Yang-Wen-Ke Liao; Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; De-Kun Dong; Yu-Ping Jiang; Yan-Hong Zhou; Xiao-Jian Xia; Wu-Sheng Liang; Jing-Quan Yu (Planta, 2012)

Analysis of indica- and japonica-specific markers of Oryza sativa and their applications - Xiao-Jun Dai; Yuan-Zhu Yang; Liang Zhou; Li-Jun Ou; Man-Zhong Liang; Wen-Jia Li; Gong-Ping Kang; Liang-Bi Chen (Plant Systematics and Evolution, 2012)

Transcriptional control of human CD2AP expression: the role of Sp1 and Sp3 - Hua-Guo Xu; Wei Ren; Li Zou; Yi Wang; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2012)

Involvement of KATP/PI3K/AKT/Bcl-2 Pathway in Hydrogen Sulfide-induced Neuroprotection Against the Toxicity of 1-methy-4-phenylpyridinium Ion - Xiao-Qing Tang; Yuan-Yuan Zhuang; Li-Li Fan; Heng-Rong Fang; Cheng-Fang Zhou; Ping Zhang; Bi Hu (Journal of Molecular Neuroscience, 2012)

Speciation in the Rana chensinensis species complex and its relationship to the uplift of the Qinghai–Tibetan Plateau - WEI‐WEI ZHOU; YANG WEN; JINZHONG FU; YONG‐BIAO XU; JIE‐QIONG JIN; LI DING; MI‐SOOK MIN; JING CHE; YA‐PING ZHANG (Molecular Ecology, 2012)
Speciation remains a fundamental issue in biology. Herein, we report an investigation into speciation in the Rana chensinensis species complex using DNA sequence data from one mitochondrial and five nuclear genes. A phylogenetic analysis of the data revealed four major clades in the complex, and each of them was found to likely represent a species, including one cryptic species. Ecological niche models were generated from 19 climatic variables for three of the four major clades, which were represented by widespread sampling, including R. chensinensis , Rana kukunoris and the potential cryptic species. Each clade is associated with a unique ecological unit, and this indicates that ecological divergence probably drove speciation. Ecological divergence is likely related to the late Cenozoic orogenesis of the Qinghai–Tibetan Plateau. In addition, gene flow between species was detected but only in peripheral portions of the ranges of the four major clades, thus likely had little influence on the speciation processes. Discordances between mitochondrial and nuclear genes were also found; the nominal species, R. chensinensis , contains multiple maternal clades, suggesting potential mitochondrial introgression between R. chensinensis and R. kukunoris .

Chaiqin Chengqi Decoction decreases IL-6 levels in patients with acute pancreatitis - Ling Wang; Yuan Li; Qin Ma; Yong Liu; Yuan-yi Rui; Ping Xue; Zong-guang Zhou (Journal of Zhejiang University-SCIENCE B, 2011)

Erratum to: Effects of proNGF on Neuronal Viability, Neurite Growth and Amyloid-beta Metabolism - Yan-Jiang Wang; Deborah Valadares; Ying Sun; Xin Wang; Jin-Hua Zhong; Xiao-Hong Liu; Shohreh Majd; Li Chen; Chang-Yue Gao; Si Chen; Yoon Lim; Anthony Pollard; et al. (Neurotoxicity Research, 2011)

The Activation of NMDA Receptor–ERK Pathway in the Central Amygdala is Required for the Expression of Morphine-Conditioned Place Preference in the Rat - Fang Li; Xiao-Sheng Wang; Ru-Ping Dai; Jian-Yi Zhang; Xin-Fu Zhou; Wei Hao; Chang-Qi Li (Neurotoxicity Research, 2011)

Characterization of a novel isoform of the human ORMDL3 gene - Rui Jin; Wen-Xiao Yuan; Hua-Guo Xu; Wei Ren; Li-Li Zhuang; Guo-Ping Zhou (Cell and Tissue Research, 2011)

The characterization of two novel IRF-3 transcripts starting from intron 2 of the wild type of IRF-3 - Wei Ren; Hua-Guo Xu; Chao Lu; Rui Jin; Li Zou; Yi Wang; Guo-Ping Zhou (Molecular Biology Reports, 2011)

Transumbilical single-port laparoscopic cholecystectomy using traditional laparoscopic instruments: a report of thirty-six cases - Li-ping Cao; Ri-sheng Que; Fan Zhou; Guo-ping Ding; De-xi Jing (Journal of Zhejiang University-SCIENCE B, 2011)

Prevalence, intensity and associated factor analysis of Tropilaelaps mercedesae infesting Apis mellifera in China - Qi Hua Luo; Ting Zhou; Ping Li Dai; Huai Lei Song; Yan Yan Wu; Qiang Wang (Experimental and Applied Acarology, 2011)

Aboveground dominant functional group predicts belowground properties in an alpine grassland community of western China - Gao-Lin Wu; Wei Li; Zhi-Hua Shi; Zhou-Ping Shangguan (Journal of Soils and Sediments, 2011)

Ion chemistry and individual particle analysis of atmospheric aerosols over Mt. Bogda of eastern Tianshan Mountains, Central Asia - Shuhui Zhao; Zhongqin Li; Ping Zhou (Environmental Monitoring and Assessment, 2011)

Diagnostic value of amplitude-integrated electroencephalogram in neonatal seizures - Lian Zhang; Yan-Xia Zhou; Li-Wen Chang; Xiao-Ping Luo (Neuroscience Bulletin, 2011)

Levels and Congener Profiles of Particle-bound Polybrominated Dibenzo-p-dioxins/furans (PBDD/Fs) in Ambient Air around Guangzhou, China - Huiru Li; Lin Zhou; Ligui Mo; Ping’an Peng; Guoying Sheng; Jiamo Fu; Zhiqiang Yu (Bulletin of Environmental Contamination and Toxicology, 2011)

Novel Fluorescent Molecular Clips: Selective Recognition Towards Fe3+ in Aqueous Solution - Lin Li; Neng-fang She; Zhuan Fei; Pui-kin So; Yu-zhou Wang; Li-ping Cao; An-xin Wu; Zhong-ping Yao (Journal of Fluorescence, 2011)

Single amino acid residue changes in subsite −1 of levansucrase from Zymomonas mobilis 10232 strongly influence the enzyme activities and products - Shuying Li; Yongliang Yan; Zhengfu Zhou; Haiying Yu; Yuhua Zhan; Wei Zhang; Ming Chen; Wei Lu; Shuzhen Ping; Min Lin (Molecular Biology Reports, 2011)

Genistein alters caffeine exposure in healthy female volunteers - Yao Chen; Chang-Qiong Xiao; Yi-Jing He; Bi-Lian Chen; Guo Wang; Gan Zhou; Wei Zhang; Zhi-Rong Tan; Shan Cao; Li-Ping Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2011)

Direct repression of the human IRF-3 promoter by E2F1 - Hua-Guo Xu; Wei Ren; Li Zou; Yi Wang; Rui Jin; Guo-Ping Zhou (Immunogenetics, 2011)

An improved Markov chain model based on autocorrelation and entropy techniques and its application to state prediction of water resources - Ping Zhou; Yuliang Zhou; Juliang Jin; Li Liu; Zongzhi Wang; Liang Cheng; Libing Zhang (Chinese Geographical Science, 2011)

Cytosolic PrP Induces Apoptosis of Cell by Disrupting Microtubule Assembly - Xiao-Li Li; Gui-Rong Wang; Yuan-Yuan Jing; Ming-Ming Pan; Chen-Fang Dong; Rui-Min Zhou; Zhao-Yun Wang; Qi Shi; Chen Gao; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Human Prion Protein Mutants with Deleted and Inserted Octarepeats Undergo Different Pathways to Trigger Cell Apoptosis - Kun Xu; Xin Wang; Qi Shi; Cao Chen; Chan Tian; Xiao-Li Li; Rui-Min Zhou; Yong-Lie Chu; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Abnormal expression and dysfunction of novel SGLT2 mutations identified in familial renal glucosuria patients - Lei Yu; Ji-Cheng Lv; Xu-jie Zhou; Li Zhu; Ping Hou; Hong Zhang (Human Genetics, 2011)

Development and application of an efficient virus-induced gene silencing system in Nicotiana tabacum using geminivirus alphasatellite - Chang-jun Huang; Tong Zhang; Fang-fang Li; Xin-yue Zhang; Xue-ping Zhou (Journal of Zhejiang University-SCIENCE B, 2011)

Single-step chromatography for simultaneous purification of C-phycocyanin and allophycocyanin with high purity and recovery from Spirulina (Arthrospira) platensis - Shi-Gan Yan; Li-Ping Zhu; Hai-Nan Su; Xi-Ying Zhang; Xiu-Lan Chen; Bai-Cheng Zhou; Yu-Zhong Zhang (Journal of Applied Phycology, 2011)

Enhanced V-ATPase activity contributes to the improved salt tolerance of transgenic tobacco plants overexpressing vacuolar Na+/H+ antiporter AtNHX1 - Shufeng Zhou; Zhiming Zhang; Qilin Tang; Hai Lan; Yinxin Li; Ping Luo (Biotechnology Letters, 2011)

Microwave irradiation synthesis of novel ramose chitosan-based-5-fluorouracil and research on its in vitro release - He-Ping Li; Zhou-dong Wang; Tao Yu (Medicinal Chemistry Research, 2011)

Molecular cytogenetic identification of a new wheat-Thinopyrum substitution line with stripe rust resistance - Li-Jun Hu; Guang-Rong Li; Zi-Xian Zeng; Zhi-Jian Chang; Cheng Liu; Jian-Ping Zhou; Zu-Jun Yang (Euphytica, 2011)

Effect of high glucose levels on the calcification of vascular smooth muscle cells by inducing osteoblastic differentiation and intracellular calcium deposition via BMP-2/Cbfα-1 pathway - Fang Liu; Hui Zhong; Jing-yuan Liang; Ping Fu; Zhi-juan Luo; Li Zhou; Rong Gou; Jun Huang (Journal of Zhejiang University-SCIENCE B, 2010)

Characterization of the biochemical properties and identification of amino acids forming the catalytic center of 3C-like proteinase of porcine reproductive and respiratory syndrome virus - Ao-Tian Xu; Yan-Jun Zhou; Guo-Xin Li; Hai Yu; Li-Ping Yan; Guang-Zhi Tong (Biotechnology Letters, 2010)

Characterization of human embryonic stem cell-derived hematopoietic progenitor phenotype - Hai-Yang Zhou; Xiao-Yi Yang; Li-Jian Tao; Yue-Tian Chang; Ru-Ping Dai (In Vitro Cellular & Developmental Biology - Animal, 2010)

Application of collagen-chitosan/fibrin glue asymmetric scaffolds in skin tissue engineering - Chun-mao Han; Li-ping Zhang; Jin-zhang Sun; Hai-fei Shi; Jie Zhou; Chang-you Gao (Journal of Zhejiang University-SCIENCE B, 2010)

Isolation and characterization of an abamectin-degrading Burkholderia cepacia-like GB-01 strain - Shinawar Waseem Ali; Rong Li; Wei-you Zhou; Ji-quan Sun; Peng Guo; Ji-ping Ma; Shun-peng Li (Biodegradation, 2010)

Association Analysis of the RET Proto-Oncogene with Hirschsprung Disease in the Han Chinese Population of Southeastern China - Cui-Ping Liu; Qian-Qian Tang; Jin-Tu Lou; Chun-Fen Luo; Xue-Wu Zhou; Dong-Mei Li; Fei Chen; Xiang Li; Ji-Cheng Li (Biochemical Genetics, 2010)

Prestack Gaussian beam depth migration under complex surface conditions - Yu-Bo Yue; Zhen-Chun Li; Ping Zhang; Xue-Feng Zhou; Ning Qin (Applied Geophysics, 2010)

Effects of Ginkgo biloba extracts on diazepam metabolism: a pharmacokinetic study in healthy Chinese male subjects - Xiao-Cong Zuo; Bi-Kui Zhang; Su-Jie Jia; Shi-Kun Liu; Ling-Yun Zhou; Jing Li; Jie Zhang; Ling-Ling Dai; Ben-Mei Chen; Guo-Ping Yang; Hong Yuan (European Journal of Clinical Pharmacology, 2010)

Polybrominated diphenyl ethers in background surface soils from the Yangtze River Delta (YRD), China: occurrence, sources, and inventory - Yan-Ping Duan; Xiang-Zhou Meng; Chao Yang; Zhao-Yu Pan; Ling Chen; Ran Yu; Feng-Ting Li (Environmental Science and Pollution Research, 2010)

Effects of proNGF on Neuronal Viability, Neurite Growth and Amyloid-beta Metabolism - Yan-Jiang Wang; Deborah Valadares; Ying Sun; Xin Wang; Jin-Hua Zhong; Xiao-Hong Liu; Shohreh Majd; Li Chen; Chang-Yue Gao; Si Chen; Yoon Lim; Anthony Pollard; et al. (Neurotoxicity Research, 2010)

Allopatric divergence and phylogeographic structure of the plateau zokor ( Eospalax baileyi ), a fossorial rodent endemic to the Qinghai–Tibetan Plateau - Li‐Zhou Tang; Liu‐Yang Wang; Zhen‐Yuan Cai; Tong‐Zuo Zhang; Hai‐Xin Ci; Gong‐Hua Lin; Jian‐Ping Su; Jian‐Quan Liu (Journal of Biogeography, 2010)
Aim Most species of temperate regions are believed to have shifted to lower latitudes or elevations during the glacial periods of the Quaternary. In this study we test whether this phylogeographic assumption is also true for the plateau zokor ( Eospalax baileyi ), a fossorial rodent endemic to the climate‐sensitive Qinghai–Tibetan Plateau (QTP), which ranges in elevation from 2600 to 4600 m. Location The QTP of western China. Methods Phylogeographic analyses were conducted based on the mitochondrial cytochrome b gene sequences of 193 individuals from 20 populations over the entire range of the species. Results A total of 54 haplotypes identified in the present study clustered into four geographically correlated clades located in the interior of the QTP (clade A) and at the plateau edge (B, C and D). Molecular calibrations suggest that the interior plateau (A) and plateau‐edge (B–D) clades diverged at 1.2 Ma and that the three plateau‐edge clades diverged between 0.85 and 0.80 Ma. These estimates are concordant with diastrophism and glaciation events in the QTP. Coalescent tests rejected both the hypothesis that all current populations originated from a single refugium at a low elevation during the Last Glacial Maximum (LGM) and the hypothesis that the two lineages diverged during the LGM. The tests instead supported the hypothesis that there were four refugia during the LGM, and that the four clades diverged prior to the late Pleistocene. Main conclusions Our results suggest that Quaternary diastrophisms and glaciations repeatedly promoted allopatric divergence of the plateau zokor into geographical clades, and that these regional clades subsequently persisted at high elevations, rather than migrating to the low‐elevation plateau edge during subsequent glacial ages.

Prediction of summer grain crop yield with a process-based ecosystem model and remote sensing data for the northern area of the Jiangsu Province, China - Weimin Ju; Ping Gao; Yanlian Zhou; Jing M. Chen; Shu Chen; Xianfeng Li (International Journal of Remote Sensing, 2010)

Viral infection of tobacco plants improves performance of Bemisia tabaci but more so for an invasive than for an indigenous biotype of the whitefly - Jian Liu; Meng Li; Jun-min Li; Chang-jun Huang; Xue-ping Zhou; Fang-cheng Xu; Shu-sheng Liu (Journal of Zhejiang University-SCIENCE B, 2010)

Effects of exogenous annexin-1 on lipopolysaccharide-induced proliferation and reactive oxygen species production partially through modulation of CRAC channels but independent of NF-κB pathway - Lei-Ming Xu; Sheng-Wei Jin; Xiao-Yan Zhou; Ping Wu; Yong-Sheng Li; Li Zhang; Yuan-Yuan Lin; Ying Chen; Du-Yun Ye (Inflammation Research, 2009)

Reciprocal regulation between M3 muscarinic acetylcholine receptor and protein kinase C-ε in ventricular myocytes during myocardial ischemia in rats - Peng-zhou Hang; Jing Zhao; Yu-ping Wang; Li-hua Sun; Yong Zhang; Li-li Yang; Na Zhao; Zhi-dan Sun; Yu-ying Mao; Zhi-min Du (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Manganese-induced changes of the biochemical characteristics of the recombinant wild-type and mutant PrPs - Xiao-Li Li; Chen-Fang Dong; Gui-Rong Wang; Rui-Min Zhou; Qi Shi; Chan Tian; Chen Gao; Guo-Yong Mei; Cao Chen; Kun Xu; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2009)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

Prevalence, genetic diversity, and antimicrobial susceptibility profiles of Staphylococcus aureus isolated from bovine mastitis in Zhejiang Province, China - Jian-ping Li; Hai-jian Zhou; Lin Yuan; Ting He; Song-hua Hu (Journal of Zhejiang University-SCIENCE B, 2009)

The effect of root exudates from two transgenic insect-resistant cotton lines on the growth of Fusarium oxysporum - Xiao-gang Li; Biao Liu; Sondre Heia; Dou-dou Liu; Zheng-min Han; Ke-xin Zhou; Jin-jie Cui; Jun-yu Luo; Yang-ping Zheng (Transgenic Research, 2009)

Insights into the Substrate Specificity, Inhibitors, Regulation, and Polymorphisms and the Clinical Impact of Human Cytochrome P450 1A2 - Shu-Feng Zhou; Li-Ping Yang; Zhi-Wei Zhou; Ya-He Liu; Eli Chan (The AAPS Journal, 2009)

Spatial Filtering Improves EMG Classification Accuracy Following Targeted Muscle Reinnervation - He Huang; Ping Zhou; Guanglin Li; Todd Kuiken (Annals of Biomedical Engineering, 2009)

Selection of scFvs specific for the HepG2 cell line using ribosome display - Lei Zhou; Wei-Ping Mao; Juan Fen; Hong-Yun Liu; Chuan-Jing Wei; Wen-Xiu Li; Feng-Yun Zhou (Journal of Biosciences, 2009)

Study on swelling model and thermodynamic structure of native konjac glucomannan - Long Li; Hui Ruan; Liu-liu Ma; Wei Wang; Ping Zhou; Guo-qing He (Journal of Zhejiang University-SCIENCE B, 2009)

Induction of cytochrome P450 2B6 activity by the herbal medicine baicalin as measured by bupropion hydroxylation - Lan Fan; Jin-Chao Wang; Feng Jiang; Zhi-Rong Tan; Yao Chen; Qing Li; Wei Zhang; Guo Wang; He-Ping Lei; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Cloning and Characterization of the SSB-1 and SSB-4 Genes Expressed in Zebrafish Gonads - Jian-Zhen Li; Ya-Ping Zhou; Yan Zhen; Yan Xu; Peng-Xiang Cheng; Huan-Nan Wang; Feng-Jiao Deng (Biochemical Genetics, 2009)

The CYP2C19 ultra-rapid metabolizer genotype influences the pharmacokinetics of voriconazole in healthy male volunteers - Guo Wang; He-Ping Lei; Zhi Li; Zhi-Rong Tan; Dong Guo; Lan Fan; Yao Chen; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Infectivity and propagation of attenuated infectious bursal disease virus in the chicken B-lymphocyte cell line DT40 - Jun Luo; Gai-Ping Zhang; Jian-Ming Fan; Man Teng; Lei-Ming You; Ling Zhou; Rui-Guang Deng; Xuan-Nian Wang; Yan-Yan Yang; Li Wang; Guang-Xu Xing; Na Cheng (Archives of Virology, 2009)

Determination of soluble solid content and acidity of loquats based on FT-NIR spectroscopy - Xia-ping Fu; Jian-ping Li; Ying Zhou; Yi-bin Ying; Li-juan Xie; Xiao-ying Niu; Zhan-ke Yan; Hai-yan Yu (Journal of Zhejiang University-SCIENCE B, 2009)

Relationships Among Genetic Makeup, Active Ingredient Content, and Place of Origin of the Medicinal Plant Gastrodia Tuber - Jun Tao; Zhi-yong Luo; Chikira Ismail Msangi; Xiao-shun Shu; Li Wen; Shui-ping Liu; Chang-quan Zhou; Rui-xin Liu; Wei-xin Hu (Biochemical Genetics, 2009)

Distribution and Accumulation of Copper and Cadmium in Soil–Rice System as Affected by Soil Amendments - Ping Li; Xing-xiang Wang; Tao-lin Zhang; Dong-mei Zhou; Yuan-qiu He (Water, Air, & Soil Pollution, 2009)

Limestone Dissolution Induced by Fungal Mycelia, Acidic Materials, and Carbonic Anhydrase from Fungi - Wei Li; Peng-Peng Zhou; Li-Ping Jia; Long-Jiang Yu; Xue-Li Li; Min Zhu (Mycopathologia, 2009)

Identification of α-gliadin genes in Dasypyrum in relation to evolution and breeding - Guang-Rong Li; Cheng Liu; Zi-Xian Zeng; Ju-Qing Jia; Tao Zhang; Jian-Ping Zhou; Zheng-Long Ren; Zu-Jun Yang (Euphytica, 2009)

Increased pathogenesis and inflammation of airways from respiratory syncytial virus infection in T cell deficient nude mice - Juan Zhou; Xi-Qiang Yang; Zhou Fu; Xiao-Dong Zhao; Li-Ping Jiang; Li-Jia Wang; Yu-Xia Cui (Medical Microbiology and Immunology, 2008)

Responses to air temperature and soil moisture of growth of four dominant species on sand dunes of central Inner Mongolia - Yuanrun Zheng; Glyn M. Rimmington; Zhixiao Xie; Lei Zhang; Ping An; Guangsheng Zhou; Xiangjun Li; Yunjiang Yu; Lijun Chen; Hideyuki Shimizu (Journal of Plant Research, 2008)

Application of NIR spectroscopy for firmness evaluation of peaches - Xia-ping FU; Yi-bin Ying; Ying Zhou; Li-juan Xie; Hui-rong Xu (Journal of Zhejiang University-SCIENCE B, 2008)

Evidence of Gene Conversion in the Evolutionary Process of the Codon 41/42 (-CTTT) Mutation Causing β-Thalassemia in Southern China - Wen Zhang; Wang-Wei Cai; Wei-Ping Zhou; Hai-Peng Li; Liang Li; Wei Yan; Qin-Kai Deng; Ya-Ping Zhang; Yun-Xin Fu; Xiang-Min Xu (Journal of Molecular Evolution, 2008)

Purification and characterization of a thermostable uricase from Microbacterium sp. strain ZZJ4-1 - Lei Kai; Xiao-Hang Ma; Xue-Lai Zhou; Xiao-Ming Jia; Xia Li; Kang-Ping Guo (World Journal of Microbiology and Biotechnology, 2008)

Reduced expression of GSTM2 and increased oxidative stress in spontaneously hypertensive rat - Si-Gui Zhou; Ping Wang; Rong-Biao Pi; Jie Gao; Jia-Jia Fu; Jian Fang; Jia Qin; Hui-Jie Zhang; Rui-Fang Li; Shao-Rui Chen; Fu-Tian Tang; Pei-Qing Liu (Molecular and Cellular Biochemistry, 2008)

Molecular and functional comparisons of the vacuolar Na+/H+ exchangers originated from glycophytic and halophytic species - Jin-yao Li; Xiao-wei He; Li Xu; Jie Zhou; Ping Wu; Hui-xia Shou; Fu-chun Zhang (Journal of Zhejiang University-SCIENCE B, 2008)

Localization of a novel gene for congenital nonsyndromic simple microphthalmia to chromosome 2q11-14 - Hui Li; Jia-Xin Wang; Cheng-Ye Wang; Ping Yu; Qiang Zhou; Yong-Gang Chen; Lu-Hang Zhao; Ya-Ping Zhang (Human Genetics, 2008)

Isolation of a new repetitive DNA sequence from Secale africanum enables targeting of Secale chromatin in wheat background - Cheng Liu; Zu-Jun Yang; Guang-Rong Li; Zi-Xian Zeng; Yong Zhang; Jian-Ping Zhou; Zhao-Hui Liu; Zheng-Long Ren (Euphytica, 2008)

Genomic analysis of a Chinese isolate of Getah-like virus and its phylogenetic relationship with other Alphaviruses - Jin-Sheng Wen; Wen-Zhong Zhao; Jian-Wei Liu; Hong Zhou; Jian-Ping Tao; Hui-Jun Yan; Yu Liang; Jing-Jiao Zhou; Li-Fang Jiang (Virus Genes, 2007)

Notch activation promotes cell proliferation and the formation of neural stem cell-like colonies in human glioma cells - Xue-Ping Zhang; Gang Zheng; Lian Zou; Hui-Ling Liu; Li-Hong Hou; Peng Zhou; Dan-Dan Yin; Qi-Jun Zheng; Liang Liang; Su-Zhen Zhang; Lei Feng; Li-Bo Yao; et al. (Molecular and Cellular Biochemistry, 2007)

Biodecolorization of Azo Dye Acid Red B under High Salinity Condition - M. Salah Uddin; Jiti Zhou; Yuanyuan Qu; Jianbo Guo; Ping Wang; Li hong Zhao (Bulletin of Environmental Contamination and Toxicology, 2007)

RNA interference of ecto-5′-nucleotidase (CD73) inhibits human breast cancer cell growth and invasion - Xiuling Zhi; Sifeng Chen; Ping Zhou; Zhimin Shao; Li Wang; Zhouluo Ou; Lianhua Yin (Clinical & Experimental Metastasis, 2007)

Successful tubes treatment of esophageal fistula - Ning Zhou; Wei-xing Chen; You-ming Li; Zhun Xiang; Ping Gao; Ying Fang (Journal of Zhejiang University-SCIENCE B, 2007)

Teager–Kaiser Energy Operation of Surface EMG Improves Muscle Activity Onset Detection - Xiaoyan Li; Ping Zhou; Alexander S. Aruin (Annals of Biomedical Engineering, 2007)

Generation of genetic engineering monoclonal antibodies against prion protein - Yin-Xia Huang; Jun Han; Chen-Fang Dong; Li Sun; Chen Gao; Xiao-Fan Wang; Lu Han; Wei Zhou; Bao-Yun Zhang; Hui-Ying Jiang; Mi-Fang Liang; Xiao-Ping Dong (Medical Microbiology and Immunology, 2007)

Genetic Analysis of RET, EDNRB, and EDN3 Genes and Three SNPs in MCS + 9.7 in Chinese Patients with Isolated Hirschsprung Disease - Xian-Ning Zhang; Miao-Ni Zhou; Yun-Qing Qiu; Shi-Ping Ding; Ming Qi; Ji-Cheng Li (Biochemical Genetics, 2007)

Nonlinear coupled analysis of a single point mooring system - Junrong Wang; Huajun Li; Ping Li; Kai Zhou (Journal of Ocean University of China, 2007)

Establishment, Characterization, and Virus Susceptibility of a New Marine Cell Line from Red Spotted Grouper (Epinephelus akaara) - Guang-Zhou Zhou; Zheng-Qiu Li; Xiu-Ping Yuan; Qi-Ya Zhang (Marine Biotechnology, 2007)

Introduction of the PPF1 gene into rice (Oryza sativa L.) results in delayed leaf senescence - Shuangcheng Li; Desuo Yin; Faqiang Wu; Shiquan Wang; Qiming Deng; Youhua Tang; Huaqiang Zhou; Ping Li (Euphytica, 2007)

Apelin suppresses apoptosis of human osteoblasts - Hui Xie; Ling-Qing Yuan; Xiang-Hang Luo; Jiao Huang; Rong-Rong Cui; Li-Juan Guo; Hou-De Zhou; Xian-Ping Wu; Er-Yuan Liao (Apoptosis, 2007)

Determination of Trace Mercury by Solid Substrate-Room Temperature Phosphorimetry Quenching Method Based on Catalytic Effect of Hg2+on Formation of the Ion Association Complex [Sn(XO)6]4+·[(Fin)4] - Jia-Ming Liu; Ruo-Hong Wu; De-Chang Li; Ping Zhou; Min-Min Zheng; Xiao-Yi Zeng; Dong-Xia Liu; Xiao-Mei Huang; Guo-Hui Zhu (Journal of Fluorescence, 2006)

Highly efficient photoactivation of Mn-depleted photosystem II by imidazole-liganded manganese complexes - Bin Liu; Ping Ping Shen; Wei Shi; Yu Guang Song; Wei Li; Zhou Nie; Yang Liu (JBIC Journal of Biological Inorganic Chemistry, 2006)

Characterization of a partial amphiploid between Triticum aestivum cv. Chinese Spring and Thinopyrum intermedium ssp. trichophorum - Yang Zu-Jun; Li Guang-Rong; Chang Zhi-Jian; Zhou Jian-Ping; Ren Zheng-Long (Euphytica, 2006)

Target HCV NS3 CD4+ Th1 Epitope to Major Histocompatibility Complex Class II Pathway - Ming Gao; Hai-Ping Wang; Yan-Ning Wang; Yong Zhou; Quan-Li Wang (Biotechnology Letters, 2006)

Expression of a begomoviral DNAβ gene in transgenic Nicotiana plants induced abnormal cell division - Xiao-feng Cui; Yun-qin Li; Dong-wei Hu; Xue-ping Zhou (Journal of Zhejiang University-SCIENCE B, 2005)

Mapping of quantitative trait loci (QTLs) for rice protein and fat content using doubled haploid lines - Zhong-Li Hu; Ping Li; Ming-Quan Zhou; Zhi-Hong Zhang; Ling-Xia Wang; Li-Huang Zhu; Ying-Guo Zhu (Euphytica, 2004)

Oxidation of elemental sulfur in paddy soils as influenced by flooded condition and plant growth in pot experiment - Wei Zhou; Min Wan; Ping He; Shutian Li; Bao Lin (Biology and Fertility of Soils, 2002)

Spatial changes of wind erosion-caused landscapes and their relation with wind field in China - Zhang Guo-ping; Liu Ji-yuan; Zhang Zeng-xiang; Zhao Xiao-li; Zhou Quan-bin (Journal of Geographical Sciences, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)